Overcoming neoliberal globalization: social-ecological transformation from a Polanyian perspective and beyond - Brand, Ulrich; Görg, Christoph; Wissen, Markus (Globalizations, 2020)
The ecological crisis has intensified in many respects. Prominent proposals to deal with the crisis are discussed under the header 'sustainability transformations' or even 'Great Transformation'. We argue that most contributions suffer from a narrow analytical approach to transformation ignoring the largely unsustainable dynamics of global capitalism and the power relations involved in it. Thus, a 'new critical orthodoxy' of knowledge about transformation is emerging which runs the danger to contribute to a spatially and socially highly uneven green capitalism. This article claims that the current debate on social-ecological transformation can be enriched by a Polanyian understanding but also based on regulation theory. We distinguish between three types of transformation: incremental adaptation of the current institutional systems, institutional change in favour of a new 'green' phase of capitalism, and a post-capitalist great transformation that implies a profound structural change of the mode of production and living.
Keywords: POLANYI, Karl, 1886-1964; capitalism; crises; debates & debating; ecological crisis; globalization; imperial mode of living; nature as fictitious commodity; regulation theory; social ecology; social-ecological transformation; sustainability

The political economy of family policy expansion: Fostering neoliberal capitalism or promoting gender equality supporting social reproduction? - Ferragina, Emanuele (Review of International Political Economy, 2019)
This article presents a new theoretical and empirical approach to understand family policy expansion in relation to the political economy of welfare state retrenchment and social reproduction in 23 OECD countries. From a Polanyian perspective, this expansion can be interpreted as a movement toward commodification and liberalization, and a countermovement of gender liberation. The first movement seems to characterize family policy expansion as a tool to foster neoliberal capitalism and the advent of a Schumpeterian Workfare State, conspiring with welfare state retrenchment to encourage employment within an environment of growing precarization. The second movement appears to assuage the social reproduction crisis. This countermovement seems to act as a cushion to soften the shift from a male income earner toward a dual earner model, supporting working parents in meeting escalating childare costs. Looking at the expansion of childcare spending and the retrenchment of minimum income guarantees for couples with children, an empirical illustration of this concomitant 'double movement' reveals that the first holds sway over the second in most countries. Furthermore, household income and maternal levels of education impact on childcare usage, magnifying the negative distributional consequences of cutting minimum income guarantees in favor of childcare.
Keywords: Schumpeterian workfare state; childcare; commodification; countermovement; family policy; gender equality; neoliberalism; social reproduction; welfare state retrenchment

SEE Beyond Substantive Economics: Avoiding False Dichotomies - Spash, Clive L. (Ecological Economics, 2019)
The proposal has been put forward that ecological economics seek to become substantive economics (Gerber and Scheidel 2018). This raises important issues about the content and direction of ecological economics. The division of economics into either substantive or formal derives from the work of Karl Polanyi. In developing his ideas Polanyi employed a definition from Menger and combined this with Tönnies theory of historical evolution. In this paper I explore why the resulting substantive vs. formal dichotomy is problematic. In particular the article exposes the way in which trying to impose this dichotomy on history of economic thought and epistemology leads to further false dichotomies. Besides Polanyi, the positions of other important thinkers informing social ecological economics (SEE) are discussed including Neurath, Kapp and Georgescu-Roegen. The aim is to clarify the future direction of ecological economics and the role in that future of ideas raised under the topic of substantive economics.
Keywords: economic anthropology; epistemology; formal economics; history of thought; social ecological economics; substantive economics

Karl Polanyi, the "always-embedded market economy," and the re-writing of The Great Transformation - Lacher, Hannes (Theory & Society, 2019)
This article seeks to subject Fred Block and Margaret Somers' influential reconstruction of Karl Polanyi's The Great Transformation to a systematic review. I show that Block & Somers's central claim—that Polanyi's thinking underwent a "theoretical shift" as he wrote his seminal book—is not supported by archival evidence. I demonstrate that all the narrative keys that Block & Somers advance to lend plausibility to their discovery of a "theory of the always-embedded market economy" in The Great Transformation, wither under critical probing. While this article does not advance a comprehensive alternative reconstruction of Polanyi's main work, the essential continuities it uncovers in his social thought suggest that Polanyi's book is best understood as the culmination of his long-standing efforts to rebuild a radically transformative socialism on non-Marxist foundations. The recognition that Polanyi's political purposes extend far beyond regulated capitalism or social-democracy, I conclude, makes it possible—and indeed necessary—to read The Great Transformation as an internally coherent work of social theory.
Keywords: BLOCK, Fred L.; SOMERS, Margaret R.; capitalism and socialism; critical institutionalism; economic sociology; fascism; neo-Polanyian social theory; political economy

Global Cities as Market Civilisation - Curtis, Simon (Global Society: Journal of Interdisciplinary International Relations, 2019)
Building upon interdisciplinary efforts to understand the origins, logic and significance of global cities, this article argues that global cities should be seen as a critical component and outcome of a political project to generate a global market society. Global cities should be seen as the successful implementation of free-market political philosophy, constructed and defended by a particular historical configuration of international society. The historical transformation of urban form signalled by the "global city" concept is tightly bound to the neoliberal restructuring of the world economy in the 1970s, underpinned by US hegemonic power. The first part of this article argues that the distinctive historical origin of global cities has shaped their current trajectories and draws the horizon of their future prospects. Having established the connection between liberal world order and global cities, the second part of the article argues that the contemporary form of the global city is under threat from two sources. The first threat is internal to the global city form itself. Global cities have internalised the contradictory forces of market liberalism. They have registered astonishing economic growth over the last four decades, and generated vast material and intellectual resources. But, at the same time, they have become deeply divided and polarised in ways that threaten the urban fabric. The second source of threat comes from the possible weakening or collapse of liberal world order, with the accelerating decline of US hegemony. Drawing on aspects of Karl Polanyi's analysis of the nineteenth-century "great transformation", the article argues that a number of future trajectories for the global city can be identified in the contemporary moment.
Keywords: global city; market liberalism

Economic Liberalism and the State: Dismantling the Myth of Naïve Laissez-Faire - Stahl, Rune Møller (New Political Economy, 2019)
The article offers a critique of the prevailing understanding of the relationship between neoliberalism and classic nineteenth-century liberalism in contemporary international political economy (IPE) and offers a redefinition inspired by Polanyi and Gramsci. Within critical IPE studies, a consensus has emerged that neoliberalism cannot be reduced to a simple attempt to roll back the economy and let loose free-market forces. However, this insight relies on contrasting neoliberalism with a classic liberalism, that is, a simple attempt to implement just this naïve laissez-faire ideology. In contrast, this article argues that nineteenth-century liberalism is also characterised by an active use of state and legislative power. Through a historical study of two cases from nineteenth-century Britain, Poor Law reform and the Gold Standard, the paper will argue that state action played a central role even during the heyday of laissez-faire liberalism. With a starting point in Polanyi's dictum that 'laissez-faire was planned', this reinvestigation will point towards a need to develop a more nuanced understanding of the distinctions between economic theory, ideology, and practical policy, as well as pointing towards a general reinterpretation of the role of the state in liberal economic ideology.
Keywords: classical liberalism; critical political economy; economic governance; history of economic thought; international political economy; liberalism; liberty; neoconservatism; neoliberalism; ordoliberalism; state theory

Repatriating Polanyi: Market Society in the Visegrad States - Hann, Chris (Central European University Press, 2019)
Karl Polanyi’s “substantivist” critique of market society has renewed topicality in the era of neoliberal globalization. Polanyi (1886–1964) is popular among critical theorists and radical political economists, but also with ecological activists, anti-globalization campaigners and all who sense that ongoing financial turmoil is symptomatic of a deeper crisis threatening the compatibility of capitalism and democracy. The author reclaims the polymath Karl Polanyi for contemporary anthropology, especially economic anthropology. The book furthermore takes his ideas back to Central Europe, where he grew up. The Polanyian approach is applied to the communist economy, with particular reference to the “market socialist” economy which evolved under János Kádár in Hungary. The same lens is used to investigate the consequences of the demise of communist power since 1990, primarily on the basis of ethnographic investigations in Hungary and South-East Poland. Stretching the discussion on Polanyi’s great transformation – for which there is considerable international interest – in the context of neoliberalization onto the concept of Eurasia, and then bringing this into conversation with the rise of neo-nationalism in Hungary and Poland and beyond as the form that the great transformation is currently taking in the region, relates Hann’s work powerfully to the current political turbulence.
Keywords: Hungary; Poland; communist economy; economic history; market socialist economy; neo-nationalism; political economy

The Rise of Populist Movements in Europe: A Response to European Ordoliberalism? - Cayla, David (Journal of Economic Issues (Taylor & Francis Ltd), 2019)
This article aims to explain the contemporary emergence of populism in the European Union. According to Polanyi's double movement framework, the emergence of these political forces can be understood as the result of protective responses from societies weakened by difficult market adjustments. Since the Single Act treaty (1986), the European economy took a path that intended to create a supranational self-adjusting markets economy based on the ordoliberal philosophy. However, by detaching the economic sphere from the reach of politics, the European Single Market has injured some important social institutions. The rise and the diversity of populisms in the European Union can therefore be explained by an attempt to preserve some national institutions that were diversely impacted by the market forces.
Keywords: European Single Market; free enterprise; institutional economics; international relations; neoliberalism; ordoliberalism; populism; social functions; social institutions

Doing justice to Karl Polanyi - Devine, Pat (Capitalism, Nature, Socialism, 2019)
Keywords: POLANYI, Karl, 1886-1964; book review; economic activity; economics; social control; social forces

Climate Change and the Polanyian Counter-movement: Carbon Markets or Degrowth? - Stuart, Diana; Gunderson, Ryan; Petersen, Brian (New Political Economy, 2019)
In the midst of a wave of market expansion, carbon markets have been proposed as the best way to address global climate change. While some argue that carbon markets represent a modern example of a Polanyian counter-movement to the environmental crisis, we adopt a structural interpretation of Polanyi to refute this claim. Carbon markets represent a further expansion of markets that fails to address the underlying contradictions related to the commodification of nature. In addition, they increase risks to society and the domination of economic elites. While carbon markets further subject social and ecological relations to market mechanisms, we examine degrowth as a possible response to climate change that prioritises social and environmental goals over economic growth. While degrowth continues to be dismissed as impractical or impossible, a growing number of scholars, scientists and activists argue it is the only way to address global climate change. In contrast to carbon markets, we argue degrowth could represent a genuine Polanyian counter-movement in response to climate change. In addition, degrowth could help all those disenfranchised by market fundamentalism by addressing the triple crises related to the commodification of land, labour and money.
Keywords: carbon markets; carbon offsetting; climate; climate change; degrowth; economic development; economic elites; emissions (air pollution); environment; environmental studies

Economic and Political Foundations of Effective Transition to Renewable Energy: Ordoliberalism, Polanyi, and Cities as Hubs for Climate Leadership and Innovation - Lysack, Mishka (Renewable Energy: International Perspectives on Sustainability, 2019)
A remarkable transition to a renewable energy economy (also known as the Energiewende) with ambitious climate protection and sustainable economic development is taking place in Germany, with many German cities exemplifying best practices in effective climate leadership to attain ambitious climate goals, such as Munich (1.4 million) moving steadily to its targets of 100% renewable energy by 2025 and 100% renewable heat by 2040. Similarly, the former coal city of Bottrop in West Germany won the Innovation Ruhr Prize for increasing its refurbishment rate to 3% (3× national average), installing solar panels, reducing its GHG emissions by 37%, and attracting over $316 million in economic investment in sustainability. However, it needs to be noted these accomplishments do not take place in a vacuum, but within a supportive and empowering policy and economic context which includes two key elements. The first entails using Karl Polanyi’s three key analytic resources of restoring the social and environmental dimensions of the economy: (1) re-embedding the economy within society and in turn, within the larger context of the environment, (2) reversing the reduction of labour and land into “fictitious commodities” and tradable goods; and (3) fostering the “double movements” of the protective responses of both government and society to correct the negative impacts of the free-market economy. Secondly, the economic approach of ordo-liberalism in Germany facilitates the shift to an economy with economic rules and “referees,” fostering the renewable energy transition through innovative economic and social capital approaches, while also deconstructing the economic monopolies and concentrations of political-economic power that arise in neo-liberal and authoritarian economies.
Keywords: double movement; fictitious commodities; ordoliberalism; reembedding; renewable energy economy; sustainability

Changing Approaches to Development since 1950: Drawing on Polanyi - Stewart, Frances (History of Political Economy, 2018)
The article focuses on analysis of Karl Polanyi in the book "The Great Transformation" which explained the changes in Great Britain from eighteenth-century mercantilism to nineteenth-century free markets to the state-centered interventionism of the mid-twentieth century evident when he was writing. It mentions additional features needed for understanding the evolution of development thought and repeal of the Corn Laws in 1846, leading to free trade in agricultural products.
Keywords: Great Transformation, The (Book); POLANYI, Karl, 1886-1964; economic development; free enterprise; free trade; mercantile system

Terrains of Civil and Uncivil Society in Post-Apartheid Durban - Bond, Patrick; Mottiar, Shauna (Urban Forum, 2018)
Post-apartheid Durban civil society politics reflects not only durable anti-racist activism, but primarily, Karl Polanyi's pendulum of a 'double movement' of the market against people and environment on the one hand, and social backlashes against neoliberalism on the other. The most important movements and campaigns of a socioeconomic nature can be summarised as follows: local resistance to economic disempowerment and lack of service delivery in various trade union strikes (1994-present), South Durban's fight against polluters and the port's expansion (1996-present), Chatsworth's water and electricity battles (1999-2012), the Treatment Action Campaign's access to AIDS medicines (early 2000s), Abahlali baseMjondolo's anti-eviction campaigns (2005-present), the defence of the Early Morning Market (2009-10), the Umlazi Occupy (2012), and sporadic community protests throughout. Resistance has occurred in urban poor neighbourhoods and townships and also penetrated the Durban inner city and university campuses. Durban activists' tactics range from militant protests to 'occupation' of space ranging from townships to the Speaker's Corner next to the Convention Centre, innovative door-to-door campaigning and court action. While the limits of single-issue and often assimilationist civil society politics are becoming obvious in one of the world's most unequal cities, there still has not yet been a successful 'united front' project to fuse interests, in part due to ideological division and the geographical diffusion of dissent.
Keywords: Durban; HIV/AIDS; South Africa; Treatment Action Campaign; anti-racism; apartheid; civil society; demonstrations (collective behavior); double movement; environmental justice; protest; social movements; socioeconomics; trade unions

Polanyi, Hayek and embedded neoliberalism - Cahill, Damien (Globalizations, 2018)
Written originally on the seventieth anniversary of the publication of Friedrich von Hayek’s The Road to Serfdom and Karl Polanyi’s The Great Transformation, this article critically analyses how the ideas of Hayek and Polanyi have been deployed to understand neoliberalism. It argues that dominant scholarly interpretations tend to miss the significance of each thinker to an understanding of neoliberalism, as well as some of the key dynamics of neoliberal forms of capitalist regulation. Drawing upon the work of Polanyi, the article advances the concept of embedded neoliberalism. From the 1970s neoliberal regulations became deeply embedded in a series of institutions, class relations and ideological norms. This helps to explain both the durability of neoliberalism, and the onset of crisis in 2008. In this context, Hayek’s ideas are best understood as providing a malleable set of concepts underpinning neoliberal ideology, rather than the chief causal agent in the neoliberal transformation of states and economies.
Keywords: HAYEK, Friedrich A. von (Friedrich August), 1899-1992; capitalism; embeddedness; liberalism; neoliberalism

‘Our world was made by nature’: constructions of spontaneous order - Dale, Gareth (Globalizations, 2018)
This article explores the concepts of spontaneity and spontaneous order, in particular their deployment by Friedrich Hayek and Karl Polanyi. Although in many respects these thinkers were poles apart, the article identifies a point of convergence. They both mobilize the concept of spontaneity in a manner that naturalizes a particular social process: for Hayek, the market economy, for Polanyi, society’s protective movement that arises in reaction against the market economy. To contextualize the uses of spontaneity by Hayek and Polanyi, I trace its evolution, with reference to Leibniz, Mandeville, and the thinkers of the Scottish Enlightenment. Having sketched the ways in which earlier thinkers understood spontaneity, I turn finally to Hayek and Polanyi. I argue that their invocations of spontaneity and spontaneous order contribute to a downplaying of relations of domination and exploitation. While Hayek sees the market system as the exemplar of spontaneous order, for Polanyi, the concept of spontaneity underpins his belief that the protective countermovement is a ‘natural’ reaction to the evils of market society; as such, power relations pass beneath the radar.
Keywords: HAYEK, Friedrich A. von (Friedrich August), 1899-1992; HAYEK, Salma, 1968-; POLANYI, Michael, 1891-1976; social order; socialism; spontaneity; spontaneity (philosophy); spontaneous order

Democracy disembedded - Dimitrijevic, Nenad (Philosophy & Social Criticism, 2018)
Democracy is in serious difficulties. Three features of the crisis stand out. First is the dominant culture of disillusionment in democracy, which transpires as the mistrust in constitutionalist institutions and values. Second, political authority, both at domestic and international levels, is largely substituted by the rule of non-transparent and unpredictable social powers. Third, democratic states are deprived of much of their capacity to govern, but they retain a non-negligible capacity to coerce.The article is structured as follows. Section I introduces Karl Polanyi’s concept of embeddedness and juxtaposes it to the theoretical defense of market disembeddedness advanced by the classical political economy. It then points to the challenge that the complexity of the contemporary society poses to the idea of embeddedness and identifies the need for further analytical clarification of the idea. Section II tries to explain why the idea of embeddedness is intuitively suspect. One reason is found in the dominant understanding of liberalism as a regime that rests on the separation between private and public realms. The section closes with a reference to internal tensions of this reading of liberalism. Section III provides a diagnosis of the contemporary condition of disembeddedness. The core claim is that the combination of neoliberalism and globalization has created a condition of multiple—normative, social, political and legal—disintegration, which questions the very survival of democracy. Section IV addresses the question of transformation, focusing on the need for the reconceptualization of liberal equality.
Keywords: POLANYI, Karl, 1886-1964; democracy; disembeddedness; embeddedness (socioeconomic theory); equality; globalization; liberalism

Polanyi’s two transformations revisited: a ‘bottom up’ perspective - Halperin, Sandra (Globalizations, 2018)
In The Great Transformation, Karl Polanyi offers a ‘top-down’ analysis of the rise and demise of Europe’s unregulated market system. He assumes that changes in the organization of the international economy provide particular kinds of opportunities for states to act which, in turn, shapes the extent to which social forces will be able to influence state policy. Consequently, his analysis focuses, first, on the international institutions created by the self-regulating market system; then on the ‘liberal state’ which these made possible; and finally on how the system impacts ‘society as a whole’. The account which this analysis produces systematically underplays the social struggles which propelled and emerged from the rise of Europe’s nineteenth century system and which ultimately led to its demise. In revisiting the two periods that are the focus of Polanyi’s analysis, this article assumes that states and interstate systems reflect the interests of powerful social forces. Thus, working from the ‘bottom up’, it focuses on the class interests that produced Europe’s market system, the state and international structures which reflected and supported them, and the social struggles that ultimately brought about the collapse of the system. What this ‘bottom up’ account reveals is the centrality of a ‘double movement’, not of market expansion and a protective countermove on the part of ‘society as a whole’, but of dominant classes monopolizing economic opportunities from global expansion, and a rising ‘red tide’ of disaffected workers. This double movement, it argues, better explains the demise of the system and the changes that ensued from it.
Keywords: class conflict; double movement; economic development; industrial capitalism; international relations; markets

Against exceptionalism: the legitimacy of the neoliberal age - Konings, Martijn (Globalizations, 2018)
After the financial crisis of 2007-08, many commentators, adopting a broadly Polanyian logic of reasoning, expected a departure from neoliberalism. The failure of this shift to materialize has typically been accounted for in ‘exceptionalist’ terms: the persistence of neoliberalism is understood not as a function of a specific legitimacy it has itself engendered, but in terms of external interventions by elites who manage to ‘capture’ executive and regulatory institutions and so to bypass democratic pressures. This paper argues that such an approach underestimates the endogenous sources of legitimacy and resilience that neoliberal governance commands. It criticizes the idea that neoliberalism is at its core dependent on a Schmittian exceptionalism and suggests a perspective on Hayek's articulation of neoliberalism that dissociates it from such an exceptionalist approach. The article proceeds to interrogate the rationality of neoliberalism by examining its distinctively secular temporal logic, rooted in speculation, preemption and reaction.
Keywords: HAYEK, Friedrich A. von (Friedrich August), 1899-1992; capitalism; exceptionalism; legitimacy; neoliberalism; preemption

The great trasformismo - Morton, Adam David (Globalizations, 2018)
The purpose of this article is to explore the commonalities and differences between Karl Polanyi and Antonio Gramsci in their assessment of the origins of fascism as located within the rise of capitalism in the nineteenth century and its structural impasse in the twentieth century. Specifically, the aim is to trace a set of associations between Polanyi and Gramsci on the transformations wrought across the states-system of Europe prior to the crises that engulfed capitalism leading to the rise of fascism in the twentieth century. Focusing on the class structures that emerged out of the expansion of capitalism across Europe in the nineteenth century reveals that there was less a ‘great transformation’ in terms of a rupture with the past through the rise of liberal capitalism. Rather, there was more a slow and protracted process of class restoration known as passive revolution, or a ‘Great Trasformismo’, referring to the molecular absorption of class contradictions marking the consolidation and expansion of capitalist social relations. In sum, it is argued that The Great Transformation is understood better if read through the epoch of passive revolution, or The Great Trasformismo, which entailed the restoration and maintenance of class dominance through state power. This approach therefore opens up questions, rather than forecloses answers, about the historical geographies constituting the spaces and places of the political economy of modern capitalism.
Keywords: GRAMSCI, Antonio, 1891-1937; POLANYI, Karl, 1886-1964; capitalism; fascism; passive revolution

Neoliberalism as a real utopia? Karl Polanyi and the theoretical practice of F. A. Hayek - Rodrigues, João (Globalizations, 2018)
This article interprets Hayek’s theoretical practice with the help of Polanyi’s framework. Hayek aimed at renewing liberalism after the interwar period, thus helping transforming it into neoliberalism, a real utopia instrumentally concerned with the political and moral economies underpinning markets. The distance between neoliberal theory and practice is less pronounced than it is sometimes assumed. The strength of neoliberalism partially stems from a capacity to articulate an effort to think about real-world mechanisms with an effort to demolish, reconfigure or transform existing structures. Despite his failure to anticipate neoliberalism, Polanyi gives ample intellectual resources to critically interpret the tasks that neoliberals would collectively have to face at the theoretical level, in an epoch of ideological marginality, before their triumphal political deployment at the global level.
Keywords: HAYEK, Friedrich A. von (Friedrich August), 1899-1992; market; neoliberalism; utopia

Market/society: mapping conceptions of power, ideology and subjectivity in Polanyi, Hayek, Foucault, Lukács - Short, Nicola (Globalizations, 2018)
In light of discussions around the common anniversary of the publication of Karl Polanyi’s The Great Transformation and F.A. Hayek’s The Road to Serfdom, this article puts these texts - iconic representations of social democratic and neoliberal political theory - into conversation with Michel Foucault’s subsequent, influential critique of neoliberalism, The Birth of Biopolitics. There are interesting points of contact in the way each text constructs its argument, even as they arrive at distinct positions vis-à-vis the material and subjective nature of market society, while nevertheless sharing an opposition to Marxian approaches. Yet the work of Polanyi and Hayek’s Marxian contemporary, Lukács’ History and Class Consciousness, offers precisely a critical framework for understanding the relationship between markets, liberty and society in which the material and the subjective need not be read as antagonistic. It is thus also examined here, in an effort to shed light on how discussions of contemporary neoliberalism are framed.
Keywords: Canada; FOUCAULT, Michel, 1926-1984; HAYEK, Friedrich A. von (Friedrich August), 1899-1992; LUKACS, Georg; MARX, Karl, 1818-1883; Marxism; Road to Serfdom (book); commodity; homo economicus; market society; neoliberalism; power

Reading Polanyi in Erbil: understanding socio-political factors in the development of Iraqi Kurdistan - Smith, Robert (Globalizations, 2018)
The Kurdistan Regional Government emerges out of the chaos of post-Saddam Iraq as a rare positive, providing both political stability and economic growth. However, the outward display masks a more complex domestic settlement where the trappings of the free market coexist with political parties who are significant economic actors. How can this model of development in Iraqi Kurdistan be explained? Turning to the writings of political economist Karl Polanyi, does his thinking on relations between society and economy offer a way to unpack the development? And what does this analysis tell us of prospects for Iraqi Kurdistan?
Keywords: Iraq; Iraqi Kurdistan; Kurdistan; Kurdistan Regional Government; POLANYI, Karl, 1886-1964; international studies

A moral householding perspective on the sharing economy - Laamanen, Mikko; Wahlen, Stefan; Lorek, Sylvia (Journal of Cleaner Production, 2018)
Abstract In this paper, we scrutinise the sharing economy from a moral householding perspective and evaluate the moral justifications for a sustainable form of the sharing economy. We consider the emergence of normative moral justifications through householding practices that rest on local mobilisation of people in defence of communities and commitments against the adverse impacts of neoliberal market capitalism. Our perspective draws on Karl Polanyi's conceptualisation of householding, that is, autarchic, communistic provision in a closed community. Using timebanking as an example, we illustrate how a moral sharing economy can be mobilised in collective battles against the current neoliberal system of economic crisis. We contribute to the amassing sharing economy literature emphasising a central, yet missing element of the current discourse: householding as practices creating self-sufficiency and autonomy as well as combining both kin and stranger.
Keywords: financial crises; householding; households; market capitalization; mobilisation; moral economy; sharing economy; sustainable development; timebanking

The Truncated Commercialization of Microinsurance and the Limits of Neoliberalism - Bernards, Nick (Development & Change, 2018)
Microinsurance — defined as low‐cost insurance products targeting low‐income populations — exemplifies key themes in contemporary neoliberalism, and has figured prominently in neoliberalism's turn to discourses such as 'risk management' and 'financial inclusion'. The development of commercial markets for microinsurance, however, has in practice been highly variable and often very limited. This article considers the implications of this process of 'truncated commercialization'. It draws on a Polanyian analytical framework that emphasizes the contradictory regulatory dynamics involved in the commodification of labour. The article applies this approach by tracing multiscalar efforts to promote microinsurance, examining the emergence of the concept in the efforts of the International Labour Organization to promote social security for informal workers in the 1980s and 1990s, looking at the adoption of explicitly commercializing imperatives in the work of the International Association of Insurance Supervisors in the 2000s, and, finally, considering a case study of South Africa. The truncated commercialization of microinsurance, it is argued, provides a useful lens through which to see the practical impossibility of neoliberal development strategies.
Keywords: International Association of Insurance Supervisors; International Labour Organisation; commercialization; microinsurance; neoliberalism; social security

China's Middle East investment policy - Kenderdine, Tristan; Lan, Peiyuan (Eurasian Geography & Economics, 2018)
China's greater Middle East geoeconomic strategy is centered on an external trade and industry policy. This trade and industry policy combines geopolicy and geoeconomic policy to export industrial capacity bases in what amounts to a geoindustrial policy and a parallel trade strategy. Practical coordination is under the umbrella of the central International Capacity Cooperation macro-policy. China's provincial governments are then tasked with offshoring China's industrial capacity to Middle East economies through specialized International Capacity Cooperation funds, which are then coordinated by sectoral industry associations: International Capacity Cooperation Industry Enterprise Alliances. The final industrial policy is then deployed by matching China's provinces and prefectures to external geographies. This amounts to a State Outward Direct Investment Strategy. This paper uses primary sourced Chinese policy documents from central and provincial state administrative agencies to build a historical institutional record. We then employ a Polanyian analysis of the embeddedness of State functions in China's external investment activities and industrial transfers, analyzing China's external trade and industry policy in the Middle East in terms of state–market institutional interrelationality.
Keywords: China; China policy; Middle East; Middle East policy; foreign investments; foreign relations; geoeconomics; geoindustrial policy; geopolicy; institutional economics; investment policy

Rethinking the Double Movement: Expanding the Frontiers of Polanyian Analysis in the Global South - Goodwin, Geoff (Development & Change, 2018)
Over the last two decades a rich and diverse body of literature has emerged which uses the ‘double movement’ to analyse social, political and economic change in the global South. The main aims of this article are to expand the boundaries of this scholarship and improve our understanding of how to use the concept to analyse capitalist development in the region. It seeks to achieve this by explaining and extending the original formulation of the double movement, creating a dialogue between scholars who follow alternative readings of the concept, and proposing a revised formulation which builds on the existing literature while moving in new directions. The article concludes by signposting potentially fruitful areas of Polanyian analysis.
Keywords: capitalism; commodification; developing countries; development studies; double movement; economic reform; liberalism; political change; social change; social movements

Review of The Hungarian Writings by Karl Polanyi - Moussaly, Omer (International Critical Thought, 2018)
In the current times of political crisis, a giant thinker such as Karl Polanyi will return to the forefront of intellectual debate. Many of his important early articles have only been available in Hungarian or in German. With the publication of The Hungarian Writings (2016), edited by Gareth Dale (Senior Lecturer in Politics and International Relations at Brunel University London), a major gap in Polanyi studies has been filled. These essays, published for the first time in English, provide a key to understanding Karl Polanyi’s later works. The range of issues that are reviewed in these writings is astounding. Everything from Marxism to politics, economics and sociology is examined by the extraordinary mind of the author. Events such as the Russian revolution and the significance of Bolshevism are also explored. Lastly, a section of correspondence to such eminent intellectuals as Georg Lukaćs and Istvan Meszaros gives the reader an inside look into the socialist worldview of Karl Polanyi. This book truly shines a new light on many aspects of Polanyi’s critique of capitalism developed in his magnum opus, The Great Transformation (1944). Various aspects of The Hungarian Writings will be explored in depth in this critical review.
Keywords: Bolshevism; Canada; Great Transformation, The (Book); Hungarian Writings, The (Book); Marxism; POLANYI, Karl, 1886-1964; Quebec; Russian Revolution, 1917-1921; economics; nonfiction; socialism

Labour Protest and Industrial Peace: Russian Steelworkers' Encounters with Economic Reforms and Unravelling Social Protections - Evans, Allison D. (Economy and Society, 2018)
The collapse of the Soviet Union brought a series of economic reforms: privatization, increased foreign direct investment and weakened benefits. Correspondingly, some scholars expected trade unions to serve as a major contribution to the development of a democratic civil society that would serve as a Polanyian double movement to these disruptive reforms. However, Russia's steelworkers have stood out as particularly weak and unwilling to strike due to their dependence on their employer for almost all aspects of their livelihoods. But is this lack of large, legally sanctioned and disruptive strikes truly evidence of worker quiescence and weak trade unions? Using an analysis of local newspaper accounts and archival documents to process-trace the interactions of workers, trade unions and management, this paper offers a counter-argument to the generalizations of past studies. Specifically, protests tend to be more frequent and extreme when there is union competition within a company and when foreign owners violate labour laws. Unions tend to engage in non-protest bargaining strategies when companies face bankruptcy or closure under domestic ownership. Because Russia was an early case of the rapid liberalization reforms that have been broadly recommended to developing and post-communist countries, a closer reading of on-the-ground conditions and protest aids in a broader understanding of the variation in backlash to global capitalism.
Keywords: Russia; cement; ceramics; collective bargaining; dispute resolution: strikes, arbitration, and mediation; double movement; glass; industry studies; metals and metal products; population; property rights; socialist systems and transitional economies: factor and product markets; socialist systems and transitional economies: political economy; trade unions: objectives, structure, and effects

European Politics and the Neoliberal Paradigm - Sliwinski, Krzysztof (Australian & New Zealand Journal of European Studies, 2018)
This paper looks at the European integration project in its current iteration drawing on Karl Polanyi's assertion that markets are inseparable from the socio-cultural context. In this regard, all attempts to liberalise the economy (not excluding European integration, which is based on the principle of the single market) have practical and indeed tangible political ramifications. The main hypothesis of the paper lies in the recognition of the fact that the neoliberal agenda is one of the defining features of European integration. It is after all, the project of the single market, with its free movement of goods, services, capital, and labour that underpins European Union integrative practice. Secondly, it is the presupposition of this paper, that there is a certain degree of congruence between the economic elites, operating within the neoliberal framework, and the centre-left political elites. The argument here is that the logic of neoliberalism has been fundamentally accepted across the mainstream of the political spectrum. This consequently means that even left-wing parties have had to reposition themselves both ideologically and practically, which brings the conclusion that the market has lost its role as the basic ideological differentiator between the traditional right and left. The axis of political debate has consequently shifted to moral issues such as the relationship between the state and the church, immigration, and gender.
Keywords: EU; European Union; European integration; democracy deficit; international studies; neoliberalism; political ideologies

A hands-on hands-off approach: governance of managed long-term care services in a context of rapid policy change - Nisbet, Elizabeth (Public Management Review, 2018)
Amidst state-level budgetary pressures and growing elderly populations, many US states have adopted managed care for home-based services funded through the Medicaid program. New York State’s managed care mandate is part of a Medicaid ‘Redesign’ targeting health outcomes, cost control, and administrative efficiency, reflecting features emphasized by both governance and New Public Management frameworks, but neither adequately captures this case. Incorporating a Polanyian perspective can elucidate this market expansion and related reactions and re-regulation. Drawing from interviews with staff of service-providing agencies, this case study reveals outcomes contrary to goals: administrative complexity, containment of care, and unexpected costs.
Keywords: United States; United States federal budget; cost control; governance; health care reform; home care services; long-term care; medicaid; medical care costs; public management

The Significance of Polanyi's Contribution: An Interpretation of the Neoliberalization and Commodification of Nature - Iannuzzi, Giulia (Janus.Net: e-Journal of International Relations, 2018)
Polanyi's analysis and contributions have been brought back into discussion due to the rapid emergence of market-based instruments designed to tackle environmental degradation. Polanyi is a crucial reference in current debates on globalization and international political economy. This article seeks to explore and discuss how his perspective, and the founding concepts of his work, can help us to interpret the current process of the neoliberalization and commodification of nature.
Keywords: commodification; commodification of nature; environment; globalization; international relations; neoliberalism

Polanyi in times of populism: Vision and contradiction in the history of economic ideas - Holmes, Christopher (Routledge, 2018)
The rise of populism across Europe and the US – first in the wake of the 2008 global financial crisis and then in the shape of Donald Trump’s presidential campaign and the Brexit vote in 2016 – are indicative of a seismic shift in the terrain of economic ideas in public discourse. Settled liberal norms concerning ever-increasing international market expansion, and the political integration required to sustain it, have been decisively upset by political forces that, whilst once on the fringes, now dominate economic debate. How might we make sense of this ideological breakdown and what might we hope for next? This book turns to the work of Karl Polanyi for answers, developing the expansive, historicised approach to political economy that Polanyi pioneered. Holmes provides a wide-ranging history of economic ideas read in terms of a series of hopeful theoretical visions of order, in which political, social and ecological contradictions could be transcended in one way or another. Through this, the book demonstrates that the failing utopian visions of pre-2008 economic orthodoxy, which have formed the backdrop to the rise of populism today, are only the latest in a series that stretches across economic thought in Western modernity as a whole. This book will interest students and scholars of IPE, political science, sociology, anthropology, law and history.
Keywords: political science / general; populism

Karl Polanyi's Genealogy of Utopian Liberalism - England, Christopher (Theory & Event, 2018)
Despite its centrality to current debates about globalization and neoliberalism, aspects of Karl Polanyi's The Great Transformation remain poorly understood. This article places Polanyi in conversation with Weber, Nietzsche, and Foucault in order to explicate his genealogy of utopian liberalism. This mode of thought emerged in the late 18[sup th] century as a response to the mass pauperism of the Industrial Revolution in England. It substituted a mechanistic naturalism for the political and ethical concerns of earlier economists. Polanyi shows that the allure of utopian liberalism is sustained because it functions as the public theodicy of a market society.
Keywords: FOUCAULT, Michel, 1926-1984; NIETZSCHE, Friedrich; POLANYI, Karl, 1886-1964; genealogy; globalization; liberalism; neoliberalism; utopian liberalism

The Moral Economists: R. H. Tawney, Karl Polanyi, E. P. Thompson, and the Critique of Capitalism - Crook, Paul (Australian Journal of Politics & History, 2018)
The Moral Economists: R. H. Tawney, Karl Polanyi, E. P. Thompson, and the Critique of Capitalism. By Tim Rogan (Princeton and Oxford, Princeton University Press, 2017), pp.263 + viii. AU$48.82 (hb). Available in Australia through Footprint Books.
Keywords: MORAL Economists: R.H. Tawney, Karl Polanyi, E.P. Thompson & the Critique of Capitalism, The (Book); POLANYI, Karl, 1886-1964 - political & social views; ROGAN, Tim; TAWNEY, R. H. (Richard Henry), 1880-1962; THOMPSON, E. P. (Edward Palmer), 1924-1993; book review; nonfiction; political attitudes

Discursive Synergies for a ‘Great Transformation’ Towards Sustainability: Pragmatic Contributions to a Necessary Dialogue Between Human Development, Degrowth, and Buen Vivir - Beling, Adrián E.; Vanhulst, Julien; Demaria, Federico; Rabi, Violeta; Carballo, Ana E.; Pelenc, Jérôme (Ecological Economics, 2018)
There is a growing awareness that a whole-societal “Great Transformation” of Polanyian scale is needed to bring global developmental trajectories in line with ecological imperatives. The mainstream Sustainable Development discourse, however, insists in upholding the myth of compatibility of current growth-based trajectories with biophysical planetary boundaries. This article explores potentially fertile complementarities among trendy discourses challenging conventional notions of (un)sustainable development – Human Development, Degrowth, and Buen Vivir – and outlines pathways for their realization. Human Development presents relative transformative strengths in political terms, while Degrowth holds keys to unlocking unsustainable material-structural entrenchments of contemporary socio-economic arrangements, and Buen Vivir offers a space of cultural alterity and critique of the Euro-Atlantic cultural constellation. The weaknesses or blind spots (‘Achilles heels’) of each discourse can be compensated through the strengths of the other ones, creating a dialogical virtuous circle that would open pathways towards a global new “Great Transformation”. As one of the main existing platforms for pluralist and strong-sustainability discussions, Ecological Economics is in a privileged position to deliberately foster such strategic discursive dialogue. A pathway towards such dialogue is illuminated through a model identifying and articulating key discursive docking points.
Keywords: biophysics; degrowth; ecosystem services; environemntal economics; post-development; pragmatics; socio-ecological transition; strategic dialogue; sustainable development; transformation discourses

Costly Fix: Power, Politics, and Nature in the Tar Sands - Urquhart, Ian Thomas (University of Toronto Press, 2018)
Costly Fix examines the post-1995 Alberta tar sands boom, detailing how the state inflated the profitability of the tar sands and turned a blind eye to environmental issues. It considers the position of First Nations, the character and strength of environmental critiques, and the difficulties that environmental groups and First Nations have had in establishing a countermovement to market fundamentalism. The final chapter discusses how Alberta's new NDP government, in its first couple of years, has addressed the legacies they have inherited from the previous Progressive Conservative government on climate change, royalties, and the blight of tailings ponds in the boreal forest. Throughout the book, Urquhart demonstrates that too many actors have done too little to prevent Alberta's boreal forest from becoming a landscape sacrificed for unsustainable economic growth.
Keywords: Alberta; Canada; First Nations; double movement; environmentalism; tar sands

Reconstructing Globalization in an Illiberal Era - DeMartino, George F. (Ethics & International Affairs, 2018)
In their new indictments of global neoliberalism and the economic profession's culpability in its harms, Dani Rodrik and Joseph Stiglitz press the case for reconstructed globalization that generates benefits for all and not just for corporate and financial elites. Both books are deeply consistent with the insights of Karl Polanyi, who had identified the inherent contradictions of the project to create what he called a self-regulating economy. Like Polanyi, Rodrik and Stiglitz are attentive to the inadequacies of neoliberalism, and both emphasize the capture of the state and international economic policy by elites, who have turned their backs on those left behind. While Stiglitz emphasizes that the profession knows how to fix the problem by applying modern Keynesian insights, Rodrik emphasizes the inherent epistemic limitations facing economists. Indeed, his arguments about development policy reflect the insights of Friedrich Hayek into the limits of economic expertise.
Keywords: HAYEK, Friedrich A. von (Friedrich August), 1899-1992; RODRIK, Dani; STIGLITZ, Joseph; globalization; international relations; nationalism; neoliberalism; policy autonomy; trade; uncertainty

Capitalism: A Conversation in Critical Theory - Fraser, Nancy; Jaeggi, Rahel (John Wiley & Sons, 2018)
In this important new book, Nancy Fraser and Rahel Jaeggi take a fresh look at the big questions surrounding the peculiar social form known as “capitalism,” upending many of our commonly held assumptions about what capitalism is and how to subject it to critique. They show how, throughout its history, various regimes of capitalism have relied on a series of institutional separations between economy and polity, production and social reproduction, and human and non-human nature, periodically readjusting the boundaries between these domains in response to crises and upheavals. They consider how these “boundary struggles” offer a key to understanding capitalism’s contradictions and the multiple forms of conflict to which it gives rise. What emerges is a renewed crisis critique of capitalism which puts our present conjuncture into broader perspective, along with sharp diagnoses of the recent resurgence of right-wing populism and what would be required of a viable Left alternative. This major new book by two leading critical theorists will be of great interest to anyone concerned with the nature and future of capitalism and with the key questions of progressive politics today.
Keywords: boundary struggle; capitalism; political philosophy; triple movement

The social aftermath of economic disaster: Karl Polanyi, counter-movements in action, and the Greek crisis - Kentikelenis, Alexander E. (Socio-Economic Review, 2018)
The economic crisis in Greece resulted in high unemployment and the dismantlement of social protection policies. How does society respond to the collapse of both welfare-state and market mechanisms? I examine these issues through the study of one working class community in Athens over 2012-13. Since the onset of the crisis, my informants experienced a simultaneous drop in living standards, loss of social status, and debasement of their symbolic construction of reality. To respond to these pressures, they relied on a combination of material survival strategies, the reconfiguration of social resources, and the reconstruction of cultural imaginaries. To explain these findings, the article draws on Karl Polanyi's analysis of countermovements to marketization and commodification. I argue in favour of augmenting the definition of countermovements to capture local-level responses, emphasising cultural aspects of social protection, and tracing the micro-foundations of countermovements that are nonetheless shaped by the macro-institutional context shaping action. This reading of Polanyi's work seeks to integrate many moving--and potentially contradictory--parts into a holistic analysis of societal responses to rapid and radical socioeconomic change.
Keywords: Greece; capitalist systems: political economy; countermovement; economic crisis (2008); financial crises; history of economic thought: individuals; national government expenditures and welfare programs

Karl Polanyi and the formation of this generation's new Left - Sandbrook, Richard (IPPR Progressive Review, 2018)
The article discusses whether the visionary thinking of economic historian Karl Polanyi provide a feasible fix in the 21st Century for forces of populism and neoliberalism. Topics include Polanyi's work is stated to offer three potential contributions to the formation of this generation's new Left which include analysis of fascism, post-Vienna approach to socialism.
Keywords: POLANYI, Karl, 1886-1964; fascism; neoliberalism; populism; socialism

Family as a Socio-economic Actor in the Political Economies of East and South East Asian Welfare Capitalisms - Papadopoulos, Theodoros; Roumpakis, Antonios (Social Policy & Administration, 2017)
In this article, we revisit Karl Polanyi's concept of 'oikos' in order to reconceptualize the role of the family as both a welfare provider and an economic actor in the social reproduction of East and South East Asian welfare capitalisms. Our article is structured in four parts. First, we critically review existing approaches on the characteristics of welfare capitalism in East and South East Asia. We argue that existing approaches tend to isolate family as a welfare provider and neglect how the role of the family is institutionalized as a collective actor. The second part focuses on the role of the family in the social reproduction of welfare capitalism, and explores how, in East and South East Asia, the specific conditions for family's role as an economic actor were institutionalized historically. The third part revisits Polanyi's concept of 'oikos' and how 'householding' constitutes one of the most important forms of economic action allowing us to examine the family as a socio-economic actor. In the fourth section, we provide an analysis of families' available strategies and discuss evidence related to private education expenditure, household debt and labour market income share. We conclude by highlighting the need to re-articulate the importance of family as a collective socio-economic actor that, despite recent reforms and path departures, remains at the epicentre of East and South East Asian welfare capitalisms.
Keywords: East and South East Asia; OIKOS (The Greek word); debt; economic conditions in Asia; families & economics; family; households and economics; social reproduction; welfare capitalism; welfare state

Why TTIP is an unprecedented geopolitical game-changer, but not a Polanyian moment - Eliasson, Leif Johan; García-Duran, Patricia (Journal of European Public Policy, 2017)
This contribution argues that the Transatlantic Trade and Investment Partnership (TTIP) is unprecedented, not because it constitutes a Polanyian moment, but rather because it offers an alternative to multilateralism through the World Trade Organization (WTO). Never before has bilateralism offered such a 'best alternative to no agreement' (BATNA) to members of the core decision-making body of the WTO negotiating arm, making TTIP an unprecedented geopolitical game-changer. The anti-TTIP campaign, however, has not been driven by concerns with either geopolitics or trade liberalization, but rather fears about the European Union's (EU's) bargaining power. By strategically focusing on the potential impact on public policy and safety standards, normative arguments promulgated by opponents reflect concerns with perceived threats to the status quo and a willingness to preserve the same. The United States is presented (implicitly) as more powerful than the EU, and therefore perceived as able to impose its preferences, which are considered too neoliberal.
Keywords: European Union; TTIP; Transatlantic Trade and Investment Partnership (TTIP); World Trade Organization (WTO); bilateralism; free trade; geopolitics; trade

Fictitious Freedom: A Polanyian Critique of the Republican Revival - Klein, Steven (American Journal of Political Science, 2017)
Prominent republican theorists invoke anonymous orders such as the market as mechanisms that secure freedom as non-domination. Drawing on Karl Polanyi's account of fictitious commodities and demonstration of the impossibility of a just and rational market society, this article critically scrutinizes neo-republican assumptions regarding the market, develops an alternate social theory within which to situate the ideal of non-domination, and illustrates the importance of this reconfiguration for the kind of collective agents and political strategies that can be expected to advance republican freedom in the economy.
Keywords: Polanyi - political & social views; economic liberty; markets; republicanism; social theory

Re-reading Friedrich Hayek and Karl Polanyi in the Late-Modern Condition of Fragility - Cha, Taesuh (Political Studies Review, 2017)
The cardinal role of complexity in Friedrich Hayek’s theory of the market has hardly gone unnoticed. Indeed, there is now a considerable corpus of literature that has established the importance of spontaneity as a central concept around which neoliberal economic theory revolves. However, as William Connolly analyzes, its closed conception of economic processes simplifies real economic volatilities and ignores both modes of self-organization and creativity found in democracy and social movements that periodically irrupt into market processes. This article builds upon this critique of neoliberalism and employs Karl Polanyi’s genealogy of modern capitalism to understand historical imbrications between the market and the social and their contribution to the fragility of capitalism. Polanyi’s notions of “(dis-)embeddedness” and the “double movement” not only show us a more “complex” view of modern political economy but also provide us with important lessons for political responses to the recent crisis of neoliberal capitalism.
Keywords: CONNOLLY, William; Friedrich Hayek; HAYEK, Friedrich A. von (Friedrich August), 1899-1992; POLANYI, Karl, 1886-1964; capitalism; complexity (philosophy); complexity theory; fragility; genealogy

When Polanyi met Farage: Market fundamentalism, economic nationalism, and Britain's exit from the European Union - Hopkin, Jonathan (British Journal of Politics & International Relations, 2017)
The vote for Brexit is not an isolated event, but part of a wave of populist, anti-elite revolts: a new 'anti-system' politics Western democracies are experiencing, shaking the existing consensus around economic integration, free markets and liberal values. This wave takes a variety of forms, but has in common a robust, even violent, rejection of the mainstream political elites and their values, and a demand for governments to act on the sources of social and economic distress and inequality. This article views Brexit as a part of this new anti-system politics, a reaction to the decline in ideological competition in democracies and the increasing impotence of politicians to address the upheavals wrought by global free market capitalism. This reaction has become particularly acute after the financial crisis of the late 2000s, which affected Britain disproportionately, and the failure of austerity policies to revive growth, crystallising the ineffectiveness of existing policies to deal with economic stagnation and cultural change. This policy failure is compounded by a perceived refusal of politicians to engage with the broader public and a lack of real choice between the mainstream political parties. The article will present evidence that a failed policy consensus, a rise in inequality and a decline in the representativeness of political elites, rather than a resurgence of intolerance or xenophobia, are the principal causes of the Brexit vote.
Keywords: Brexit; British economic policy - 2010-; British withdrawal from the European Union, 2016-; Europe - Foreign relations - Great Britain; European Union; Great Britain - politics & government - 2007-; economic nationalism; economics; markets; membership; nationalism; protectionism

The Quest to Bring Land under Social and Political Control: Land Reform Struggles of the Past and Present in Ecuador - Goodwin, Geoff (Journal of Agrarian Change, 2017)
Land reform was one of the most important policies introduced in Latin America in the twentieth century and remains high on the political agenda due to sustained pressure from rural social movements. Improving our understanding of the issue therefore remains a pressing concern. This paper responds to this need by proposing a new theoretical framework to explore land reform and providing a fresh analysis of historical and contemporary land struggles in Ecuador. Drawing on the pioneering work of Karl Polanyi, the paper characterizes these struggles as the attempt to increase the social and political control of land in the face of mounting commodification. The movement started in the 1960s and remains evident in Ecuador today. Exploring land reform in Ecuador from this theoretical perspective provides new insight into land struggles in the country and contributes to debates over land reforms of the past and present elsewhere in the Global South.
Keywords: Ecuador; commodification; land markets; land reform; reforms; social movements

The Second Time Around? Polanyi and Today's Fascist Tendency - Sandbrook, Richard (Peace Magazine, 2017)
Discusses the relevance of Polanyi’s double movement in light of increasing support for far-right, authoritarian and neo-fascist movements in Europe and North America. The author quotes The Great Transformation on how fascism “was rooted in a market system that refused to function” (21), however, he chooses to center his analysis on an unpublished essay of Polanyi’s entitled “The Fascist Virus”. From this, he extrapolates that fascism operates like a disease within liberal capitalism, becoming lethal when tensions between capitalism and democracy hit crisis levels and unleashing itself into the body politic (20).
Keywords: fascism; right-wing populism

Karl Polanyi: A Life on the Left - Kurtz, Geoffrey (New Political Science, 2017)
Keywords: DALE, Gareth; Karl Polanyi: A Life on the Left (Book); book review

What American Government Does - Luger, Stan; Waddell, Brian (JHU Press, 2017)
It has become all too easy to disparage the role of the US government today. Many Americans are influenced by a simplistic anti-government ideology that is itself driven by a desire to roll back the more democratically responsive aspects of public policy. But government has improved the lives of Americans in numerous ways, from providing income, food, education, housing, and healthcare support, to ensuring cleaner air, water, and food, to providing a vast infrastructure upon which economic growth depends. In What American Government Does, Stan Luger and Brian Waddell offer a practical understanding of the scope and function of American governance. They present a historical overview of the development of US governance that is rooted in the theoretical work of Charles Tilly, Karl Polanyi, and Michael Mann. Touching on everything from taxes, welfare, and national and domestic security to the government’s regulatory, developmental, and global responsibilities, each chapter covers a main function of American government and explains how it emerged and then evolved over time. Luger and Waddell are careful to both identify the controversies related to what government does and those areas of government that should elicit concern and vigilance. Analyzing the functions of the US government in terms of both a tug-of-war and a collaboration between state and societal forces, they provide a reading of American political development that dispels the myth of a weak, minimal, non-interventionist state. What American Government Does represents a major contribution to the scholarly debate on the nature of the American state and the exercise of power in America. -- Sidney Plotkin, Vassar College, coauthor of Private Interests, Public Spending: Balanced-Budget Conservatism and the Fiscal Crisis
Keywords: American government; history - Americas (North, Central, South, West Indies); political science - history and theory

Karl Polanyi: a life on the left - Payne, Anthony (International Affairs, 2017)
Keywords: DALE, Gareth; Karl Polanyi: A Life on the Left (Book); POLANYI, Karl, 1886-1964; biography; book review; economists; nonfiction

Karl Polanyi, The Great Transformation and a New Political Economy - Watson, Matthew; Holmes, Christopher; Clift, Ben (brunobertez, 2017)
Karl Polanyi, The Great Transformation and a new political economy Professor Matthew Watson, Assistant Professor Christopher Holmes and Professor Ben Clift, Politics and International Studies Avert…
Keywords: Great Transformation, The (Book); HAYEK, Friedrich A. von (Friedrich August), 1899-1992; KEYNES, John Maynard, 1883-1946; MARX, Karl, 1818-1883

Reviving Hayek’s Dream - Worth, Owen (Globalizations, 2017)
This short piece suggests that the roots of the successful Brexit vote can be found in the free market purity that was implicit within the ideals behind Thatcherism. Whilst the rhetoric of populist and British (or in many parts English) nationalism were utilised in order to win support, the ideological driving force implicit within many Brexit figureheads rested in the belief that the EU watered down their visions of a harder neoliberal reality. Yet, by stimulating right-wing reactionary forces, they may have created more than they bargained for. I concur with Karl Polanyi that free market liberalism tends to generate the forces of its own demise.
Keywords: Brexit; Brexit Referendum, 2016; free enterprise; liberalism; market idealism; neoliberalism; populism; the far right

Karl Polanyi in Dialogue: A Socialist Thinker for our Times - Brie, Michael (Black Rose Books, 2017)
Featuring essays from Michael Brie (Rose Luxemburg Foundation, Berlin), Nancy Fraser (New School for Social Research, New York) and Kari Polanyi-Levitt (McGill University, Montreal). The contemporary Left fights its political battles on various fronts: protesting the crippling structural inequalities that sustain neoliberal economic policy; developing sustainable, community-based alternatives to the consumerism and short-termism that exacerbate the environmental crisis; and advocating for the cultural recognition, emancipation and celebration of the diversity and pluralism of human identity. But despite this versatility the Left appears to be in worldwide retreat whilst an aggressive new ‘Alt-Right’ is taking to the internet and the streets, regurgitating a regressive and patriarchal vision of society that has already won startling political victories in the US and Europe. Amidst the vertiginous tension of such a crisis, Michael Brie argues for an urgent theoretical and practical reorganisation of the Left. Developing the work of philosopher and social theorist Karl Polanyi, Brie advocates an alliance of socialist liberals and libertarian ‘commonists’ that unites contemporary campaigns for recognition, difference and human dignity with more traditional struggles for social welfare and economic democracy. Starting with Nancy Fraser’s critical reappraisal of Polanyi in her article “A Triple Movement? Parsing the Politics of Crisis after Polanyi” (included), Brie powerfully reinterprets Polanyi’s thought for present times, developing concrete proposals for a Polanyian political response to neoliberalism, an ascendent authoritarian right and the ongoing threat of global ecological disaster. Also included are two articles by Polanyi translated into English for the first time and Kari Polanyi-Levitt’s lecture at the Rosa Luxemburg Foundation “From the Great Transformation to the Great Financialisation”.
Keywords: biography; ecology; economics; feminism; history; labor; labour; politics; racism; sociology

The moral economists: R.H. Tawney, Karl Polanyi, E. P. Thompson, and the critique of capitalism - Rogan, Tim (Princeton University Press, 2017)
A fresh look at how three important twentieth-century British thinkers viewed capitalism through a moral rather than material lens What's wrong with capitalism? Answers to that question today focus on material inequality. Led by economists and conducted in utilitarian terms, the critique of capitalism in the twenty-first century is primarily concerned with disparities in income and wealth. It was not always so. The Moral Economists reconstructs another critical tradition, developed across the twentieth century in Britain, in which material deprivation was less important than moral or spiritual desolation. Tim Rogan focuses on three of the twentieth century's most influential critics of capitalism--R.H. Tawney, Karl Polanyi, and E.P. Thompson. Making arguments about the relationships between economics and ethics in modernity, their works commanded wide readerships, shaped research agendas, and influenced public opinion. Rejecting the social philosophy of laissez-faire but fearing authoritarianism, these writers sought out forms of social solidarity closer than individualism admitted but freer than collectivism allowed. They discovered such solidarities while teaching economics, history, and literature to workers in the north of England and elsewhere. They wrote histories of capitalism to make these solidarities articulate. They used makeshift languages of "tradition" and "custom" to describe them until Thompson patented the idea of the "moral economy."
Keywords: HENRY, Richard; PALMER, Edward; TAWNEY, R.H.; THOMPSON, E.P.; capitalism; moral and ethical aspects; moral economy; socialism

Progressive Responses to Populism: A Polanyian Critique of Liberal Discourse - Yarrow, David (The Political Quarterly, 2017)
This article explores the recent rise of populist politics from the perspective of Karl Polanyi's theory of the ‘double movement’. It firstly introduces Polanyi's understanding of interwar populism, and relates this to his broader critique of liberal economic thought. This framework is then used to analyse three prominent explanations for populism which emerged in the wake of the UK's 2016 EU referendum: globalisation; cultural reaction; and social media. I show how each of these explanations exogenises contemporary populist movements, narrating them as something external to the liberal economic restructuring pursued globally since the 1980s. Failing to diagnose adequately the causes of contemporary populist movements, which lie in this utopian attempt to treat labour as a commodity, they cannot support an intellectually coherent progressive response to Brexit. Finally, I outline a political agenda centred on labour de-commodification, which could directly address populist grievances and reclaim the discourse of ‘taking back control’ for the left.
Keywords: Brexit; commodification; double movement; labour; liberal discourse; populism

Karl Polanyi: A Life on the Left - Moravcsik, Andrew (Foreign Affairs, 2016)
Keywords: DALE, Gareth; Karl Polanyi: A Life on the Left (Book); biography; book review; nonfiction; sociologists

Counterbalancing marketization informally: Georgia’s new-institutionalist reform and its discontents - Rekhviashvili, Lela (Debatte: Review of Contemporary German Affairs, 2016)
Discussing the case of institutional change and its discontents in the Georgian context, this article critically engages with one of the most influential perspectives on informal economic practices, namely the new institutionalist perspective. The examination of the responses to the new-institutionalist remedies reveals counterintuitive outcomes to allegedly successful market-enhancing reforms. The reforms were resisted and they failed to deliver the promise of improved entrepreneurial opportunities and eased social vulnerability. I suggest that the new-institutionalist prescriptions result in counterintuitive outcomes as they are based on two misleading assumptions. First, they read informal practices as a priori market-like and second, they see the transition to a market economy as a relatively harmonious process. I argue that, informal economic practices are not necessarily market-like, nor is the establishment of market-enhancing reforms uncontested by informally operating actors. Instead, the persons operating informally draw on non-commodified resources and suffer significant social and economic losses when the state-supported process of marketization deepens. The process of adjusting to marketization and coping with its costs inevitably involves elaboration of practices and interventions that defy and contradict the market logic. Precisely, this dismissal of the need for non-market-based solutions in current theory and practice leads to informalization of the resistance against marketization.
Keywords: Eastern Europe; Georgia; Polanyian institutionalism; informal economic practices; informal sector (economics); marketization; markets; new-institutionalism; organizational change

How Will Capitalism End?: Essays on a Failing System - Streeck, Wolfgang (Verso Books, 2016)
The provocative political thinker asks if it will be with a bang or a whimperAfter years of ill health, capitalism is now in a critical condition. Growth has given way to stagnation; inequality is leading to instability; and confidence in the money economy has all but evaporated.In How Will Capitalism End?, the acclaimed analyst of contemporary politics and economics Wolfgang Streeck argues that the world is about to change. The marriage between democracy and capitalism, ill-suited partners brought together in the shadow of World War Two, is coming to an end. The regulatory institutions that once restrained the financial sector’s excesses have collapsed and, after the final victory of capitalism at the end of the Cold War, there is no political agency capable of rolling back the liberalization of the markets.Ours has become a world defined by declining growth, oligarchic rule, a shrinking public sphere, institutional corruption and international anarchy, and no cure to these ills is at hand.
Keywords: political science / globalization; political science / political economy; political science / political ideologies / democracy

Regulating class in the neoliberal era: the role of the state in the restructuring of work and employment relations - Howell, Chris (Work, Employment & Society, 2016)
The article argues that, in the last three decades, states have become more preoccupied with, and interventionist in, the regulation of class relations in order to facilitate a broad liberalization of employment relations institutions. Drawing on insights from Regulation theorists and Karl Polanyi, the article examines the market-making role of states during periods of transition from one growth regime to another. The more prominent role of the state follows from the stickiness of institutions and the role that states can play in compensating workers from the consequences of liberalization. The article illustrates the argument with an examination of France and Sweden in the period since the early 1980s. For all their differences, in both cases substantial liberalization of employment relations institutions took place and in both cases, but for the state, the process of liberalization would have been either stymied or much more uneven than it was.
Keywords: class; employment relations; liberalization; state

The failure of regulation: Work, environment and production at Taranto’s ILVA - Greco, Lidia; Chiarello, Franco (Economic & Industrial Democracy, 2016)
The article focuses on the case of the largest steel plant in Europe, located in Taranto (Italy), to argue that its current crisis is not simply dictated by technological or managerial failings. Rather, the article contends that its problems stem from a regulatory crisis and, specifically, from the failure of the deregulation model pursued after the industry’s process of privatization. Such a model has hinged upon the logic of a big private firm that, on the one hand, has sought to disembed itself from the socio-institutional context and, on the other, has set and followed its own rules with disruptive effects on the local society and environment, as well as on the plant’s economic viability. Such a model entered a crisis when the other socio-institutional actors started to react to the disastrous situation existing in Taranto. To use Polanyian language, a ‘double movement’ has emerged: disruptive pressures have triggered defensive reactions.
Keywords: Taranto (Italy); economic democracy; employee ownership; employee participation in management; financial crises; financial crisis; industrial democracy; institutional change; privatization - Italy; sociology; technological innovations

Karl Polanyi: The Hungarian Writings - Dale, Gareth (Oxford University Press, 2016)
The work of Karl Polanyi has gained in influence in recent years to become a point of reference to a wide range of leading authors in the fields of economics, politics, sociology, and social policy. The volume is a combination of reflections on, and assessment of, the nature of Polanyi's contribution and new strands of work, both theoretical and empirical, that has been inspired by Polanyi's insights. It gathers together the key contributions to the first ever workshop on the work of Karl Polanyi held in the United Kingdom. The workshop was opened by Kari Polanyi-Levitt, who also has written the Introductory Foreword to this book. Several of the contributions develop Polanyian ideas in relation to contemporary capitalism. However, in a critical spirit, other contributions in the volume substantially transform his concept 'instituted economic process' in considering a broad range of contemporary socio-economic change: markets for mobile telephony, call centre operations, and European labour markets.
Keywords: history - modern; political history; political philosophy; political theory

In search of Karl Polanyi's International Relations theory - Dale, Gareth (Review of International Studies, 2016)
Karl Polanyi is principally known as an economic historian and a theorist of international political economy. His theses are commonly encountered in debates concerning globalisation, regionalism, regulation and deregulation, and neoliberalism. But the standard depiction of his ideas is based upon a highly restricted corpus of his work: essentially, his published writings, in English, from the 1940s and 1950s. Drawing upon a broader range of Polanyi's work in Hungarian, German, and English, this article examines his less well-known analyses of international politics and world order. It sketches the main lineaments of Polanyi's international thought from the 1910s until the mid-1940s, charting his evolution from Wilsonian liberal, via debates within British pacifism, towards a position close to E. H. Carr's realism. It reconstructs the dialectic of universalism and regionalism in Polanyi's prospectus for postwar international order, with a focus upon his theory of 'tame empires' and its extension by neo-Polanyian theorists of the 'new regionalism and European integration. It explores the tensions and contradictions in Polanyi's analysis, and, finally, it hypothesises that the failure of his postwar predictions provides a clue as to why his research on international relations dried up in the 1950s.
Keywords: CARR, Edward Hallett, 1892-1982; deregulation; international relations; liberalism; neoliberalism

The Commonalities of Global Crises: Markets, Communities and Nostalgia - Karner, Christian; Weicht, Bernhard (Springer, 2016)
Bringing together contributions from an international group of social scientists, this collection examines diverse crises, both historical and contemporary, which implicate market forces, widening inequalities, social exclusion, forms of resistance, and ideological polarisation. The Commonalities of Global Crises offers carefully researched case studies which stretch across large geographical distances- from Egypt to the US and from northern, central, eastern and southern Europe to South America- and covers timely issues including human rights, slavery, care, migration, racism, and the far right. The volume demonstrates that such different settings and diverse concerns are characterized by a common tension in which the crises that unfold around pressures of widening marketization and commodification are met by the (re)building or re-assertion of various communities, and competing politics of solidarity and nostalgia.
Keywords: business & economics / general; commodification; disembedding; double movement; economic theory; political science / general; social science / general

The Hill and Knowlton Affair and the Marketization of the First Gulf War. a Polanyian Perspective - Petre, Silviu Valentin (Proceedings of the Scientific Conference AFASES, 2016)
The 1990-1991 First Gulf War became a classic manual of PR or manipulation, depends on the terms one chooses. Within the whole manipulative framework, Hill and Knowlton, one of USA’ s foremost advertising brands played a pivotal, ripple-making role. With the money provided by Kuwaiti government in exile, H&K faked several testimonies according to which Saddam’s soldiers had been responsible of appalling deeds by pillaging Kuwaiti hospitals, where they stole incubators and left newborn babies to die. Thus, President Bush gained legitimacy in front of the US Congress and international fora to assemble a coalition of the willing to deal with Iraqi aggression. This article will not only dwell upon the abovementioned episode, but shall also sketch an explanatory framework using Karl Polanyi’s writings.
Keywords: BUSH, George H.W.; Gulf War; HUSSEIN, Saddam; Hill and Knowlton Strategies (Company); POLANYI, Karl, 1886-1964 - political and social views; Persian Gulf War, 1991; manipulation; manipulative behavior; public opinion; public relations & politics

Bourgeois Equality: How Ideas, Not Capital or Institutions, Enriched the World - McCloskey, Deirdre N. (University of Chicago Press, 2016)
There’s little doubt that most humans today are better off than their forebears. Stunningly so, the economist and historian Deirdre McCloskey argues in the concluding volume of her trilogy celebrating the oft-derided virtues of the bourgeoisie. The poorest of humanity, McCloskey shows, will soon be joining the comparative riches of Japan and Sweden and Botswana.   Why? Most economists—from Adam Smith and Karl Marx to Thomas Piketty—say the Great Enrichment since 1800 came from accumulated capital. McCloskey disagrees, fiercely. “Our riches,” she argues, “were made not by piling brick on brick, bank balance on bank balance, but by piling idea on idea.” Capital was necessary, but so was the presence of oxygen. It was ideas, not matter, that drove “trade-tested betterment.”  Nor were institutions the drivers. The World Bank orthodoxy of “add institutions and stir” doesn’t work, and didn’t. McCloskey builds a powerful case for the initiating role of ideas—ideas for electric motors and free elections, of course, but more deeply the bizarre and liberal ideas of equal liberty and dignity for ordinary folk. Liberalism arose from theological and political revolutions in northwest Europe, yielding a unique respect for betterment and its practitioners, and upending ancient hierarchies. Commoners were encouraged to have a go, and the bourgeoisie took up the Bourgeois Deal, and we were all enriched.   Few economists or historians write like McCloskey—her ability to invest the facts of economic history with the urgency of a novel, or of a leading case at law, is unmatched. She summarizes modern economics and modern economic history with verve and lucidity, yet sees through to the really big scientific conclusion. Not matter, but ideas. Big books don’t come any more ambitious, or captivating, than Bourgeois Equality. KM - Part IV heavily engages with Polanyi's ideas, including embeddedness
Keywords: Europe; business & economics; economic history; embeddedness; history; political science; political theory; social science

The Great Acceleration: An Environmental History of the Anthropocene since 1945 - McNeill, J. R. (Harvard University Press, 2016)
The pace of energy use, greenhouse gas emissions, and population growth has thrust the planet into a new age—the Anthropocene. Humans have altered the planet’s biogeochemical systems without consciously managing them. The Great Acceleration explains the causes, consequences, and uncertainties of this massive uncontrolled experiment.
Keywords: anthropocene; history / modern / 20th Century; history / world; nature / environmental conservation & protection; political science / public policy / environmental policy

Fair trade certification as oversight: an analysis of fair trade international and the small producers' symbol - Clark, Patrick; Hussey, Ian (New Political Economy, 2016)
In this article we analyse Fair Trade as a form of non-state regulation, building on the literature on the internal politics and governance of Fair Trade International (FTI) certification. We focus on recent developments in the FTI certification system, including the split of Fair Trade USA from FTI and the emergence of the Small Producer's Symbol (SPP) as an alternative to FTI certification. We highlight the role of the three regional Producer Networks, in particular the Latin American Producer Network, the CLAC, in the politics and governance of the FTI system. In order to analyse these issues we employ an alternative reading of Karl Polanyi's work in relation to Fair Trade. We problematise the claim made by some in the literature that FTI certification is an example of Polanyi's concept of re-embedding. Instead, we draw on Polanyi's concept of oversight to analyse Fair Trade certification. We argue that the emergence of the SPP out of the CLAC shows promise for being a mechanism of oversight more reflective of Polanyian re-embedding than FTI certification. We also emphasise how the growth of the SPP and the pressure from the Producer Networks have prompted governance reform within the FTI system.
Keywords: Canada; Carleton University; European Union countries; certification; economic conditions; fair trade; financial crises; financial crisis; governance; liberalization (finance); municipal services; producer networks; small producers; unfair competition

Revisiting Free Market Utopia: A Hayek-Polanyi Reminder - Usenmez, Ozgur; Duman, Levent (Journal of Economic and Social Thought, 2016)
As pundits discuss the causes and results of the 2008 financial crisis and ensuing Great Recession, economists of various strands--led mainly by Keynesians--are slowly beginning to question the supposed wisdom of unfettered markets. Since Keynesian-liberal disputes revolve around the symptoms of the crisis rather than the historical and structural features of market economies, we thought that a Hayek-Polanyi comparison would be a timely intervention in order to understand the real nature of the subject. This comparison may also pave the way for the creation of an alternative to the vagaries of unfettered markets.
Keywords: Austrian; HAYEK, Friedrich A. von (Friedrich August), 1899-1992; Keynesian; Keynesianism; business fluctuations; cycles; evolutionary; financial crises; financial markets; financial markets and the macroeconomy; general aggregative models: Keynes; history of economic thought: individuals; institutional; post-Keynesian

Governing by Panic - Woodruff, David M. (Politics & Society, 2016)
The Eurozone’s reaction to the crisis beginning in late 2008 involved not only efforts to mitigate the arbitrarily destructive effects of markets but also vigorous pursuit of policies aimed at austerity and deflation. To explain this paradoxical outcome, I build on Karl Polanyi’s account of a similar deadlock in the 1930s. Polanyi argued that a society-protecting response to malfunctioning markets was limited under the gold standard by the prospect of currency panic, which bankers used to push for austerity, deflationary policies, and labor’s political marginalization. I reconstruct Polanyi’s “governing by panic” theory to explain Eurozone policy during three key episodes of sovereign bond market panic in 2010–12. By threatening to allow financial panics to continue, the European Central Bank promoted policies and institutional changes aimed at austerity and deflation, limiting the protective response. Germany’s Ordoliberalism, and its weight in European affairs, contributed to the credibility of this threat.
Keywords: European Central Bank; Eurozone; Eurozone crisis; Eurozone debt crisis; depressions (economics) - 1929; economic conditions; euro; governing by panic; ordoliberalism

The new agrarian double movement: hegemony and resistance in the GMO food economy - Carroll, Myles (Review of International Political Economy, 2016)
This paper draws on the work of Antonio Gramsci and Karl Polanyi in analyzing the consequences of legal regimes that regulate genetically modified foods. Against the tide of neoliberalism, a binding, precautionary agreement over trade in genetically modified organisms (GMOs) has emerged through the Cartagena Protocol on Biosafety. This Protocol exemplifies what Polanyi termed the ‘self-protection of society,’ the second phase of his double movement. The Protocol's final form was a product of European governments’ responses to public concerns over the potential environmental and health impacts of GMOs in an unregulated global economy. This ‘self-protective’ turn has been manifest at regional and national scales, including in Australia. Drawing on Gramsci, I argue that this unlikely turn emerged in the context of shifting public opinion, effective anti-GMO activism, and alternative discursive framings. It took hold with European publics and governments, generating the relations of force needed to become the hegemonic framing of GMOs globally. The objectives of this paper are thus to demonstrate how a double movement has occurred in the regulation of GMOs and to use Gramsci's relations of force to explain how this double movement has nonetheless failed to challenge the underlying neoliberal basis of GMO agriculture as it exists today.
Keywords: Australia; GMOs; agriculture - Australia; biosafety; double movement; economics; hegemony; international political economy; law; political economy; relations of force; transgenic organisms

Market Reforms and Water Wars - Simmons, Erica S. (World Politics, 2016)
Responses to the imposition of market-oriented economic policies have varied. This article asks two questions: (1) How can we better understand when marketization will or will not prompt resistance? And (2) when people do mobilize, why are some movements broad-based while others draw on particular segments of society? The author argues that these questions can best be answered by focusing not only on the political contexts and resources available to potential social movements, but also on what is perceived to be at stake during marketization. These perceptions influence mobilization processes and the kinds of groups available for mobilization. When people understand markets as threatening to material wellbeing, as well as to widely shared community relationships, understandings, and commitments, heightened feelings of group belonging can contribute to broad-based mobilization. The author develops this argument through analysis of the broad-based, widespread movement that emerged to protest water privatization in Cochabamba, Bolivia, in 1999 and 2000. In the context of a history of agriculture, irrigation, drought, and conflict, water helped to produce and reproduce imagined communities of nation, region, and ethnic group, as well as quotidian communities revolving around the routine production and consumption of water. These meanings help to explain the dynamics of the resistance that emerged.
Keywords: Latin America; marketization; political science; social movements; water wars

Reconstructing Karl Polanyi - Dale, Gareth (Pluto Press, 2016)
Karl Polanyi was one of the most influential political economists of the twentieth-century and is widely regarded as the most gifted of social democrat theorists. In Reconstructing Karl Polanyi, Gareth Dale draws upon primary sources archived in the countries that Polanyi called home—Hungary, Austria, Britain, the United States, and Canada—to provide a sweeping survey of his contribution to the social sciences. Polanyi’s intellectual and political outlook can best be summarized through paradoxical formulations such as ‘romantic modernist’, ‘liberal socialist’, and ‘cosmopolitan patriot.’ In exploring these paradoxes, Dale excavates and reconstructs Polanyi’s views on a range of topics that have been neglected in the critical literature, including Keynesian economic policy, the evolution and dynamics of Stalin’s Russia, regional integration, and McCarthyism. He reinterprets Polanyi’s philosophy of history, his theory of democracy, and his economic historiography of Ancient Greece and Mesopotamia, and guides readers through Polyani's critical dialogue with Marxism. While the central threads and motifs of this study are intellectual-historiographical in nature, Dale also critically analyzes the views of Polanyi and his followers on issues of pressing present-day relevance, notably the clash between democracy and capitalism, and the nature and trajectory of European unification.
Keywords: political theory; social theory

Treble Troubles? Marketization, Social Protection and Emancipation Considered Through the Lens of Slavery - Davidson, Julia O’Connell (The Commonalities of Global Crises, 2016)
This chapter considers white European and American thinking on transatlantic slavery historically and, more briefly, in relation to today’s antislavery movement. Combining historical longue durée and a critical engagement with Nancy Fraser’s neo-Polanyian position, O’Connell Davidson shows that abolitionists were, and are, hard to fix as proponents of either market freedom or social protection, or indeed of ‘emancipation’. The postabolition experience of freed slaves shows that marketization, social protection and emancipation are not fully disarticulable political forces, suggesting that the idea of the ‘triple movement’ may be less useful for those committed to a politics of nondomination than it may initially appear.
Keywords: economics; public choice; slavery; social choice; social inequality; social protection; social structure; triple movement; welfare economics

Singapore’s Social Contract Trilemma - Yeoh, Lam Keong; Auyong, Hawyee; Yeo, Andrew Zhi Jian (Globalization and Democracy in Southeast Asia, 2016)
The last 50 years of nation building has firmly established Singapore as a globally competitive and highly successful economy and city-state with one of the highest per capita incomes in the world. Singapore has achieved a prosperity undreamed of by its founders. How successfully Singapore can evolve into a fully developed nation, with a firm sense of national belonging, social cohesion, political legitimacy and participation—and not just a strong and successful developmental state—will depend on the extent to which the country is able to translate this success to broader social protection and democratic participation for her people, and the extent to which the country is able to forge a common national identity.
Keywords: FRASER, Nancy; Singapore; democracy; double movement; globalization; neo-Polanyian; policy studies; triple movement

Polanyi in the European Single Market: The Re- Regulation of Insurance - Mabbett, Deborah (Economic Sociology: The European Electronic Newsletter, 2015)
This article discusses the difference between a social policy approach to the regulatory embedding of a market and a moral economy approach using the insurance case wherein the European Union's Court of Justice ruled that insurers may not discriminate on grounds of sex in identifying risks.
Keywords: Court of Justice of the European Union; insurance; lawsuits & claims; reembedding; regulation; social policy

Benjamin Cohen on global political order: when Keynes meets realism – and beyond - Guzzini, Stefano (Contexto Internacional, 2015)
This article analyses the trajectory of Benjamin J. Cohen's work by focusing on his ongoing concern with the nature and governance of world order. It does so by playing out his debt to realism and to Keynesianism. In a first moment, Cohen criticises the economic determinism of dependency scholarship, while turning to political realism, and then to possible Keynesian co-operation under anarchy: agents have the power to affect positive change. Later, Cohen the disillusioned Keynesian, watching how the possible reform of financial markets is marginalised by politicians and academics alike, shifts his analysis to more structural aspects of governance or rule that affect actors' preferences. I draw two conclusions. First, in this shift towards theorising the global political order away from steering capacity towards impersonal rule and bias, Cohen also questions the very setup of the theories with which we deal with that world – only to see that this very inspiration of original IPE is abandoned in the course of the ongoing ‘professionalisation' of IPE as practised in the United States. Second, his analysis seems to incorporate a warning. The underlying grand question is nothing less than the bargain between capitalism and liberal democracy as we know it, since the present system undermines equality before the law – money trumps equal political rights – and undermines democratic accountability. One of the main achievements of the post-war Keynesian turn was the reappropriation of political space from anti-democratic forces. Therefore, the decline of Keynesianism could provoke a Polanyian nightmare in which the ‘double movement' by which the laissez-faire is answered by moves to protect society does not strengthen democracies, as in earlier times of ‘embedded liberalism', but undermines them instead.
Keywords: COHEN, Benjamin J.; Keynesian economics; capitalism; dependency; embedded liberalism; global governance; international finance; international relations; political realism; securities markets; structural power

Polanyi, Hayek, and the Impossibility of Libertarian Ideal Theory - Lindsay, Peter (Polity, 2015)
In 1944, two seminal works of political and social theory appeared: F.A. Hayek's The Road to Serfdom and Karl Polanyi's The Great Transformation. Both works focused on society's spontaneous resistance to the 'marketization' of life. Yet, the authors arrived at opposite normative conclusions. This article attributes the normative distance to a methodological clash over the role and limits of normative theorizing in the concrete and sometimes uncooperative world of politics. This clash, in turn, illuminates recent debates about 'ideal' and 'non-ideal' theory, and suggests limits to the applicability of the former.
Keywords: Great Transformation, The (Book); HAYEK, Friedrich A. von (Friedrich August), 1899-1992; Road to Serfdom (book); free enterprise; free markets; ideal theory; laissez-faire; libertarian theory; non-ideal theory

Gellner’s genealogy of the open society: Biopolitics as fragment and remainder - Ryan, Kevin (Thesis Eleven, 2015)
A decade before Foucault began to work with the related concepts of biopolitics and biopower, Gellner posed a series of questions which are suggestive of a similar line of inquiry. Gellner did not pursue this strand of his thought as an historical sociologist however. Instead he packaged it into a functionalist account of how industrial society reproduces itself. In Gellner’s writings, biopolitics is both present and absent, like a redacted text. This is the focus of this article, which locates Gellner’s method of inquiry within a corpus of genealogical studies that includes the work of Polanyi, Weber and Foucault. What distinguishes Gellner is that the history he reconstructs is a story of achievement in the face of terrible historical odds, but this culminates in a normative genealogy that limits the scope for critical analysis. The article concludes by adopting an alternative – yet still Gellnerian – approach to the question of social reproduction, thereby using Gellner to critique Gellner.
Keywords: FOUCAULT, Michel, 1926-1984; GELLNER, Ernest; biopolitics; biopolitics (philosophy); biopower; genealogy; historical sociology; realism; social aspects

The Bioeconomy as Political Project: A Polanyian Analysis - Goven, Joanna; Pavone, Vincenzo (Science, Technology & Human Values, 2015)
The bioeconomy is becoming increasingly prominent in policy and scholarly literature, but critical examination of the concept is lacking. We argue that the bioeconomy should be understood as a political project, not simply or primarily as a technoscientific or economic one. We use a conceptual framework derived from the work of Karl Polanyi to elucidate the politically performative nature of the bioeconomy through an analysis of an influential Organization for Economic Cooperation and Development (OECD) initiative, The Bioeconomy to 2030. We argue that this initiative is a response to some of the most acute challenges facing the current neoliberal-capitalist accumulation regime, which seeks to protect and extend that regime, through both what it occludes and what it promotes. Rather than taking the bioeconomy as a description of some subset of economic activity, we regard it as a promissory construct that is meant to induce and facilitate some actions while deterring others; most explicitly, it is meant to bring about a particular set of political–institutional changes that will shape the parameters of possible future action. The bioeconomy concept highlights the potential dangers of failing to situate ethnographic examinations of horizontal micro-relations within a political–economic macro-context that enables and constrains. Scholarly work in science and technology studies and elsewhere that does not recognize the wider politics of the bioeconomy risks unintentionally contributing to the legitimation of this political project.
Keywords: bioeconomy; commodification; cooperation; economics; ethnographic analysis; futures; inequality; literature; markets/economies; neoliberalism; organization; politics

The Great Mindshift: Linking Forerunners of a New Sustainability Paradigm - Gopel, Maja (Brookings Inst Press, 2015)
Making sustainability a policy goal is one of the greatest challenges of the 21st century. Calls for a paradigm shift are becoming increasingly frequent and urgent. In fact, change toward a sustainable form of society seems to be more within reach than ever before. The mindset of people has changed in the course of economic and environmental crises. This publication presents the current scientific and practical approaches that shape and empower the process of change toward true sustainability. It also raises the question as to the new possibilities that may arise from linking these approaches.
Keywords: environmental policy; environmental science; global warming & climate change; public policy; science

The limits to China's non-interference foreign policy: pro-state interventionism and the rescaling of economic governance - Gonzalez-Vicente, Ruben (Australian Journal of International Affairs, 2015)
China's foreign policy has been long committed to a principle of non-interference in the internal affairs of sovereign countries. While one could easily point out past and present-day inconsistencies in its implementation, this article argues that defenders and critics of the principle both rely on a limited interpretation of ‘interference’ or ‘intervention’ based on an ideology of Westphalian sovereignty. Particularly problematic is the conceptual distinction between the ‘political’ or ‘diplomatic’, on the one hand, and the ‘economic’, on the other. As Polanyi's concept of embeddedness reminds us, markets, society and politics occur simultaneously, and can only act as discrete realms in epistemological abstractions. It is thus argued that non-interference is a semi-formal institution that governs China's diplomatic engagements and affects its economic activities. While the totality of China's interactions with the world has diverse and sometimes contradictory impacts on global governance, non-interference itself has apparent consequences for the rescaling of regional economic governance. Specifically, this article contends that Chinese non-interference results in the empowerment of political elites at national levels, and thus in the (re-)emergence of the nation state as a gatekeeper and facilitator of the advancement of capitalist enterprises. As a result, through non-intervention, China's foreign policy undermines supranational regulatory approaches and fosters state-based regional architectures.
Keywords: China; China - foreign relations; People's Republic of China; Westphalians - foreign countries; bilateralism; economic policy; embeddedness; foreign policy; non-interference; socioeconomic theory; supranationalism

The power of market fundamentalism: Karl Polanyi's critique - Gamble, Andrew (Cambridge Review of International Affairs, 2015)
Keywords: BLOCK, Fred; Power of Market Fundamentalism: Karl Polanyi's Critique, The (Book); SOMERS, Margaret R.; markets; nonfiction; review

Mutating Neoliberalism: The Promotion of Italian Investors in Slovakia before and after the Global Financial Crisis - Sellar, Christian; Pástor, Rudolf (International Journal of Urban & Regional Research, 2015)
In the context of the literature on 'actually existing neoliberalisms', this article analyzes the policies and services supporting Italian foreign direct investment (FDI) in Slovakia. It identifies a group of organizations, both Slovak and Italian, which shape and deliver neoliberal pro-FDI policies. By studying such an 'investment promotion community' (IPC) before and after the global financial crisis of 2009, and during Italy's prolonged crisis, this article shows both the persistence and adaptability of neoliberal policies and institutions. In so doing, it highlights some of the transnational flows underpinning the 'domestication' of neoliberalism in Slovakia. These findings support recent literature arguing that post-crisis neoliberalism can be interpreted as a stunted Polanyian double movement, in which the state has improved some of its regulatory functions but without questioning the overarching neoliberal principles. Specifically, it shows that FDI policies and the support of Italian investors rest upon a professional community that has not changed much since the 2009 crisis. This community played a crucial role in embedding neoliberal rationalities in Slovakia and supports the persistence of this ideology in the post-crisis environment.
Keywords: Bratislava; Italy; Košice; Kralovsky Chlmec; Slovakia; Slovakia - economic conditions; Slovakia - foreign economic relations; capitalists & financiers; double movement; financial crisis; foreign direct investment; foreign investments; global financial crisis, 2008-2009; neoliberalism

Toward a Sartrean Economics - Kail, Michel; Sobel, Richard (Rethinking Marxism, 2015)
Despite the absence of a systematic analysis of economics in Sartre's work, we argue that a Sartrean economics can indeed be said to exist, even if it is an economics that still awaits development. The status that Sartre accords to the concept of scarcity allows him to advance the critique of economism begun by Karl Polanyi, who, for his part, had been satisfied simply to challenge the reduction of economics to its formal definition. Scarcity, Sartre teaches us, should not be submitted to the process of instrumental reason but should be considered as a fact of human history. Economic analysis, meanwhile, should not be based solely on the theme of man's confrontation with a typically ungrateful nature but should rather be articulated through the concept of the world as elaborated in Sartrean philosophy.
Keywords: POLANYI, Karl, 1886-1964; SARTRE, Jean-Paul, 1905-1980; economic systems; economism; scarcity; world

The Limits of Transformation: Contemporary Applications of Karl Polanyi - England, Christopher (Journal of Australian Political Economy. Summer2015/16, Issue 76, 2015)
The article explores the conception of the Great Transformation (GT) by economic historian Karl Polanyi and its contemporary applications. Topics covered include the continued existence of free market fundamentalism as a prominent ideology and as a living political project, the persistence of free market utopianism, and Polanyi's genealogy of the market system. Also discussed are his conception of industrialism and his use of functionalist theory to build a unified image of the social system.
Keywords: economics; free enterprise; functionalism; industrialism; political economy; social systems; utopias

A Reversed Double Movement in Brazil: The (Controversial) Evolution of the Partido dos Trabalhadores' Education Policy since 1980 - Guedes-Neto, Joao Victor (Journal of International Studies, 2015)
Karl Polanyi identified a double movement which took place during the bourgeoisie hegemony when, instead of liberalism, it has made use of interventionism to perpetuate its domination over the working class. Several studies have tried to update his analysis by identifying the double movement nowadays. Nevertheless, the academia has not addressed the possibility of a reversed phenomenon where the working class would make use of liberalism to perpetuate itself in power. This paper aims at analyzing the Brazilian case where the Partido dos Trabalhadores, a proxy for the working class, has implemented pro-market policies in higher education. Whereas the party has not passed through structural reforms such as the British and German working class parties, it has drastically changed its approach to policy-making and campaigning since its origin in 1980. The study concludes that a reversed double movement may occur when the working class is in charge of the government.
Keywords: double movement; economic development; education; education: government policy; human development; human resources; income distribution; migration; national government expenditures and education

Contesting 'Actually Existing' Neoliberalism - Ryan, Matthew (Journal of Australian Political Economy, 2015)
The article explores the established conception of actually existing neoliberalism. Topics covered include free-market neoliberalism, the nature of neoliberal theory, and the distinction between esoteric and exoteric neoliberalisms. Also discussed are the ideas of scholars Karl Polanyi and Ha-Joon Chang about the role of the state in capitalist development, and scholar Damien Cahill's idea that neoliberalism is defined by microeconomic policies of privatization, marketization and deregulation.
Keywords: CAHILL, Damien; CHANG, Ha-Joon; esotericism; free enterprise; neoliberalism; political economy

Greening of Capitalism: How Asia Is Driving the Next Great Transformation - Mathews, John (Stanford University Press, 2014)
As China, India, and other industrializing giants grow, they are confronted with an inconvenient truth: They cannot rely on the conventions of capitalism as we know them today. Western industrialism has achieved miracles, promoting unprecedented levels of prosperity and raising hundreds of millions out of poverty. Yet, if allowed to proceed unencumbered, this paradigm will do irreversible harm to the planet. By necessity, a new approach to environmentally conscious development is already emerging in the East, with China leading the way. Positioning its argument against zero-growth advocates and free-market environmentalists, Greening of Capitalism charts this transformation and sketches out a framework for more sustainable capitalism. State-mandated changes in energy use (as opposed to carbon taxes), a circular flow of resources (as opposed to emissions standards), and the introduction of new financial instruments that support green growth are cornerstones of China's framework. John A. Mathews argues that these tenets will be emulated around the worldfirst in India and Brazil. In light of this emerging shift, Mathews considers core debates over national security, international relations, and economic policy, ultimately addressing the question of whether these measures will be far-reaching or timely enough to prevent further damage.
Keywords: business & economics; economic policy; energy; government & business; industries; public policy; sustainable capitalism

Polanyian Reading of the Socio-Economic Transformations of the European Union - Savevska, Maja (Journal of Contemporary European Studies, 2014)
In an attempt to analyse the socio-economic transformations of the European Union, an increasing number of scholars have resorted to Polanyi's double movement thesis. In doing so, some scholars, by looking at the evidence of intensified marketisation of social relations, consider the EU disembedded; whereas others identify a re-embedding tendency in the recent surge of socio-environmental protection. The paper follows Lacher, Burawoy, Dale and Streeck's readings of Polanyi and argues that the exiting socio-environmental provisions do not re-embed the economy. Socio-environmental protection does not eclipse the neoliberal accumulation strategy which continues to propagate the disembedding tendency, because it fails to decommodify fictitious commodities. The EU is characterised by a heightened intensification of both disembedding and protective tendencies, which Polanyi contends is disruptive in nature. What emerges out of the dialectics between neoliberalisation and socio-environmental provisions is a decelerated rate of change, which, although it temporarily secures the habitation of man, prevents the inception of a synthesis that is capable of sublating the contradictions of the marketisation/protection binary. Moreover, we have a paradoxical situation wherein the socio-environmental measures, despite their protective invocation, are predicated on deepened commodification.
Keywords: European Union; commodification; disembedded; double movement; international political economy; neoliberalism; socioeconomics

On the Dialectics of Global Governance in the Twenty-first Century: A Polanyian Double Movement? - Patomäki, Heikki (Globalizations, 2014)
Following decades of economic globalisation and market-oriented reforms across the world, Karl Polanyi'sdouble movementhas been invoked not only to explain what is happening but also to give reasons for being hopeful about a different future. Some have suggested a pendulum model of history: a swing from markets to society leading, in the next phase, to a swing from society to markets, and so on. The double movement can also be understood dialectically as a description of an irreversible historical development following its own inner laws or schemes of development. Going beyond a thesis–antithesis–synthesis pattern, I maintain that conceptions and schemes drawn from dialectics, and especiallydialectical critical realism, can provide better geo-historical hypotheses for explaining past changes and for building scenarios about possible future changes. I analyse political economy contradictions and tendencies, and focus on normative rationality, to assess substantial claims about rational tendential directionality of world history. I argue that democratic global Keynesianism would enable processes of decommodification and new syntheses concerning the market/social nexus. A learning process towards qualitatively higher levels of reflexivity can help develop global transformative agency. Existing contradictions can be resolved by means of rational collective actions and building more adequate common institutions. These collective actions are likely to involve new forms of political agency such as world political parties. (English)
Keywords: 21st century; Keynesian economics; contradiction; critical realism; dialectic; double movement; economics - history; global governance; globalization; market; political economy; political parties; scenario; utopia

Class Struggle or Embedded Markets? Marx, Polanyi and the Meanings and Possibilities of Social Transformation - Selwyn, Benjamin; Miyamura, Satoshi (New Political Economy, 2014)
Marx and Polanyi both held that socialism, in one form or another, was a preferable and possible alternative to capitalism. Their ideas are seen to offer theoretical tools to understand the tensions and contradictions of capitalism, and to inform ways to overcome them. This paper discusses Polanyi's work from a Marxist perspective in order to illuminate his strengths and weaknesses. Its main focus is to discuss Polanyi's juxtaposing of commodification against exploitation, in diagnosing the problems of capitalist expansion. We suggest that by juxtaposing these two moments, Polanyi not only misses out on a crucial arena of capitalist activity (exploitation), but also undermines his own explication of processes of commodification. This has deleterious consequences for his understanding of the prevalence of poverty under capitalism. It also means that his vision of social transformation and of socialism is profoundly different, and potentially antithetical, to that of Marx. We suggest that for Polanyi's conception of de-commodification to gain greater traction it needs to be combined with Marx's analysis of exploitation and class struggle.
Keywords: MARX, Karl, 1818-1883; Polanyi; commodification; exploitation; historical materialism; institutionalism

Reclaiming Karl Polanyi, Socialist Intellectual - Clark, Timothy David (Studies in Political Economy, 2014)
The crisis of neoliberal globalization has led many scholars back to Karl Polanyi in their search for alternatives to the present malaise. The dominant reading appropriates the concepts of embeddedness and the double movement in support of a system of regulated, welfare-state capitalism. This article contends, however, that the concepts of embeddedness and the double movement point not towards the need to regulate capitalist markets, but towards the radical supersession of capitalism itself.
Keywords: Canada; capitalism; globalization; radical change

Making Capitalism Fit For Society - Crouch, Colin (John Wiley & Sons, 2014)
Capitalism is the only complex system known to us that can provide an efficient and innovative economy, but the financial crisis has brought out the pernicious side of capitalism and shown that it remains dependent on the state to rescue it from its own deficiencies. Can capitalism be reshaped so that it is fit for society, or must we acquiesce to the neoliberal view that society will be at its best when markets are given free rein in all areas of life? The aim of this book is to show that the acceptance of capitalism and the market does not require us to accept the full neoliberal agenda of unrestrained markets, insecurity in our working lives, and neglect of the environment and of public services. In particular, it should not mean supporting the growing dominance of public life by corporate wealth. The world’s most successful mature economies are those that fully embrace both the discipline of the market and the need for protection against its negative outcomes. Indeed, a continuing, unresolved clash between these two forces is itself a major source of vitality and innovation for economy and society. But maintenance of that tension depends on the enduring strength of trade unions and other critical groups in civil society - a strength that is threatened by neoliberalism’s increasingly intolerant onward march. Outlining the principles for a renewed and more assertive social democracy, this timely and important book shows that real possibilities exist to create a better world than that which is being offered by the wealthy elites who dominate our public and private lives.
Keywords: business & economics; capitalism; economic theory

The Passage West: Philosophy After the Age of the Nation State - Marramao, Giacomo (Verso Books, 2014)
In this ambitious work, Giacomo Marramao proposes a radical reconceptualization of the world system in our era of declining state sovereignty. He argues that globalization cannot be reduced to mere economics or summarized by phrases such as ‘the end of history’ or the ‘westernization of the world’. Instead, we find ourselves embarking on a passage to a new, post-nation state age destined to transform all civilizations – and to disrupt Western geopolitical dominance. To confront the challenges of this interregnum one must think in terms of a new and radical universalism, a universalism of difference able to revitalize politics and to demythologize identity.Building on the great interwar discussion between Spengler, Junger, Schmitt and Heidegger, Marramao’s new work engages with Habermas, Derrida and post-colonialism. Arguing against the classic Western pretension to universal norms of democracy and reason, he develops instead the idea of a ‘universal politics of difference’. KM - contains chapter: Gift, exchange, obligation: Karl Polanyi and social philosophy
Keywords: exchange; international relations; religious philosophy; social philosophy

Law and Politics in Europe's Crisis: On the History of the Impact of an Unfortunate Configuration - Joerges, Christian (Constellations, 2014)
EXCERPT [KM]: Karl Polanyi has experienced a renaissance in recent years.13 We refer to his work in our remarks on the failures of the European project for three interrelated reasons: (1) Polanyi has underlined that modern markets were not generated by some evolutionary process but established by political planning.14 Europe's “internal market project” is the best conceivable confirmation of his thesis. (2) One of the most important insights of his work concerns the “social embeddedness” of markets and the economy.15 These insights are of crucial importance because Europe has on the one hand realized that the functioning of markets requires comprehensive regulatory activities but at the same time tends to disregard the economic, political and cultural variety and dependence of markets. (3) Polanyi can also provide clarity with regard to the growing skepticism about so many firmly held beliefs about the benefits of ever more European integration. EXCERPT 2: Led by the prompting of its highest court, Europe is waving the flag of economic freedoms of Europe's market citizens and is retreating from its commitment to collective labor law – once the institutionalized countermovement to the commodification of labor.1
Keywords: European Union; economic law; fictitious commodities; internal market project; social embeddedness

Polanyi in Brussels or Luxembourg? Social rights and market regulation in European insurance - Mabbett, Deborah (Regulation & Governance, 2014)
The decision of the Court of Justice of the European Union to ban sex discrimination in insurance has shown the potential reach of the principle of non-discrimination. This paper discusses the different positions taken by participants in the policy process leading up to the decision, in order to reveal the potential and limitations of non-discrimination as the basis for market-regulatory social policy. It is shown that the European Commission's initial support for prohibiting insurance discrimination faltered with the realization that the measure would have little efficacy as a distributive social policy. It was left to the Court to assert that non-discrimination rights are constitutive for European markets, regardless of their functional and instrumental limitations. The Court's focus was on the market-integrative potential of rights as sources of norms for the conduct of insurance relationships. It is argued that this form of constitutive regulation is distinct from distributive social policy as it does not require that outcomes are egalitarian, but, rather, that the processes governing market relations should respect fundamental rights.
Keywords: Gender Directive; discrimination; insurance; rights; social regulation

Moral versus Commercial Economies: Transylvanian Stories - Velicu, Irina (New Political Science, 2014)
Historically, the production of a market society has depended on the commodification of valuables such as land and labour, which has also meant the disembedding of capital from elements of the “primordial,” such as kinship, spiritual relations, and identities. Today we are still witnessing the invocation of such elements of moral economies as a basis for people's collective mobilization against market pressures. The case study in this article refers to Rosia Montana, a semi-urban village in Transylvania where a Canadian corporation is planning to create the largest cyanide opencast mine in Europe. Through attempts at privatizing and commodifying whole areas of social life, the market logic promoted by the corporation in the last twelve years portrays the mine as the “only alternative” for the development of the region. Rosieni and activists have blocked the project for more than fourteen years by reclaiming other fundamental values related to spirituality, ancestry, land, and nature. They challenge the prevailing violence of the market by problematizing the logic of the commercial economy and by re-evaluating what the corporate project devalues. How does the post-communist context inspire a moral critique of global corporate capitalism and a democratic socialist alternative? In this article Polanyi's argument related to the “fictitious commodities” of the market will be used to support the argument that moral principles inspire forms of resistance against commodification in the former Eastern bloc and may produce future alternative forms of development. If one noticed an increase in social and environmental activism in Romania over the last five years would it also be due to the perseverance of Rosieni and its supporters in challenging not only a corporation and some co-opted/corrupted officials, but an entire dominant discourse of neoliberalism?
Keywords: Canadian corporations; Rosia Montana; Transylvania (Romania); commodification; corporate capitalism; disembeddedness; economic aspects; moral economy; neoliberalism

The Rise and Fall of Ireland's Celtic Tiger: Liberalism, Boom and Bust - Ó Riain, Seán (Cambridge University Press, 2014)
In 2008 Ireland experienced one of the most dramatic economic crises of any economy in the world. It remains at the heart of the international crisis, sitting uneasily between the US and European economies. Not long ago, however, Ireland was celebrated as an example of successful market-led globalisation and economic growth. How can we explain the Irish crisis? What does it tell us about the causes of the international crisis? How should we rethink our understanding of contemporary economies and the workings of economic liberalism based on the Irish experience? This book combines economic sociology and comparative political economy to analyse the causes, dynamics and implications of Ireland's economic 'boom to bust'. It examines the interplay between the financial system, European integration and Irish national politics to show how financial speculation overwhelmed the economic and social development of the 1990s 'Celtic Tiger'.
Keywords: business & economics; economic conditions; economic development; economic history; economic policy; liberalism; political science; public policy

Marketisation, public services and the city: the potential for Polanyian counter movements - Warner, Mildred E.; Clifton, Judith (Cambridge Journal of Regions, Economy and Society, 2014)
Marketisation of urban service delivery gained renewed intensity in the crisis. Mobilising Polanyi’s concept of double movement, we analyse how marketisation of public services both creates and constrains the potential for urban counter movements in the USA and Europe. We identify three main urban responses: ‘hollowing out’, where cities engage in service cut backs; ‘riding the wave’, where cities attempt to harness the market; and ‘push backs’, where cities and citizen movements oppose marketisation. Although the city is constrained by marketisation at national and international levels, we find evidence of push back and, in it, the potential for public service alternatives.
Keywords: city; crisis; double movement; marketisation; public services; urban studies

Karl Polanyi in Vienna - Dale, Gareth (Historical Materialism, 2014)
In this article I discuss Polanyi's intellectual formation in early twentieth-century Budapest and in 1920s Vienna, focusing in particular upon his relationship to Guild Socialist and Marxist theory and to Austrian Social Democracy. It was a period in which Marxism was evolving rapidly, and Polanyi was too. In his twenties, he reacted forcefully against what he saw as the evolutionary and deterministic traits of Marxist philosophy. In his thirties, his relationship to Marxism underwent a 'double movement': his long-held doubts about Marxism crystallised into an forceful critique, swiftly followed by a sympathetic dialogue with the ideas and politics of Austro-Marxism, the 'Rousseauian' commitments of which were not unlike his own. I examine Polanyi's relationship with Marxism in each of these phases, and explore the affinities between Guild Socialism and Austro-Marxism. The final section introduces the distinctly un-Polanyian analysis of Austrian Social Democracy offered by Polanyi's wife, Ilona Duczynska.
Keywords: 20th century; Austria; Austro; Austro-Marxist school; DUCZYNSKA, Ilona; Hungary; Marxism; Marxist philosophy; ROUSSEAU, Jean-Jacques; Vienna (Austria); biography; communism; determinism; functional theory; guild socialism; history; intellectual life; social democracy

The Global Development Crisis - Selwyn, Benjamin (John Wiley & Sons, 2014)
The central paradox of the contemporary world is the simultaneous presence of wealth on an unprecedented scale, and mass poverty. Liberal theory explains the relationship between capitalism and poverty as one based around the dichotomy of inclusion (into capitalism) vs exclusion (from capitalism). Within this discourse, the global capitalist system is portrayed as a sphere of economic dynamism and as a source of developmental opportunities for less developed countries and their populations. Development policy should, therefore, seek to integrate the poor into the global capitalist system. The Global Development Crisis challenges this way of thinking. Through an interrogation of some of the most important political economists of the last two centuries Friedrich List, Karl Marx, Leon Trotsky, Joseph Schumpeter, Alexander Gerschenkron, Karl Polanyi and Amarta Sen, Selwyn argues that class relations are the central cause of poverty and inequality, within and between countries. In contrast to much development thinking, which portrays ‘the poor’ as reliant upon benign assistance, this book advocates the concept of labour-centred development. Here ‘the poor’ are the global labouring classes, and their own collective actions and struggles constitute the basis of an alternative form of non-elitist, bottom-up human development.
Keywords: business & economics / development; economic development; embedded markets; political science / public policy / general; socialism

Neo-pluralist political science, economic sociology and the conceptual foundations of the comparative capitalisms literatures - Bruff, Ian; Hartmann, Eva (Capital & Class, 2014)
In this paper, we critically assess two of the key conceptual foundations for the comparative capitalisms (CC) literatures, neo-pluralist political science and economic sociology, in order to identify more clearly the deep intellectual roots of these literatures. Principally, we focus on how the strengths of neo-pluralism and economic sociology – their attention to detail in considering the huge range of ‘types’ of capitalism that exist across the world – come at a high price. Put briefly, the redefinition of ‘capitalism’ as ‘the economy’ concentrates research agendas on the specific political and social conditions found across the world, leaving ‘the economy’ relatively untouched. In consequence, ‘capitalist diversity’ is quickly, and often silently, equated to ‘political diversity’ or ‘social diversity’. As such, a key weakness of CC scholarship, identified by various authors in this Capital & Class special issue – that it does not provide a satisfactory theoretical understanding of capitalist societies – is a problem that runs deeper than the limitations that can be observed in contemporary debates. The implications of our argument are discussed in the conclusion.
Keywords: capitalism; capitalist diversity; comparative capitalisms; economic sociology; neo-pluralism; political economy

The Polanyian Perspective Meets the Varieties of Capitalism: Inspecting the Consequences of the Institutional Changes in South Korea since 1997 - Šitera, Daniel (Perspectives: Central European Review of International Affairs, 2014)
This article attempts to combine the Polanyian perspective on the issue of market societies with an the analysis of the institutional foundations of capitalism that is facilitated by the Varieties of Capitalism(VoC) approach. The article departs fromthe argument that the VoC school has upgraded our insight into the institutional working ofmodern capitalism, but became entrapped in an overt structuralismwhich considers institutional change as just an interplaywithin a self-odering institutional structure.However, the article employs Karl Polanyi's doublemovement, the dialectic of marketizing dis-embedding and socializing re-embedding, to demonstrate that the institutional changemust be rather conceived as embedded in a social life. Only then can one recognize considers that such a change is primarily conditioned by social contests among sentient agents which engage in an ideational struggle over its final outcome. These theoretical reconsiderations are tested on the empirical terrain of Korean capitalism after the Asian Crisis of 1997 and the Global Crisis of 2007. First, the double movement is used to demonstrate that the post-crises institutional changes have transformed Korean capitalism's institutional and societal model from developmentalism to embedded neoliberalism. Second, it is documented that this transformation has been characteristic of certain ideational struggles which turned into a socially contested, largely contradictory, uneven, and open-ended process.
Keywords: Asia; POLANYI, Karl, 1886-1964; South Korea; capitalism; developmentalism (economics); double movement; financial crises; global financial crisis, 2008-2009; international affairs; neoliberalism; varieties of capitalism

Kari Polanyi: Nine Decades of Scientific and Militant Life - Rioux, Michele (Revue interventions economiques/Papers in Political Economy, 2014)
Keywords: biography; history of economic thought: individuals

The double movement and new labor market regulations in Korea, Japan, and Taiwan - Yun, Ji-Whan (A comparative study of East Asian capitalism, 2014)
Keywords: Japan; Korea; Taiwan; consolidation; diverging paths; double movement; dual labour markets; economics; labour; labour market reforms; politics and government; systemic change

Transforming Capitalism: The Triple Crisis - Kirby, Peadar (Irish Journal of Sociology, 2013)
This article identifies a triple crisis of capitalism based on the three fictitious commodities as identified by Karl Polanyi: labour, money and land. This framework is used to integrate the environmental crisis into the wider crisis of capitalism. It argues that international actions required to reduce greenhouse gas emissions are going to present major challenges for capitalism with implications for the current dominance of market power and the subservience of state and social power. The article critically examines the potential of climate capitalism to achieve a low-carbon society by 2050 and introduces the need to face the challenges of degrowth.
Keywords: climate capitalism; climate change; de-growth; degrowth; development models; fictitious commodities; sustainability

The Politics of Dispossession: Theorizing India’s “Land Wars” - Levien, Michael (Politics & Society, 2013)
While struggles over land dispossession have recently proliferated across the developing world and become particularly significant in India, this paper argues that existing theories of political agency do not capture the specificity of the politics of dispossession. Based on two years of ethnographic research on anti-dispossession movements across rural India, the paper argues that the dispossession of land creates a specific kind of politics, distinct not just from labor politics, but also from various other forms of peasant politics that have been theorized in the social sciences. It illustrates how the process of land dispossession itself shapes the targets, strategy and tactics, organization, social composition, goals, and ideologies of anti-dispossession struggles. It concludes with reflections on why land conflicts are less easily institutionalized than labor conflicts and may therefore constitute a significantly disruptive force in the emerging centers of global capitalism for the foreseeable future.
Keywords: India; accumulation by dispossession; agrarian change; agriculture; capitalism; eviction; land grabs; peasant politics; peasants; property rights; social movements

From the Great Transformation to the Great Financialization: On Karl Polanyi and Other Essays - Polanyi Levitt, Kari (Zed Books, 2013)
Four years into the unfolding of the most serious crisis since the 1930s, Karl Polanyi's prediction of the fateful consequences of unleashing the destructive power of unregulated market capitalism on peoples, nations, and the natural environment have assumed new urgency and relevance. Polanyi's insistence that 'the self-regulating market' must be made subordinate to democracy otherwise society itself may be put at risk is as true today as it was when Polanyi wrote. Written from the unique perspective of his daughter, From the Great Transformation to the Great Financialization is an essential contribution to our understanding of the evolution and contemporary significance of Karl Polanyi's work, and should be read against the background of the accelerating accumulation of global finance that created a series of financial crises in Latin America, Russia, Asia, and, eventually, the heartlands of capitalism itself.
Keywords: HAYEK, Friedrich A. von (Friedrich August), 1899-1992; Latin America; business & economics; economic conditions; economic development; economic history; global financial crisis; political economy; political science

Cosmologies and Regionalisms from ‘Above’ and ‘Below’ in the post-cold war Americas: the Relevance of Karl Polanyi for the 21st century - Roncallo, Alejandra (Third World Quarterly, 2013)
Drawing on a Polanyian analysis of the land question, this article aims to analyse both Western and Indigenous cosmologies of Abya Yala—the name that indigenous peoples give to the American continent—to understand the relationship between human beings and land and nature. These cosmologies are at the heart of the way in which two distinct societies construct their regional space, one from ‘above’, the other from ‘below’, and they are therefore key to understanding today’s climate change problématique. Following this nexus it is argued that, since the end of the Cold War, a new regional ‘double-movement’, unleashed by the quest for land and natural resources has been in the making. This is a superstructural or legal battle between Western transnational regime-making and a law that originated at the ‘centre of the Earth’. The article explains both regionalisms and the dialectical interaction between them and demonstrates that Karl Polanyi’s legacy remains relevant for the 21st century.
Keywords: climate change; cosmologies; double movement; indigenous land question

Polanyi's Magnum Opus ? Assessing the Application of the Counter-Movement in International Political Economy - Worth, Owen (International History Review, 2013)
The concept of the ‘counter-movement’ has had a significant impact within studies in International Political Economy (IPE). In the light of the credit crisis and the growth of growing resentment to the notion of the free market, the idea of the counter-movement has been utilised to understand social reaction to neoliberalism. This article argues that whilst the counter-movement has been used in unique and innovated ways, Karl Polanyi himself used the term largely to refer to a specific period in nineteenth-century British history. This article argues that whilst the counter-movement remains interesting, its application remains open to scrutiny. It questions whether the concept was indeed central to Polanyian economic thought and how much can be given to it in today's contemporary era of neoliberalism. It also suggests that by focusing merely on the counter-movement, Polanyian accounts within IPE are in danger of ignoring much of his wider critique of market economics.
Keywords: capitalism; countermovement; economic policy; equilibrium (economics); foreign investments; free enterprise; international economic relations; international political economy; neoliberalism

From Neoliberalism to Pluralism: A Response to Mulheirn and Jacobs - Finlayson, Alan (The Political Quarterly, 2013)
This essay puts into context the debate between Michael Jacobs and Ian Mulheirn, exploring the theories and themes underpinning their arguments, published in issue 84 1 of the Political Quarterly. It discusses, firstly, the roots of Mulheirn's approach in European neoliberalism and, secondly, the roots of Jacobs' approach in a range of sources currently contending for authority over debates within the Labour party. These include themes drawn, broadly, from Polanyi, Keynes, Schumpeter and Schumacher. In a conclusion the article makes the case for a ‘pluralistic’ to the organisation of political and economic power in the UK.
Keywords: neoliberalism; pluralism; political economy; social market

Fortunes of Feminism: From State-Managed Capitalism to Neoliberal Crisis - Fraser, Nancy (Verso Books, 2013)
Charts the history of women’s liberation and calls for a revitalized feminism.Nancy Fraser’s major new book traces the feminist movement’s evolution since the 1970s and anticipates a new—radical and egalitarian—phase of feminist thought and action.During the ferment of the New Left, “Second Wave” feminism emerged as a struggle for women’s liberation and took its place alongside other radical movements that were questioning core features of capitalist society. But feminism’s subsequent immersion in identity politics coincided with a decline in its utopian energies and the rise of neoliberalism. Now, foreseeing a revival in the movement, Fraser argues for a reinvigorated feminist radicalism able to address the global economic crisis. Feminism can be a force working in concert with other egalitarian movements in the struggle to bring the economy under democratic control, while building on the visionary potential of the earlier waves of women’s liberation. This powerful new account is set to become a landmark of feminist thought.
Keywords: critical theory; feminism; feminist theory; triple movement

Ignorance, denial, internalisation, and transcendence: a post-structural perspective on Polanyi's double movement - Holmes, Christopher (Review of International Studies, 2013)
In this article, I suggest what an engagement between post-structuralism and the work of Karl Polanyi might look like. I do this by presenting a reading of Polanyi's concept of ‘double movement’ as a form of problematisation through binary opposition. I suggest that the central opposition that the double movement depicts – between economy and society as reflected in processes of marketisation and social protection – presents itself in such a way that the problems emanating from the opposition can only be solved through its transcendence. On one hand, the terms of transcendence are limited by the terms of the opposition. On the other hand, since transcendence is never reached, the double movement problematisation stabilises the existence of a lacuna between the lived experience of market society and the discursive field of that market society. As such, the form of the problematisation places a double-limit upon the ways in which ‘solutions’ can be presented. I present this thesis in relation to two instances of double movement discussed by Polanyi in his book, The Great Transformation. I then apply the argument to invocations of the economy-society opposition in contemporary political economic discourse, where it remains as ubiquitous as ever.
Keywords: Great Transformation, The (Book); denial (psychology); double movement; ignorance (theory of knowledge); political economic analysis; postmodernism; poststructuralism; social aspects

From Blue to Green and Everything in Between: Ideational Change and Left Political Economy after New Labour - Finlayson, Alan (British Journal of Politics & International Relations, 2013)
This article argues that ideational and institutionalist approaches to the study of policy continuity and change should be complemented by research into political ideologies, and with exploration of an 'intermediate' public sphere in which there is extensive intra-ideological dispute. Exploring contemporary left-wing debate about political economy in Britain it is shown that ideational change takes place in the context of disputes rooted in ideological tradition, involving the rearrangement of concepts, the emphasising of some and the marginalisation of others. In the present moment that debate is marked by what may be thought of, heuristically, as 'Keynesian', 'Polanyian', 'Schumpeterian' and 'Schumacherian' points of reference. Assessing the likelihood of this debate developing into a coherent 'crisis narrative' it is shown that the development of the relationship between these poles will be decisive but that at present they stumble over the conceptualisation of 'equality' and 'the state'.
Keywords: Great Britain; discursive and rhetorical institutionalism; economic conditions; equality; labour party; political doctrines; political economy; political ideology; politics and government; social attitudes

Europe and Problems of Marketization: from Polanyi to Scharpf - Crouch, Colin (Firenze University Press, 2013)
The author uses the theory of the 'Great Transformation' of the industrialisation of England developed by Karl Polanyi to describe the current situation in Europe. There is a strong marketisation of the economy and also of social life, but what is missing is the social policy that needs to accompany this process, if there are not to be major problems. From this perspective marketization and social policy do not exist in a zero-sum game, but are mutually dependent. The emphasis on negative rather than positive integration (to use the terms conceived by Fritz Scharpf) in the development of Europe makes this interdependence more difficult to achieve. The division of competences between the European level (market policies) and the nation states (social policies) makes this situation even worse. The only way forward is a strengthening of the European social dimension.
Keywords: Europe; business & economics; commodification; economic theory; social policy

A Triple Movement? - Fraser, Nancy (New Left Review, 2013)
Keywords: double movement; social protection; triple movement

Adam Smith's Green Thumb and Malthus's Three Horsemen: Cautionary Tales from Classical Political Economy - Dale, Gareth (Journal of Economic Issues (Taylor & Francis Ltd), 2012)
This essay identifies a contradiction between the flourishing interest in the environmental economics of the classical period and a lack of critical parsing of the works of its leading representatives. Its focus is the work of Adam Smith and Thomas Malthus. It offers a critical analysis of their contribution to environmental thought and surveys the work of their contemporary devotees. It scrutinizes Smith's contribution to what Karl Polanyi termed the "economistic fallacy," as well as his defenses of class hierarchy, the "growth imperative" and consumerism. It subjects to critical appraisal Malthus's enthusiasm for private property and the market system, and his opposition to market regulation. While Malthus's principal attraction to ecological economists lies in his having allegedly broadened the scope of economics, and in his narrative of scarcity, this article shows that he, in fact, narrowed the scope of the discipline and conceptualized scarcity in a reified and pseudo-scientific way.
Keywords: MALTHUS, T. R.; SMITH, Adam, 1723-1790; classical political economy; consumerism; ecological economics; economistic fallacy; environmental economics; environmental policy; growth imperative; natural capital; scarcity

Exchange Rising? Karl Polanyi and Contentious Politics in Contemporary Latin America - Silva, Eduardo (Latin American Politics and Society, 2012)
Free-market reforms in the last quarter of the twentieth century weakened the point of production—labor unions—as the source of effective nonparty political countermovement to liberal capitalism. Has another significant source of societal resistance arisen in association with the resurgence of market economics? Building on the work of Karl Polanyi, this article argues that circuits of exchange—the commodification of labor, land, and money—can be powerful sources of movement against contemporary forms of free-market capitalism. It draws on the cases of Argentina, Bolivia, and Ecuador to explore how Polanyi's exchange-based approach helps to elucidate three phenomena: the great variety of identities behind the myriad movements against free-market capitalism, the emergence of community as a powerful locus for organizing, and the proliferation of new forms of transgressive and highly disruptive direct action to reinforce the debilitated effectiveness of the strike.
Keywords: Latin America; circuits of exchange; countermovement

Solidarity Economy in Brazil: Movement, Discourse and Practice Analysis Through a Polanyian Understanding of the Economy - Lemaître, Andreia; Helmsing, A. H. J. (Bert) (Journal of International Development, 2012)
Solidarity economy (SE) initiatives constitute a worldwide phenomenon that is today at the heart of numerous economic and social debates. They are active in very diverse economic sectors, aiming for example to create employment for poor and low-qualified workers. We begin with presenting a Polanyian framework for the analysis of such economic activities, which enables us to develop a plural and integral conception of a productive organisation. We draw on Polanyi's thesis that economy is a political and institutionalised process and present a historic overview of the construction of the SE ‘sector’ in Brazil. We put forward the hypothesis that the SE today in Brazil represents a social movement. Then, we ask ourselves if the SE movement led to a change in grassroots economic initiatives, such as ‘people's cooperatives’. We present the results of exploratory research undertaken on 15 people's cooperatives in the State of Rio de Janeiro and its conclusions. Copyright © 2012 John Wiley & Sons, Ltd.
Keywords: Brazil; inclusion; international development; local development; people's cooperative; social movement; solidarity economy

The missing movement: a Polanyian analysis of pre‐crisis America - Herman, Dan (International Journal of Social Economics, 2012)
The purpose of this paper is to seek to apply Polanyi's theory of the double movement as a response to the effects of economic liberalization and globalization to the pre‐2007 American economy. In so doing, it seeks to ascertain the reasons why this assumed double movement did not materialize until after the post‐2007 global economic crisis. Design/methodology/approach – This paper is structured as a theoretical and historical analysis, building upon Polanyi's nineteenth century observations and applying them to contemporary policy economic and social experience in the USA in the late twentieth century. The argument proposes a correlation between the missing and/or delayed movement and the role of access to debt and participation in equity markets. Findings – This paper argues that Polanyi's concept of a societal countermovement has been absent from the post‐1970 period of economic liberalism and globalization until just recently due to an explicit attempt by the forces of capital to circumvent its role in lessening the harmful effects of American capitalism. In particular, the double movement that should have sought to lessen income inequality, unemployment and wage stagnation was instead replaced by access to cheap credit and the democratization of market investments that spurred consumer purchases and a false belief that what was good for the markets was good for working class Americans. Research limitations/implications – This paper highlights the need for ongoing research into the sociotropic nature of trade and of economic policy, and its evolution throughout the contemporary period of economic uncertainty and economic transition. Practical implications – The paper proposes several policy implications arising from the contemporary application of Polanyi's double movement, notably related to international trade and public and political support for ongoing trade liberalization. Social implications – This paper highlights important connections in the relationship between economic policy and the day‐to‐day lives of those who are governed by it. Building on “everyday political economy”, it provides a foundation for arguments that a new balance must be found between economic globalization and transnational capital interests and domestic stability. Originality/value – This paper promotes a novel approach to understanding the political economy of pre‐2007 America, in particular the reflexive nature of economic policy and societal perceptions.
Keywords: countermovement; double movement; economic liberalization; global economic crisis; globalization

Karl Polanyi: The Limits of the Market - By Gareth Dale - Langton, Robert W. (Political Studies Review, 2012)
The article reviews the book "Karl Polanyi: The Limits of the Market," by Gareth Dale.
Keywords: DALE, Gareth; Karl Polanyi: The Limits of the Market (Book); book review; nonfiction

What can Okun teach Polanyi? Efficiency, regulation and equality in the OECD - Hopkin, Jonathan; Blyth, Mark (Review of International Political Economy, 2012)
Arthur Okun famously argued that “effciency is bought at the cost of inequalities in income and wealth”. Okun's trade-off represents the antithesis to Karl Polanyi's view of the relationship that the more embedded markets are in society, the better the social and economic outcomes they produce. This paper refines both these views. We argue that not all forms of market embeddedness are created equal, and that the relationship between equality and efficiency can be both positive and negative. We show this by examining how different ways of embedding economic activity in society through market regulation produce different combinations of efficiency and equality. We identify empirically three broad patterns: market liberal regulatory frameworks that promote competitive markets without decommodifying institutions; embedded liberal regulations that allow markets to work efficiently, but within the framework of decommodification and equality; and embedded illiberalism, where regulations hinder markets in favor of powerful social groups and where decommodification undermines both efficiency and equality. Okun's trade-off emerges as a special case limited to the English-speaking democracies: other OECD countries tend to exhibit either efficiency and equality together, or inefficiency and inequality together. These findings suggest a corrective to both nave market liberal views of the incompatibility of efficiency and equality, but also to the more sophisticated Varieties of Capitalism framework, which pays insufficient attention to the ways in which markets can be embedded in stable but apparently dysfunctional institutional arrangements.
Keywords: OECD; OKUN, Arthur; critique; embeddedness; international political economy; regulation

A Polanyian Analysis of Capitalism: A Commentary on Fred Block - Bandelj, Nina (Political Power & Social Theory, 2012)
This chapter responds to Fred Block's article about the weaknesses of the concept of capitalism because of its close association with Marxism, and his proposal for a Polanyian analysis of political economy. In this chapter, I interrogate what may be the commonalities as opposed to divergences between Marx and Polanyi, and I question whether the concept of capitalism is really so wedded to Marxism so as to loose its analytic value, and be better replaced by notions such as market society, or political economy, as used by Polanyi. I agree with Block that a Polanyian analysis importantly widens our view beyond economic reductionism to an understanding of economy and society as co-constitutive. However, I see utility in adding the qualifier "capitalist" to "political economy" to differentiate between socialist and capitalist political economies, for instance, and to properly characterize a system based on private property rights, guided by pursuit of material gain, which advantages some strata in society more than others, leading to endemic social inequality. I propose that a Polanyian focus on society and economy as co-constitutive is more effectively coupled with an analysis that considers capitalism not as a self-driven system of surplus extraction and accumulation, but as an institutional order dependent on political choices. Such a perspective would advance a Polanyian analysis of capitalism.
Keywords: BLOCK, Fred L.; Marxist philosophy; capitalism; economics; equality; market society; political economy; political science

Double movements and pendular forces: Polanyian perspectives on the neoliberal age - Dale, Gareth (Current Sociology, 2012)
In the neoliberal era, Karl Polanyi’s notion of the ‘double movement’ has been widely deployed by social scientists as a critique of the prevailing order and a predictor of its demise. This article presents the double movement theorem, drawing upon Polanyi’s published and unpublished writings. It explores parallels between his explanation of the advent of the 19th-century free-market regime in Britain and recent Polanyian accounts of the rise of neoliberalism. Following an analysis of the ‘pendular’ refunctioning of Polanyi’s thesis, it closes by asking whether the recent global financial crisis heralds a pendulum swing from neoliberalism (or ‘market fundamentalism’) towards a form of socially coordinated capitalism, or towards ‘more of the same’. As of 2011, it appears that neoliberal policy and ideology remain hegemonic, not in reinvigorated form but as an ‘undead’ policy regime, one that has spawned a burgeoning literature on ‘zombie capitalism’ and ‘zombie neoliberalism’.
Keywords: Great Britain; Great Britain - economic conditions - 19th century; crise financière; crisis financiera; double movement; financial crises; financial crisis; free enterprise; international competition; mouvement double; movimiento doble; neoliberalism; neoliberalismo; néolibéralisme; social scientists; zombi; zombie

Global Climate Governance: A Legitimation Crisis - Van Vossole, Jonas (Review: A Journal of the Fernand Braudel Center, 2012)
This article frames the failure of COP19 in Warsaw, the problems of the RIO+20 summit, the failure of the Copenhagen COP15, and the problems of the carbon markets within a broader legitimacy crisis of global governance, a consequence of the crisis of the global capitalist socio-ecology. Two mechanisms give rise to the loss of legitimacy: unequal development and mercantilization, or the reconfiguration of the power balance and the destruction of social ties. As a consequence, both winners and losers contest the legitimacy of the institutions and mechanisms that govern global capitalism. In this article, we distinguish between Marx-type contestation, referring to emerging classes/states, and Polanyi-type contestation, referring to the victims of global mercantilization. As related to climate governance, the roles of the BRICs in climate negotiations and the global environmental justice movement represent these two types of contestation of the established organizational structures within the global capitalist socio-ecology.
Keywords: 21st century; BRICS countries - environmental conditions; BRICS countries - politics & government; MARX, Karl, 1818-1883; alienation; capitalism; climate governance; decision making in environmental policy; globalization & politics; history; organizational legitimacy; power (social sciences); research

Embeddedness and regional integration: waiting for Polanyi in a Hayekian setting - Hopner, Martin; Schêfer, Armin (International Organization, 2012)
This article analyzes the social potential of regional integration processes by using the example of European integration. Recent case law from the ECJ has led some observers to argue that judicial decisions increasingly provide European politics with a ôPolanyianö drive. We test this claim by distinguishing three dimensions to European economic and social integration: market-restricting integration, market-enforcing integration, and the creation of a European area of nondiscrimination. We also identify two forms of integration that have different speeds, scopes, and potentials: political integration and judicial integration. The evidence shows that the EU has come closer to Hayek's vision of ôinterstate federalismö than is usually warranted because market-enforcing integration and European nondiscrimination policies have asymmetrically profited from ôintegration through lawö.
Keywords: European-integration; HAYEK, Friedrich A. von (Friedrich August), 1899-1992; embeddedness; regional integration; regional-integrationá

Neoliberalism through the Lens of 'Embeddedness' - Paton, Joy (Neoliberalism: Beyond the Free Market, 2012)
Keywords: capitalist systems; history of economic thought: individuals; history of economic thought: macroeconomics; political economy

Critique of Current Neoliberalism from a Polanyian Perspective-Politics, Philosophy, and Economics - Seccareccia, Mario (International Journal of Political Economy, 2012)
An introduction is presented which discusses articles within the issue on topics including neoliberalism, the Austrian economist Karl Polanyi's perspective on the history of industrial society during the nineteenth and twentieth centuries and free enterprise.
Keywords: POLANYI, Karl, 1886-1964; free enterprise; neoliberalism; political economy

Beyond Neoliberalism? Crisis and the Prospects for Progressive Alternatives - Cahill, Damien (New Political Science, 2011)
The onset of the current global economic crisis was hailed by many as signalling the demise of neoliberal hegemony. Two years on however, neoliberalism appears to be quite durable. Indeed, after a brief period of Keynesian-type responses, states, on the whole, have embraced neoliberal solutions to the fiscal problems generated by the crisis. Greece, for example, is now following an IMF programme of privatisation and cuts to social expenditure, while other European nations are pursuing austerity policies. In the USA, state and municipal governments are selling off public assets in response to mounting deficits. This paper explains the durability of neoliberalism and the opportunities and challenges it creates for non-neoliberal progressive policy agendas. Drawing upon Karl Polanyi's conceptual framework, this paper argues that neoliberalism is best understood as a historically specific process of state and economic restructuring that is socially embedded through three mechanisms: ideological norms, class relations, and institutional rules. This paper examines responses by states to the crises and concludes that, although the ideological legitimacy of neoliberalism has been somewhat weakened, there is little evidence to suggest that the three mechanisms, through which neoliberalism is socially embedded, have been significantly eroded. The implication for progressive politics is that, just as neoliberalism is socially embedded, so would a successful progressive non-neoliberal political programme need to be socially embedded: through the articulation of a coherent alternative ideology; through the mobilisation of social forces; and through the institutionalisation of non-neoliberal rules and norms within the apparatuses of the state.
Keywords: Keynesian economics; economic policy; global financial crisis, 2008-2009; neoliberalism; progressivism; social embeddedness

Polanyi and Post-neoliberalism in the Global South: Dilemmas of Re-embedding the Economy - Sandbrook, Richard (New Political Economy, 2011)
Although Karl Polanyi Studied a different epoch and focused on Europe, his ideas have inspired an outpouring of studies on contemporary problems and prospects in the neoliberal era. The bulk of these studies pertain to industrial countries or global economic issues. However, the human, environmental and financial impact of market deregulation is arguably more devastating in the ‘developing’ countries than in the core. A question thus arises: do Polanyi's reflections on progressive alternatives to liberalism clarify contemporary debates on development alternatives in the Global South? I contend that democratic socialism – Polanyi's preferred remedy to the ‘demolition’ of society and nature occasioned by market civilisation – is problematical in light of what we have learned from the twentieth century, but his framework for evaluating alternatives – featuring the re-embedding of economy in society – remains as powerful as ever, I support this argument with an exploration of socialism and social democracy – as well as community – based alternatives arising from ‘reciprocity’. Each possibility raises distinctive dilemmas, as an analysis of cases reveals.
Keywords: Global South; communitarianism; development alternatives; global south; globalisation; globalization; political economy; post-neoliberalism; social democracy; socialism

The Embedded Firm: Corporate Governance, Labor, and Finance Capitalism - Williams, Cynthia A.; Zumbansen, Peer (Cambridge University Press, 2011)
The globalization of capital markets since the 1980s has been accompanied by a vigorous debate over the convergence of corporate governance standards around the world towards the shareholder model. But even before the financial and economic crisis of 2008/2009, the dominance of the shareholder model was challenged with regard to persisting divergences and national differences in corporate law, labor law and industrial relations. This collection explores this debate at an important crossroads, echoing Karl Polanyi's famous observation in 1944 of the disembeddedness of the market from society. Drawing on pertinent insights from scholars, practitioners and regulators in corporate and labor law, securities regulation as well as economic sociology and management theory, the contributions shed important light on the empirical effects on the economy of the shift to shareholder primacy, in light of a comprehensive reconsideration of the global context, policy goals and regulatory forms which characterize market governance today.
Keywords: business & economics / management; corporate governance; disembeddedness; international law; political science / public policy / economic policy

Lineages of Embeddedness: On the Antecedents and Successors of a Polanyian Concept - Dale, Gareth (American Journal of Economics & Sociology, 2011)
Since the 1980s, much debate has revolved around Karl Polanyi's concept of the 'dis/embedded economy,' generating some light and not a little heat. This paper looks at three reasons that account for part of the 'heat.' It begins by tracing the sources upon which Polanyi drew. They include Karl Marx, Ferdinand Tönnies, and Max Weber, along with anthropology of the inter-war period, and German and American Institutionalist economics. After exploring the differing ways in which these varying currents conceptualize the relationship between economy and society, I explore the different interpretations of what Polanyi means by embeddedness, and the different purposes to which contemporary economic sociologists have put the term. For some, he is held up as the originator of a line of sociological analysis that treats 'the economy' as a subsystem 'embedded in' a social system. In this reading the emphasis is upon the moral underpinnings of market behavior, in contrast to the naturalism of Ricardo, Malthus and their heirs. For others, his 'disembedding' thesis contains a more radical tale: of the market economy coming to dominate 'society,' bringing forth a sorcerer's apprentice world of untrammeled market forces that, although human creations, lie beyond conscious human control.
Keywords: MARX, Karl, 1818-1883; POLANYI, Karl, 1886-1964; TONNIES, Ferdinand, 1855-1936; WEBER, Max, 1864-1920; economic philosophy; economics; embeddedness; influence (psychology); intellectual life - history; socioeconomics

Conceptualizing the Economic Role of the State: Laissez-Faire, Technocracy, and the Democratic Alternative - Sabeel Rahman, K (Polity, 2011)
This article contrasts three visions of political economy that appear in the writings of Keynes, Hayek, and Polanyi, and discusses their relevance to current debates over economic policy in the United States. Keynes proposed optimizing market practices through technocratic governance. In recent decades, this influential approach has proven vulnerable to the revival of Hayek's laissez-faire arguments. Polanyi, by contrast, introduced a framework that criticizes both laissez-faire conceptions and the technocratic approach pioneered by Keynes. Because of its emphasis on democratic participation, Polanyi's reasoning provides the building blocks for a new type of contemporary progressive politics.
Keywords: HAYEK, Friedrich A. von (Friedrich August), 1899-1992; KEYNES, John Maynard, 1883-1946; United States; economic policy; free enterprise; government regulation; progressivism; the state

The second great transformation: Towards a solidarity society - Brie, Michael; Klein, Dieter (International Critical Thought, 2011)
The double transition to a society based on unfettered capital valorisation, which attempts to legitimize itself by claiming to be a democratic society founded on human rights, can be defined as the first great transformation of the contemporary period. These bourgeois capitalist societies are now in a crisis of their reproduction, integration, rule and security. Three possible scenarios can be discerned: the first attempts to continue the present development (conventional world), the second, the formation of authoritarian fortresses in the centres within an ocean of insecurity and degradation, or, the third, a new transformation to a solidaristic social development. This transformation would begin in capitalism and at the same time point beyond it to a society whose most important goal is the development of free individuals through solidarity-based associations in the economy, in politics and in culture. Its basis would be a solidarity-based multi-sector economy and a participatory democracy. Although the totality of a new society cannot be anticipated, concrete entry projects for a new second transformation can be developed.
Keywords: capitalism; double transformation; socialism; solidarity economy

Positivism and 'Functional Theory' in the Thought of Karl Polanyi, 1907-1922 - Dale, Gareth (Sociology Compass, 2011)
Karl Polanyi is the author of a modern social science classic, The Great Transformation, as well as a number of well-known and widely debated essays collected in Trade and Market in the Early Empires and Primitive, Archaic and Modern Economies. These texts were researched and written either during his second exile in 1930s Britain or in wartime or post-war North America. Not so well known, however, are his Hungarian writings from the 1910s. Until recently, very few of these had been republished or translated, although this is in the process of being rectified [: Karl Polanyi: The Hungarian Writings]. With reference to new translations of his Hungarian writings, to interviews with his daughter, Kari Polanyi-Levitt, as well as to biographical essays by György Litván, Évá Gábor, Endre Kiss, and Zoltán Horváth, this article explores his early influences, drawing attention in particular to his flirtation with and then violent reaction against philosophical materialism and 'objectivist' sociology, his appreciation of Ernst Mach's positivism, and his adherence to the 'functional theory' of contemporary Guild Socialism.
Keywords: positivism; religion; social sciences; socialism

Polanyi on Markets, Democracy and the Crisis of Liberalism - Ebner, Alexander (The Beginnings of Scholarly Economic Journalism, 2011)
Karl Polanyi, who was born in 1886 in Vienna and died in 1964 in Pickering, Ontario remains a most influential theoretical figure in the social sciences, in particular stimulating both analytical and policy-related concerns that are related with the new institutionalism in economics, sociology and political science. Polanyian insights on the political economy of economic development from an institutional perspective have persistently shaped a variety of discourses that range from the theory of the welfare state to research in comparative economic systems and economic anthropology. Polanyi’s “Great Transformation” may be singled out as a key contribution to both the domains of economic sociology and political economy, as it addresses basic tensions between the developmental dynamics of the market economy and the institutional substance of political democracy (Block 2001).
Keywords: crisis of liberalism; early writings; methodology; methodology of the social sciences

Marketization, Social Protection, Emancipation: Toward a Neo-Polanyian Conception of Capitalist Crisis - Fraser, Nancy (Business as Usual: The Roots of the Global Financial Meltdown, 2011)
BOOK ABSTRACT: Situates the current crisis in the historical trajectory of the capitalist world-system, showing how the crisis was made possible not only by neoliberal financial reforms but by a massive turn away from manufacturing things of value towards seeking profit from financial exchange and credit. Much more basic than the result of a few financial traders cheating the system, this is a potential historical turning point. In original essays, the contributors establish why the system was ripe for crisis of the past, and yet why this meltdown was different. The volume concludes by asking whether as deep as the crisis is, it may contain seeds of a new global economy, what role the US will play, and whether China or other countries will rise to global leadership. Contributors include: Giovanni Arrighi, Gopal Balakrishnan, Manuel Castells, Daniel Chirot, Fernando Coronil, Nancy Fraser, James K. Galbraith, David Harvey, Caglar Keyder, Beverly J. Silver, and Immanuel Wallerstein. The three volumes can purchased individually or as a set. Business as Usual is the first part of a trilogy comprised of the first three books in the Possible Future series. Volume 1: Business as UsualVolume 2: The Deepening CrisisVolume 3: Aftermath The three volumes are linked by a common introduction and can be purchased individually or as a set.
Keywords: capitalism; emancipation; feminism; gender; welfare state

Karl Polanyi, Globalisation and the Potential of Law in Transnational Markets - Joerges, Christian; Falke, Josef (Hart, 2011)
The patterns and impact of globalization have become a common concern of all international jurists, sociologists, political scientists, and philosophers. Many have observed the erosion of the powers of nation states and the emergence of new transnational governance regimes, and seek to understand their internal dynamics, re-regulatory potential, and normative quality. Karl Polanyi's seminal book - The Great Transformation - is attracting new attention to such endeavors, mirroring a growing sensitivity to the social and economic risks of dis-embedding politics. Their re-construction by Polanyi - including his warning against a commodification of labor, land, and money - provide the trans-disciplinary reference point for the contributions to this book. Political economy, political theory, sociology, and political science inform this discussion of Polanyi's insights in the age of globalization. Further theoretical essays and case studies look at his 'false commodities': money, labor (and services), and land (and the environment). Jurists have hardly ever discussed Polanyi, and the law has not been taken very seriously among 'Polanyians.' It is nevertheless clear that economic stability and social protection are simply inconceivable without the visible hand of law. The legal discussion in this book's concluding chapters do not, and cannot, depart directly from such premises. The framework of their analyses is, instead, informed by current debates on the emergence of para-legal regimes, the fragmentation of international law, and the prospects of constitutional perspectives within which the rule of law and the notion of law-mediated legitimate governance are established. Polanyi's notion of the co-originality of dis-embedding moves and re-imbedding countermoves can, however, be usefully employed in the re-construction of the sociological background of the moves and tensions which jurists discern.
Keywords: conflict of laws; jurisprudence; law - commercial; political science - history and theory

Karl Polanyi And The Great Transformation - Örmeci, Ozan (Sosyal Bilimler Dergisi, 2011)
Özet: 20. yüzyılın önde gelen iktisatçılarından olan Karl Polanyi (1886-1964), Büyük Dönüşüm adlı eserinde ortaya koyduğu özgün tezler ile halen kapitalizme en ciddi eleştiriyi getirmiş kişilerden biri kabul edilmektedir. Polanyi'nin klasik ENG: Karl Polanyi is known as one of the most famous economists of the world who strongly criticized liberalism and the idea of self-regulating market. Polanyi’s masterpiece The Great Transformation is still accepted as one of the most powerful critiques of liberal economics and many writers from different political backgrounds refer to this book while criticizing the dominant liberal economic understanding. The Great Transformation is a very rich and complex book in which Polanyi analyzes the evolution of the free-market ideology and the counter movement against the damages of liberal economics. Although Polanyi called himself as a socialist, his ideas are very dense and it is not easy to label him as a defender of certain ideology.
Keywords: Great Transformation, The (Book); review

Towards a Neo-Polanyian Political Economy of Development - Sandbrook, Richard (Conference Papers -- International Studies Association, 2011)
The Global South has entered an era of ideological flux. The inadequacies of neoliberalism have spawned a widespread questioning of this dominant worldview. Intellectuals and political movements search for an alternative development ideology that explains what has gone wrong, provides a vision of a more desirable future and suggests a process for achieving this goal. Responding to these challenges, the World Bank and other purveyors of the dominant model have undertaken a gradual shift from an unpopular and inefficacious “Washington Consensus” to a more complex and politically progressive “Post-Washington Consensus”. This shift, though blunting the attack on neoliberalism, has moved the debate on legitimate development strategies to the left and towards more statist approaches. Socialism, the developmental state, social democracy, and emancipatory community-based development have moved back into development discourse. In an earlier era of ideological flux, Karl Polanyi probed the origins of the implosion of economic liberalism in the Great Depression and two world wars, as well as the alternatives that might, by re-embedding the economy in society, allow people to live freer and more secure lives. These reflections came together in The Great Transformation, his masterwork that appeared in 1944. Although Polanyi studied a different era (1830-1940) and focused on Europe, his ideas have inspired an outpouring of studies on contemporary problems and prospects in the neoliberal era (since 1980). The bulk of these studies pertain to industrial countries or global economic issues. However, the human, environmental and financial impact of market deregulation is arguably more devastating in the ‘developing’ countries than in the core. A question thus arises: do Polanyi’s reflections on progressive alternatives to liberalism clarify contemporary debates on progressive alternatives to neoliberalism in the Global South?
Keywords: Global South; World Bank; economic development; global south; ideology; political movements; social democracy; socialism

Simultaneous Transitions: Democratization, Neoliberalization, and Possibilities for Class Compromise in South Korea - Kim, Wonik (Review of Radical Political Economics, 2010)
The purpose of this paper is to bring class compromise back into the study of South Korean political economy and present it as a possible alternative to the overwhelmingly one-sided neoliberal trajectory in South Korea. The process and conditions under which positive class compromise is acquired are identified in terms of the Polanyi-Gramsci nexus. This perspective suggests that the restoration of state-led developmentalism would be unfeasible under a democratic regime, while the implementation of a purely neoliberal blueprint may lead to unproductive class conflict. Employing this theoretical framework, I examine possibilities for positive class compromise in the context of the simultaneous transitions—democratization and neoliberalization—in South Korea. JEL classification: B5, H7, O53, P5
Keywords: GRAMSCI, Antonio, 1891-1937; Gramsci; class compromise; democratization; developmental state; neoliberalism

Polanyi's Double Movement and Neoliberalization in Korea and Japan - Kim, Wonik (Social Movement Studies, 2010)
This paper reformulates and extends Polanyi's main insights in The Great Transformations (2001 [1944]) and attempts to theorize the societal countermovement against neoliberalism by illustrating the cases of Korea and Japan. Polanyi's main approach was to synthesize three critical domains: the state, market, and society, and his notion of double movement should be understood as such. Predicated on his double movement, I analytically decompose the mechanism of societal countermovement, emphasizing the importance of social organizations that aggregate people's insecurities and translate them into a political voice capable of acquiring social protection. Applying this analytical framework of the double movement to Korea and Japan reveals that the problem with the conventional understanding of the double movement is that it necessarily arrives at social compensation equilibrium. This paper implies that a highly contentious society, like Korea's, and a highly docile society, like Japan's, may both hinder social welfare provision.
Keywords: Japan; Korea; civil society; civil society organizations; double movement; neoliberalism; social movement studies

Labour as a (Fictitious) Commodity: Polanyi and the Capitalist ‘Market Economy’ - Paton, Joy (The Economic and Labour Relations Review, 2010)
In The Great Transformation, Karl Polanyi problematised the commodity status of labour. He described it as ‘fictitious' and asserted the human aspect of labour necessitates ‘protection’. In bringing Polanyi's mature works to bear on these claims, this article uses the ‘fictitious commodity’ concept to highlight the tension in neoclassical theory between concrete reality and its idealist construction of the economy. This contradiction directly challenges the veracity of the self-regulating market. The article develops two related themes. The first is Polanyi's critique of the neoclassical conception of ‘the economy’ as an ideal (market) construct which gave rise to the notion that labour could be regulated by the forces of supply and demand. The second is the lack of logic in the notion of a ‘self regulating’ market and Polanyi's appreciation of the concrete tendencies of capitalist economies to develop institutional arrangements that ensure the economy is always, and necessarily, more than ‘the market’.
Keywords: capitalist economy; fictitious commodities; fictitious commodity; institutionalisation; labour; laissez-faire; markets; political economy; regulation; self-regulation; social embeddedness

Uncertainty Markets and Carbon Markets: Variations on Polanyian Themes - Lohmann, Larry (New Political Economy, 2010)
Enormous new markets in uncertainty and in carbon have been created recently, ostensibly to enhance the cost-effectiveness of both finance and climate action. In both cases, however, creating the abstract commodity framework necessary to make sense of the notion of 'cost-effectiveness' has entailed losing touch with what was supposedly being costed, helping to engender systemic crisis. The new financial markets expanded credit and multiplied leverage by isolating, quantifying, slicing, dicing and circulating diverse types of uncertainty; the resulting unchecked pursuit of liquidity led to a catastrophic drying up of liquidity. The carbon markets, meanwhile, by identifying global warming solutions with reductions in an abstract pool of tradable pollution rights and linking them with 'offsets' manufactured through quantitative techniques, ended up blocking prospective historical pathways toward less fossil fuel dependence and thus exacerbated the climate problem. Unsurprisingly, both markets have provoked strong, if diverse and confused, movements of societal self-defence. This pattern of action and reaction constitutes a chapter in the political history of commodification as significant in some ways as that describing the movements to commodify land and labour analysed by Karl Polanyi.
Keywords: atmospheric carbon dioxide; cap and trade; carbon credits; carbon offsetting; carbon trading; climate policy; derivatives; emissions trading; financial crisis; greenhouse gas mitigation; offsets

Cultural political economy and critical policy studies - Jessop, Bob (Critical Policy Studies, 2010)
This article introduces cultural political economy as a distinctive approach in the social sciences, including policy studies. The version presented here combines critical semiotic analysis and critical political economy. It grounds its approach to both in the practical necessities of complexity reduction and the role of meaning-making and structuration in turning unstructured into structured complexity as a basis for ‘going on’ in the world. It explores both semiosis and structuration in terms of the evolutionary mechanisms of variation, selection, and retention and, in this context, also highlights the role of specific forms of agency and specific technologies. These general propositions are illustrated from ‘economic imaginaries’ (other types of imaginary could have been examined) and their relevance to economic policy. Brief comments on crisis-interpretation and crisis-management give this example some substance. The conclusion notes some implications for research in critical policy studies.
Keywords: complexity; crisis; crisis-management; cultural political economy; cultural turn; finance-led accumulation; green new deal; neoliberalism

Globalization, Crisis and Social Transformation: A View from the South - Munck, Ronaldo (Globalizations, 2010)
The dominant narrative around the unfolding capitalist crisis is firmly focused on the dominant economies, and in particular the US. This is understandable given that the proximate causes of the crisis lie in the imperial heartlands and crisis resolution measures taken there will have a global impact. But a 'view from the South' is needed to redress the balance and prevent the decimation of global majority likelihoods being presented as mere collateral damage. The first section below tackles the crisis from a global (globalization) perspective emphasizing its impact in the South and what that it might mean in terms of political prospects. I then go on to develop a hybrid Karl Polanyi/Antonio Gramsci theoretical lens on counter-movements based on their writings responding to the last systemic capitalist crisis in the 1930s. Finally, I turn to the ways in which the international labour movement and the subaltern or post-colonial worlds are contesting the terrain vacated by unregulated market capitalism. As Gramsci would say the old is dying but the new has not yet been born. La narrativa dominante alrededor de la crisis capitalista revelada, esta firmemente enfocada a las economias dominantes, y particularmente E.E.U.U. Esto es comprensible, dado que las proximas causas de la crisis yacen en la region central imperial y las medidas de resolucion de la crisis que se tomaron alli tendran un impacto global. Pero se necesita un 'punto de vista desde el sur' para compensar el equilibrio y prevenir la devastacion de las posibilidades de las mayorias globales presentadas como simple dano colateral. La primera seccion abajo trata la crisis desde una perspectiva global (globalizacion), enfatizando su impacto en el sur y lo que eso puede significar en terminos de prospectos politicos. Luego procedo con el desarrollo de una lente teorica hibrida de Karl Polanyi/Antonio Gramsci sobre movimientos opuestos en base a sus escritos que responden a la ultima crisis capitalista sistemica en la decada de 1930. Finalmente, vuelvo a las maneras en las cuales el movimiento laboral internacional y los mundos subalternos o postcoloniales estan disputando el terreno vacio por el mercado capitalista sin regulacion. Como Gramsci diria, lo viejo se esta muriendo, pero lo nuevo no esta aun por nacer. [image omitted]
Keywords: GRAMSCI, Antonio, 1891-1937; South; capitalism; countermovement; crisis; financial crises; financial crisis; globalization; hegemony; international markets; labour; post-colonial; social change; transformation

An Australian international political economy? The high road and the low road - Leaver, Richard (Australian Journal of International Affairs, 2010)
Drawing on Karl Polanyi's distinction between formal and substantive theory, this article argues that 'an Australian international political economy' could (and should) be erected on the historical study of Australia's substantive articulations with the global economy.
Keywords: Australia; economic policy; international economic relations; international relations; policy sciences

Work After Globalization: Building Occupational Citizenship - Standing, Guy (Edward Elgar Publishing, 2010)
Per Google Books: This is a scholarly and erudite work. . . There is a wealth of detail, all illustrated with plenty of fascinating examples. . . It is impossible to give the full flavour of this thoughtful and stimulating book in even a long review, but it deserves to be
Keywords: business & economics - labor; business & economics - labour; embeddedness; industrial citizenship; political science / labor & industrial relations; political science / labour & industrial relations; social science / sociology / general

Karl Polanyi: the limits of the market - Dale, Gareth (Key contemporary thinkers series, 2010)
Karl Polanyi: The Limits of the Market is the first comprehensive introduction to Polanyi's ideas and legacy. It assesses not only the texts for which he is famous – prepared during his spells in American academia – but also his journalistic articles written in his first exile in Vienna, and lectures and pamphlets from his second exile, in Britain. It provides a detailed critical analysis of The Great Transformation, but also surveys Polanyi’s seminal writings in economic anthropology, the economic history of ancientand archaic societies, and political and economic theory. Its primary source base includes interviews with Polanyi's daughter, Kari Polanyi-Levitt, as well as the entire compass of his own published and unpublished writings in English and German. This engaging and accessible introduction to Polanyi's thinkingwill appeal to students and scholars across the social sciences,providing a refreshing perspective on the roots of our currenteconomic crisis.
Keywords: economics; philosophy

The Global Financial Crisis: Other issues to watch » TripleCrisis - Grabel, Irene (2010)
Keywords: G-20; Polanyi moment; austerity; global financial crisis

Concluding reflections on globalization(s) and labour in China and India: a Polanyian perspective - Harriss, John (Globalization and labour in China and India: impacts and responses., 2010)
Keywords: China; India; economics; globalization; labor; labour

Polanyi in Brussels? Embeddedness and the Three Dimensions of European Economic Integration - Höpner, Martin; Schäfer, Armin (Max-Planck-Institut für Gesellschaftsforschung, 2010)
In a recent article, Caporaso and Tarrow have argued that the jurisprudence of the European Court of Justice (ECJ) is increasingly moving in a social policy direction that will ultimately put European politics on a “Polanyian” course. We take issue with their claim and distinguish three dimensions of European economic and social integration: market-correcting integration, market-enforcing integration, and the creation of a European area of nondiscrimination, the latter consisting of two subdimensions, namely nondiscrimination on the basis of characteristics such as gender, age, and ethnic origin, on the one hand, and nondiscriminatory transnational access to the social security systems of the member states, on the other. Increased heterogeneity among European varieties of capitalism perpetuates the different ranges and speeds of these integration dimensions. We conclude that the Polanyi-in-Brussels hypothesis is misleading. Politically enforced social integration has not made much progress in the last decades, while market-enforcing integration and European nondiscrimination policies have asymmetrically profited from “integration through law.” So far, the impact of European integration on political economy has been “Hayekian” rather than “Polanyian.” Jüngst haben Caporaso und Tarrow argumentiert, die Rechtsprechung des Europäischen Gerichtshofs (EuGH) weise zunehmend soziale Züge auf und führe dazu, dass die europäische Integration eine „Polanyische“ Richtung einnehme. Wir wenden uns gegen diese These und unterscheiden drei Dimensionen der europäischen Wirtschafts- und Sozialintegration: die marktkorrigierende Integration, die marktschaffende Integration und die Schaffung eines europäischen Antidiskriminierungsraums, wobei letztere aus zwei Subdimensionen besteht, nämlich der Nichtdiskriminierung aus Gründen wie denen des Alters, der ethnischen Zugehörigkeit und des Geschlechts einerseits, und der Durchsetzung eines diskriminierungsfreien transnationalen Zugangs zu den sozialen Sicherungssystemen der Mitgliedstaaten andererseits. Die gestiegene Heterogenität europäischer Spielarten des Kapitalismus perpetuiert die unterschiedlichen Reichweiten und Geschwindigkeiten der Integration in den drei Dimensionen. Wir kommen zu dem Ergebnis, dass die „Polanyi in Brüssel“-These unzutreffend ist. Während die politisch herbeigeführte, soziale Integration kaum Fortschritte macht, profitieren die marktschaffende Integration und die europäische Antidiskriminierungspolitik von der „Integration durch Recht“. Die europäische Integration trägt daher weit mehr „Hayeksche“ als „Polanyische“ Züge.
Keywords: Europe; Polanyi-in-Brussels hypothesis

Globalization(s) and Labour in China and India: Introductory Reflections - Harriss, John (Global Labour Journal, 2009)
I find it helpful to view the events of the past twenty years or so in a Polanyian frame, and specifically to enquire as to the working out of the ‘double movement’ as the attempt has been made, in both China and India, albeit partially, to shift towards the self-regulating market.
Keywords: China; India; double movement; globalization; labor; labour

Industrial Policy in the United States: A Neo-Polanyian Interpretation - Schrank, Andrew; Whitford, Josh (Politics & Society, 2009)
The conventional wisdom holds that U.S. political institutions are inhospitable to industrial policy. The authors call the conventional wisdom into question by making four claims: (1) the activities targeted by industrial policy are increasingly governed by decentralized production networks rather than markets or hierarchies, (2) "network failures" are therefore no less threatening to industrial dynamism than market or organizational failures, (3) the spatial and organizational decentralization of production have simultaneously increased the demand and broadened the support for American industrial policy, and (4) political decentralization is therefore likely to improve the functioning of industrial policies designed to combat network failures.
Keywords: United States; decentralization in government; economic activity; federalism; governance; industrial organization (economic theory); industrial policy; networks; production (economic theory)

Political Cycles, Political Institutions and Public Expenditure in India, 1980-2000 - Sáez, Lawrence; Sinha, Aseema (British Journal of Political Science, 2009)
In Western democracies it is held that parties and their positions affect how politicians choose to make public expenditure and investment. This article examines the public policy choices of politicians in India, a large well-established democracy with remarkable subnational variation. Public expenditure, from education and health to agriculture and irrigation, is analysed. Counterintuitive findings - that election timing and political factors play a strong role in the subnational states, and that party competition increases investment in education - are explained by highlighting the role economic and political uncertainty plays in politicians' choices. Building a 'Polanyi' argument enhanced by a supply-side mechanism highlights the importance of compensation and insurance and the imperatives of political stability for subnational politicians, who attempt to maximize re-election chances in an uncertain environment.
Keywords: India; budget - law and legislation; elections; government purchasing; government spending policy; policy sciences; public administration; public spending; representative government; tax and expenditure limitations

‘Habitation vs. Improvement’ and a Polanyian Perspective on Bank Bail-outs - Watson, Matthew (Politics, 2009)
The bank bail-outs enacted by the Brown government in the wake of the 2007 credit crunch have had a distinctive political character. Despite the government's pronouncements on the merits of swift and decisive interventions, I argue that this does not amount to a return to the interventionist regulatory form associated with post-war British welfare capitalism. The Polanyian distinction between ‘habitation’ and ‘improvement’ is used to show that the bail-outs were designed by contrast to defend the underlying deregulatory logic of the existing financial regime. The only real change of note was to uncover forcibly the often hidden influence of the state in the making and regulation of an ostensibly market-led neoliberalism and the creation instead of a much more overt state-led neoliberalism. Habitation strategies were incorporated into a structure of financial deregulation, making it more rather than less difficult to rejuvenate state capacities consistent with enhancing societal welfare. The bank bail-outs offered short-term salvation for distressed firms within the financial sector without providing the state with socialised control over the conduct of banking business in order to promote forms of social policy consistent with post-war British welfare capitalism.
Keywords: BROWN, Gordon, 1951-; Great Britain; Great Britain - politics & government - 2007-; bailouts (finance); banking industry; habitation

Challenging Neoliberalism in Latin America - Silva, Eduardo (Cambridge University Press, 2009)
At the turn of the twentieth century, a concatenation of diverse social movements arose unexpectedly in Latin America, culminating in massive anti-free market demonstrations. These events ushered in governments in Argentina, Bolivia, Ecuador, and Venezuela that advocated socialization and planning, challenging the consensus over neoliberal hegemony and the weakness of movements to oppose it. Eduardo Silva offers the first comprehensive comparative account of these extraordinary events, arguing that the shift was influenced by favorable political associational space, a reformist orientation to demands, economic crisis, and mechanisms that facilitated horizontal linkages among a wide variety of social movement organizations. His analysis applies Karl Polanyi's theory of the double movement of market society to these events, predicting the dawning of an era more supportive of government intervention in the economy and society.
Keywords: Latin America; double movement; market society; neoliberalism; political science / comparative politics; political science / world / general

Headlong into the Polanyian Dilemma: The Impact of Middle-Class Moral Panic on the British Government's Response to the Sub-prime Crisis - Watson, Matthew (The British Journal of Politics & International Relations, 2009)
This article focuses on the discursive construction in Britain of a middle-class moral panic occasioned by the distress caused to self-styled ‘responsible mortgage borrowers’ by falling house prices. In the context of the move towards asset-based welfare the sub-prime crisis manifested itself most obviously in the popular consciousness as a threat to housing market wealth. The Labour government used the political space opened up by the narrative of middle-class moral panic in order to protect banks' balance sheets from the consequences of their own failed investments in mortgage-backed securities. The ensuing arrangements immunised banks from the implications of market self-regulation in the first-phase response to the sub-prime crisis while simultaneously allowing them to continue to impose the experience of market self-regulation on their customers. An increasingly asymmetric approach to banking regulation has arisen analogous to that which Karl Polanyi associated with the contradictory co-existence of market and non-market forms.
Keywords: market self-regulation; moral panic; protective re-embedding of finance; sub-prime crisis

Drivers of development over the next 30 years: Some speculations - Harriss, John (Journal of International Development, 2009)
Class relationships are amongst the fundamental drivers of development, and it is argued here that over the next 30 years a major influence on the pattern and path of development will be exerted by the rise of the ‘new middle classes’ of Asia. At the same time, in the context of the blocked transition of the present, it seems unlikely that those who are marginalised and excluded will be able adequately to organise resistance, much less change structures of power, but poverty will be managed through welfare interventions like India's National Rural Employment Guarantee Scheme. Copyright © 2009 John Wiley & Sons, Ltd.
Keywords: Asia; India; double movement; eastern hemisphere; economic development; middle class; new middle class; social change; social classes; social structure

Institutionalization of Trust as Response to Globalization: The Case of Consumer Cooperatives in South Korea - Choi, Hyejin (Transition Studies Review, 2009)
This paper explores an explanation which elaborates how individuals effectively enact and sustain trust in the sphere of social economy and the capability. I discuss how value employed by actors and the strategies and power relation in the socio-economic value sphere and focus on the function of ‘trust’ as the key mechanism of the interaction. This paper examine South Korean consumer cooperative Hansalim as a case of social economy which successfully institutionalize their system in competitive economic market arena.
Keywords: disembeddedness; double movement; embeddedness; food trust; governance; public administration; risk socety; social economy

Karl Polanyi's Great Transformation and Development Politics - Deutschmann, Moritz (Grin Verlag, 2009)
English, abstract: Attempts to understand the transformation processes in the developing world have often led to a closer examination of Europe′s and America′s own history, as many theories of development suggest a specific interpretation of these histories: Modernization theorists, for example, see Europe′s and America′s history mainly as a straightforward progression towards welfare and democracy, eclipsing the aspects that do not fit into this picture, like the World Wars or the American Civil War. Therefore, although Karl Polanyi′s "The Great Transformation" treats mainly historical events in Europe, it can at the same time be an important contribution to our understanding of the economic and social transformations in the developing world. In this essay, I will first try to make clear, what assumptions underlie Polanyi′s argument and what he means by the notion of "market society." I will proceed in three steps: first, I will explore the different roles that the economy, according to Polanyi, plays in capitalist and pre-capitalist societies; I will look then at the historical processes that led to the rise of a "market society." Finally, I will discuss the political reactions to these processes which can be characterized, in Polanyi′s view, by a "double movement." As Polanyi is one of the most important critics of economic liberalism, it is helpful to compare his account of the "Great Transformation" to a second, even more influential anti-liberal perspective, Marxism. Apart from some similarities, the fundamental difference seems to be that Polanyi does not give a positive account of modernization. This leads to the question, how Polanyi′s theori
Keywords: Great Transformation, The (Book); development; double movement; market society; modernization

Globalization and Backlash: Polanyi's Revenge? - Burgoon, Brian (Review of International Political Economy, 2009)
This paper investigates political-economic backlash to economic globalization in industrialized polities. It analyzes data on the content of party platforms to develop measures of party support for, or opposition to, political-economic closure, anti-democratic nationalism, and xenophobia in all party platforms of 23 Organization for Economic Cooperation and Development countries for all national elections between 1960 and 2003. These allow broader judgments of trends in autarky and autarchy than focusing on electoral success of particular extreme-right parties. Based on these measures, the paper quantitatively analyzes how international trade and capital openness and flows, and immigration flows, all influence the embrace or rejection of political-economic backlash among parties. The main explanatory finding is that immigration and capital flows and openness tend to increase marginally such backlash when national welfare compensation is very modest, but to reduce it when national compensation is generous, cushioning citizens from globalization's economic risks. This finding provides evidence that the current wave of globalization only marginally resembles the dark politics ending its nineteenth-century predecessor, and that welfare protection may help make the difference between political-economic backlash and liberalism in contemporary globalization.
Keywords: elections; international business; international economic order; international factor movements; legislatures; lobbying; political processes; rent-seeking; voting

Karl Polanyi in Budapest: On his Political and Intellectual Formation - Dale, Gareth (European Journal of Sociology / Archives Européennes de Sociologie, 2009)
AbstractA major thinker and inspiring teacher, Karl Polanyi's contributions have long been influential in a variety of disciplines, notably economic sociology and economic history. Two of his innovations, substantivist economic anthropology and the “double movement thesis,” are recognized as seminal. All of the works for which he is known, however, were written late in life, when in exile, and very little is known of his Hungarian writings, virtually none of which had, until now, been translated. Despite his fame, the biographical literature on Polanyi remains modest: some studies provide invaluable insights, yet all are brief. This article attempts to make some headway in remedying these lacunae. It sketches the contours of that extraordinary historical-geographical conjuncture in which he was formed, and explores his intellectual and political engagements in the Galilei Circle and the Radical Bourgeois Party. It seeks in particular to elucidate the complex roles played by questions of nation, ethnicity and class in the life of the young Karl Polanyi.
Keywords: Hungary; Jewish assimilation; biography; liberal radicalism

Towards a Green Republicanism: Constitutionalism, Political Economy, and the Green State - Barry, John (The Good Society, 2009)
In lieu of an abstract, here is a brief excerpt of the content: Towards a Green Republicanism: Constitutionalism, Political Economy, and the Green State John Barry (bio) The republic is threatened—who will stand by the republic? Introduction The range of threats to modern society ranging from growing environmental stresses (water shortages, deforestation, soil erosion to climate change), food and energy insecurity, peak oil, rising poverty and inequalities within and between societies, increasing passivity of citizens within democracies and the inexorable rise of corporate power within and over the democratic state can be summed up as facets of 'unsustainability' or 'unsustainable development.' Just as it is commonplace to declare that the 21st century will be China's century, equally the politics of the 21st century are and will be the politics of sustain-ability. Taking it as given that the transition to sustainability will be the dominant challenge and opportunity facing all societies in the coming decades ahead, this article looks at two traditions of political thought—namely green political theory and civic republicanism—and seeks to conjoin them to outline a new political approach—'green republicanism'—which may respond and rise to this challenge. It needs to be pointed out from the outset that what is discussed below is 'green politics' and not 'environmentalism,' which is narrowly concerned with environmental preservation, species conservation or combating climate change. In broad terms green politics aims at 'sustainable development' which, inter alia, deals with securing basic human rights, lowering socio-economic inequalities, eradicating environmental injustices (within nation-states and globally as well as intergenerationally) and ensuring the demands of the human economy do not outstrip the regenerative capacities of the eco-systems upon which that economy depends. Sustainable development therefore is a radical proposal, indicating not simply the 'ecologising' or 'greening' of the current political and economic order. Such reformist proposals may be viewed as interim staging posts such as those represented by 'ecological modernisation' and discourses of 'natural capitalism,' but suggest the transformation to a different distinctly 'green' or 'sustainable' political order.1 While the metabolism between the human economy and its ecological systems is the most pressing and significant [End Page 3] dimension of sustainable development, questions of political economy and the economic order are always already present in any green analysis (whether explicit or not). In the same way that I take it as given that a sustainable society is one that is a post-carbon society (in terms of energy production and consumption), the green republican perspective offered here is also one which sees such a society as post-liberal, though not anti-liberal. Green politics can be viewed as 'post' not 'anti-liberal' in Robyn Eckersley's terms, and this can be seen to settle around the centrality of separating free market capitalism as the dominant organization of the economy, from liberalism (representative democratic governance, citizen freedoms, equality of citizens, etc.) in the creation of a sustainable society.2 In short, a green republicanism is one which asks the question 'How do we maintain and sustain liberty in a post-liberal political, post-capitalist economic and post-carbon, sustainable order?' In that context it is important to look at what are the political and institutional dynamics within, between and below the nation-state of this transformation away from current unsustainable development paths. If we are to live in a sustainable/green political order different than the current liberal democratic one based on the capitalist free market, what are the types of legal, constitutional and institutional innovations we might expect to see in a greening state or in a fully fledged 'green state?' Thus, while this article is critical of reformist ecological modernisation and strategies that focus on securing (often through technological innovation) the ecological conditions for the political economy of expansionist fossil-fuelled capitalism, it is also critical of radical green proposals (mostly anarchistic in character) which argue for the eradication or transcendence of the nation-state as a necessary condition of achieving sustainable development. Thus, the position outlined here is firmly within that school of green political thought which is concerned about the evolution and emergence of green states and pragmatic/strategic considerations about the 'greening' of existing liberal democratic states. Green Constitutionalism Given that constitutional provisions...
Keywords: embeddedness; green republicanism; political economy

Affect and the Rise of the Self-Regulating Market - Gammon, Earl (Millennium: Journal of International Studies, 2008)
This article outlines a post-rationalist approach to international political economy that factors in the role of affect in social causation. There are key historical junctures where social transformations cannot be neatly explained by instrumental logics, such as the profit motive or the pursuit of increasing productive efficiency. Affect, in the form of anxiety and aggression, overdetermines social behaviour in ways that belie conventional notions of rationality, premised on a clear ordering of needs or preferences by social actors. This analysis specifically reassesses the role of affect in the rise of market civilisation in Britain in the early part of the nineteenth century. It critiques Karl Polanyi's account, which privileges technology and pecuniary greed as the expedients of the institution of the self-regulating market. As an alternative, this article explains the rise of the self-regulating market as a retributive mechanism, whereby the market became conceived as a means of punishing and disciplining social behaviour in the early Victorian period. The market, I argue, was an aggressive response to anxiety that plagued Victorian society regarding social order, an anxiety precipitated by the waning belief in a natural moral economy guided by the hand of Providence.
Keywords: Great Britain; affect; critique; international political economy; post-rationalist IPE; self-regulating market; social causation

Karl Polanyi's The Great Transformation: perverse effects, protectionism and Gemeinschaft - Dale, Gareth (Economy and Society, 2008)
Drawing upon Karl Polanyi's journalistic writings and unpublished lectures from the 1920s and 1930s, this article reconstructs the lineaments of his research programme that was to assume its finished form in The Great Transformation. It identifies and corrects a common misinterpretation of the thesis of that book, and argues that Polanyi's basic theoretical framework is best conceived as Tönniesian: market society is Gesellschaft, while the ‘protective counter-movement’ of The Great Transformation is Gemeinschaft, understood dynamically. It examines the two central mechanisms by which, in Polanyi's understanding, Gesellschaft broke down in the mid-twentieth century: the ‘clash between democracy and capitalism’ and the ‘perverse effects’ whereby political intervention in markets impairs profitability and saps the vitality of the market system.
Keywords: Ferdinand Tönnies; TONNIES, Ferdinand, 1855-1936; The Great Depression; capitalism; democracy; perverse effects doctrine

Genealogies of Citizenship: Markets, Statelessness, and the Right to Have Rights - Somers, Margaret R. (Cambridge University Press, 2008)
REVIEW: Genealogies of Citizenship is a remarkable rethinking of human rights and social justice. As global governance is increasingly driven by market fundamentalism, growing numbers of citizens have become socially excluded and internally stateless. Against this movement to organize society exclusively by market principles, Margaret Somers argues that socially inclusive democratic rights must be counter-balanced by the powers of a social state, a robust public sphere and a relationally-sturdy civil society. Through epistemologies of history and naturalism, contested narratives of social capital, and Hurricane Katrina's racial apartheid, she warns that the growing authority of the market is distorting the non-contractualism of citizenship; rights, inclusion and moral worth are increasingly dependent on contractual market value. In this pathbreaking work, Somers advances an innovative view of rights as public goods rooted in an alliance of public power, political membership, and social practices of equal moral recognition - the right to have rights. "Building on Karl Polanyi, T. H. Marshall, and Hannah Arendt. Margaret Somers demonstrates that civil society rests on Ihe right to have rights. But this right has been swept away by three decades of market-dominated discourse and policies. Somers brilliantly shows how Hurricane Katrina's devastating impact on New Orleans was the culmination of this dynamic." -Fred Block
Keywords: ARENDT, Hannah; citizenship; civics and citizenship; civil rights; history / Europe / general; political science - history and theory; right to have rights

Michael and Karl Polanyi: Conflict and Convergence - Gulick, Walter (Political Science Reviewer, 2008)
The article focuses on social philosophers and brothers Michael and Karl Polanyi. Particular attention is given to Michael's political, economic, and social thoughts and how they compare to Karl's. The author wishes to illuminate Michael's social though through this comparative study. Topics include the brother's family background, Michael's early thought, and divergent paths.
Keywords: POLANYI, Michael, 1891-1976; biography; comparative studies; social theory

The Great Transformation: The Double Movement in China - Shaoguang, Wang (boundary 2, 2008)
KM: Both the title and the subtitle of this essay are adopted from Karl Polanyi, who published his famous book The Great Transformation: The Political and Economic Origins of Our Time in 1944. More than six decades have passed since its publication, but, as Joseph E. Stiglitz states in the preface of the recent new reprint, “the issues and perspectives Polanyi raises have not lost their salience . . . it often seems as if Polanyi is speaking directly to present-day issues.” ... China is experiencing “a transformation unprecedented in thousands of years” (qiannian weiyou zhi da bianju). More than one hundred years ago, the Qing official Li Hongzhang used these words to describe the era he was living in. Two decades later, the May Fourth generation had a similar take on their time, too. However, in terms of the economic foundation and the speed, depth, and scope of the social structure’s transformation, no other era can be compared to the last two decades or so.
Keywords: China; Great Transformation, The (Book); double movement

Going Global: The Transnational Politics of the Dalit Movement - Smith, Peter (Globalizations, 2008)
This article analyses the involvement of the Dalits (formerly 'untouchables') in the World Social Forum (WSF) processes. The focus will be on one networked organization in particular, the National Campaign for Dalit Human Rights (NCDHR) as a key organization which served as a catalyst for linking the Dalit struggle against neoliberal globalization and casteism with the social forum process and the global justice movement. The article argues that the Dalit struggle, domestically and internationally, can best be understood from a Polanyian perspective, as a countermovement for social protection against neoliberal globalization. It examines the dialectic of globalization within an Indian context first in terms of the impact of neoliberal globalization upon the Dalit community and then the NCDHR's decision to go global, to the WSF. In taking their cause beyond India, a central focus of Dalit activity remains rooted in making the Indian state serve as a means of social protection for the Dalit peoples. Este artículo analiza la participación de los Dalits (previamente llamados "intocables") en los procesos del Foro Social Mundial (WSF, por sus siglas en inglés). El enfoque se concentrará particularmente en una organización en red, la Campaña Nacional por los Derechos Humanos de los Dalits (NCDHR, por sus siglas en inglés) como una organización clave que sirvió como catalizadora por haber enlazado la lucha de los Dalits contra la globalización neoliberal y el casteísmo, con el proceso del foro social y el movimiento de justicia global. El artículo plantea que la lucha de los Dalits, tanto doméstica como internacionalmente, puede entenderse mejor desde una perspectiva polanyana, como un contramovimiento para la protección social en contra de la globalización neoliberal. El mismo examina la dialéctica de la globalización dentro del contexto indio, primero en términos del impacto de la globalización neoliberal sobre la comunidad de los Dalits y luego, en términos de la decisión de la Campaña Nacional por los Derechos Humanos de los Dalits (NCDHR) de tomar una dirección global, hacia el Foro Social Mundial. Al llevar su causa más allá de la India, el tema central sobre la actividad de los Dalits permanece arraigado obligando al estado indio a servir como un medio de protección social para los Dalits.
Keywords: Dalits; class politics; countermovement; globalization - social aspects; human rights; international relations

IPE and European Integration: Applying Karl Polanyi's 'the Great Transformation' - Copeland, Paul (2008)
European integration is usually studied within the realms of comparative politics. The multitude of empirical studies concerning the topic have been well suited to its numerous methodologies and analytical frameworks. Comparative politics however, usually ignores the question of why European integration has both progressively deepened and widened during the last thirty years. Therefore there is a distinct absence of how developments in the global political economy determine European integration. Such an approach fails to address the issues of power and constraint within the global economy. We would therefore expect the process to be examined within international political economy, yet there has been a relative neglect of European integration within IPE as it considers the process to be a mere regional response to global developments. This paper argues that European integration is a more complex process than IPE has considered and addresses its relative neglect by applying Polanyiâs 'the Great Transformation'. Firstly, this paper argues that existing comparative politics and IPE approaches to European integration have a number of shortcomings which limits their application. Secondly, to address these limitations this paper applies 'the Great Transformation' to European integration and argues there to be strong parallels between Polanyiâs theory and the process. Thirdly, the paper argues that European integration is much more than a simplistic regional response to globalisation. European integration has been a contradictory process oscillating between neoliberalism and the European Social model. This highlights not just the contradictions of European integration, but also what Polanyi termed the âmarket societyâ. ..PAT.-Unpublished Manuscript
Keywords: European integration; comparative government; globalization; international economic relations; international political economy; neoliberalism

Reciprocity, Exchange and Redistribution. An experimental investigation inspired by Karl Polanyi’s The Economy as Instituted Process - Danese, Giuseppe; Mittone, Luigi (MyScienceWork, 2008)
Inspired by Karl Polanyi’s writings on three allocation modes, namely reciprocity, exchange and redistribution, we first tested a reciprocity ring with ten players. The baseline treatment, with no possibility of socialisation, displayed very low levels of allocative efficiency. Consistently with the Polanyian approach to reciprocity, we found that inducing the notion of symmetry among the players increased efficiency levels significantly. We then simulated a market exchange, with significant allocative efficiency gains. We conclude that indirect-reciprocity rings among anonymous players can seldom function in the absence of definite institutional refinements, promoting forms of symmetry-acknowledgement.
Keywords: instituted economic process; reciprocity

Is Market Liberalization Pathological? Debating the Causes of Corruption in Chinese Banking - Eaton, Sarah (2008)
Neoclassical economists posit that the freeing of market forces will lead, ceteris paribus, to a reduction in levels of corruption. There are several mechanisms through which this hypothesized effect is channeled, the most important of which is competition pressure brought by the entry of foreign firms into the domestic market. The empirical leverage of this approach has been strongly challenged by events of recent years. In China and Russia, market liberalization has not had the expected effects: corruption has exploded alongside market opening. Why? The view among many economists is that the benefits of market opening were stymied by the political logic governing the process of reforms (e.g. cronyism in privatization, trade policy protection of inefficient domestic firms et cetera). The Polanyi-inspired counter-claim is that reform-era corruption is itself an effect of the disembedding of the political economy. My research on corruption in the Chinese banking industry lends empirical insight to the debate. Because the Chinese market is variegated, with some firms being much more exposed to competition than others, there is the opportunity to test these explanatory variables against corruption levels in different segments of the market. On the basis of original fieldwork conducted in China, this paper suggests that the neoclassical economists faith in market opening as an anticorruption mechanism is unwarranted. ..PAT.-Unpublished Manuscript
Keywords: China; banking industry; corruption; disembeddedness; ethics; market liberalization; white collar crimes

Labour and the Transformation of East Asian Capitalism: A Regional View - Gray, Kevin (Conference Papers -- International Studies Association, 2008)
Two of the most salient aspects of the recent shift towards financialisation and neoliberal restructuring since the 1970s have been the restructuring of global production towards China, and the growing threat to workersâ livelihoods posed by increased capital mobility. Both of these trends can be seen as capitalâs response to the crisis of profitability that has arisen from the unsustainable global social accord between workers and capital that was inherent in post-War US hegemony. Transnational manufacturing capital sought ever cheaper sites of cheaper and non-unionised labour, whilst there was at the same time a tendency for capital to withdraw from productive investment altogether and enter the financial market. This paper will seek to explore the implications of these developments for the working classes of East Asia as a region, and will take examine the present transformations from the perspective of Polanyi's depiction of social responses to earlier periods of financialisation. The emergence of China as the 'workshop of the world' has had profound effects on working classes in the rest of East Asia, and have changed the parameters within which political challenges can be mobilized. Similarly, the viability of the recent restructuring of the East Asian regional political economy is highly contingent upon how working class movements develop in China, and whether China can continue to act as a "spatial fix". Through an examination of the empirical evidence on what kind of strategies are being adopted by labour movements within the East Asian countries, the paper will attempt to adopt an explicitly regional view of the transformations of regional capitalism which overcomes the limitations of national-level analyses. ..PAT.-Unpublished Manuscript
Keywords: East Asia; capitalism; economic conditions in East Asia; economic structure; financialization; international economic relations; international trade

The revenge of ideas: Karl Polanyi and Susan Strange - Halliday, Fred (openDemocracy, 2008)
Keywords: STRANGE, Susan

The Space of Rights: On Benjamin, Gramsci, and Polanyi - Holub, Renate (Conference Papers -- International Studies Association, 2008)
For intellectual generations born at the end of the 19th century in Europe, the discourses on rights were to a large measure determined by proponents and detractors of various versions of Marxism. Hence the debates on justice and rights predominantly operated with the conceptual and analytical instruments of European political economy. These debates also were premised on assumptions about the status of the political economy of Europe and North America in the distribution of global space. But the intellectual generations born at the end of the 19th century, and particularly those with interests in the Marxist project -- as Benjamin, Gramsci, and Polanyi were-- were also witnesses to the facts of the Soviet Revolution and its evolution into the Stalinist state. In this paper I will first of all examine the ways in which Walter Benjamin, Antonio Gramsci, and Karl Polanyi elaborated and expanded the concept of transatlantic space inscribed into the Marxist project. I will then investigate to which extent their familiarity with the rights practices of Stalinism impacted their elaboration of new forms of the space of rights: Benjaminâs concept of the historical space of âmessianismâ that transcends the historical limits of the space of rights of historical materialism; Gramsciâs concept of cultural space as a struggle for rights that expands Marxâs terrain of political economy, and Polanyiâs concept of anthropological space that expands the conceptual space of economic analysis of classical Marxism. The purpose of the paper is to gain a measure of understanding of the links that obtain between conceptual apparatuses of leading intellectuals and global transformations in the first half of the twentieth century, particularly since these intellectuals developed their ideas relatively independently from the structures of organized knowledge production of universities and academies. ..PAT.-Unpublished Manuscript
Keywords: BENJAMIN, Walter, 1892-1940; GRAMSCI, Antonio, 1891-1937; communism; human rights; political science

America transformed: globalization, inequality, and power - Hytrek, Gary J.; Zentgraf, Kristine M. (Oxford University Press, Incorporated, 2008)
Globalization--the interconnection of the world culturally, socially, politically, and economically--has generated intense theoretical and practical concerns. Is globalization inevitable? What are the effects of globalization on social structures and individual perceptions? What is the effect of globalization on societal level inequality? America Transformed: Globalization, Inequality, and Power examines these questions by analyzing the links among global processes and shifting patterns of stratification, inequality, and social mobility in the United States. While many texts separate discussions of macro- and micro-level processes when examining globalization, this book skillfully integrates general macro-level processes with specific reference to the micro-level effects of globalization in the U.S. Exploring the critical dimensions of inequality--class, gender, and immigration--America Transformed situates the U.S. experience within the broader global context, and fleshes out the mechanism through which global processes affect social stratification. By examining the social construction of globalization, the authors identify the key policy challenges of globalization, and some of the innovative community-based responses to social inequality.America Transformed provides powerful insights into the contested dialectical relationship between global and local forces: how globalization shapes stratification and inequality in the U.S., and how local communities attempt to mediate those changes.
Keywords: globalization; social classes; social science / sociology / general

Movements of the World Unite! Assessing Prospects for Social Movement Unionism in Canada - MacArthur, Julie (Conference Papers -- International Studies Association, 2008)
Within the field of critical political economy exists a literature urging a re-conceptualization of democracy (Munck 2002, Cox 1997, Webster and Adler 1998). Liberal, particularly neo-liberal, political systems are critiqued for their binary separation of economics and politics leading to substantive disenfranchisement and elitest governance. Robert Cox (1997) has called this âlimited democracyâ and argues that consumer choice and infrequent elections cannot be equated with democratic citizenship. One theorized response to this problem builds on the work of Karl Polanyi (1944) and his concepts of âembeddednessâ and the âdouble movementâ. Democracy can be deepened and strengthened by asserting social control over the economy and society at multiple levels and across issue areas. This is accomplished by a movement of social forces forcing a re-embedding in response to periods of increasing economic and elite consolidation. A problem in this literature has consistently been the agent or agents of change.This paper critically explores the argument that Social Movement Unionism (SMU), the organizational and theoretical blend of trade unionism and social movements, can and may serve as the agent of a Polanyian double movement in Canada. While theorists of SMU argue that labour necessarily needs to branch out laterally as a response to neo-liberal policies, I explore the tensions between âoldâ labour and contemporary social movements in Canada, such as the environmental movement. I ask: to what extent is organized labour taking on issues beyond their narrow collective-bargaining interests? Is there significant personnel overlap between labour and social movement organizations such as environmental, womenâs or anti-war groups? In answering these questions I intend to draw out the tensions between various actors these theories look to for change and assess their relevance in the Canadian context. By bringing together literature on transnational social movements, labour studies, political economy and international relations this paper takes an interdisciplinary approach to understanding these challenges. ..PAT.-Unpublished Manuscript
Keywords: Canada; democracy; economics; elite (social sciences); political science

KARL POLANYI ABOUT INSTITUTED PROCESS OF ECONOMIC DEMOCRATIZATION AND SOCIAL LEARNING - Mendell, Marguerite (PEKEA Newsletter N° 14, April – June 2008 / ResearchGate, 2008)
This text will not focus on The Great Transformation but will deal with previous and following writings from Karl Polanyi where his emphasis is on the constitutive elements that define us as social beings and as agents of social change.
Keywords: Great Transformation, The (Book); economic democratization; education; instituted economic process; social learning

Double Movement in China - Wang, Shaoguang (Economic and Political Weekly, 2008)
This paper traces China's move towards a market economy in the mid-1980s, the near triumph of market forces in the 1990s, and the countermovement this engendered as inequalities between the rich and poor increased and social security networks collapsed. It focuses on the country's regional and healthcare policies to illustrate how it has dealt with issues of inequality and insecurity over time. The prevailing view now is that the market is necessary but it must be embedded in society. And the state must play an active role in the market economy to prevent a disembedded and self-regulating market economy from dominating society.
Keywords: China; double movement; market economy

Charismatic Economies: Pentecostalism, Economic Restructuring, and Social Reproduction - Barker, Isabelle V. (New Political Science, 2007)
Pentecostalism is one of the world's fastest growing religions, expanding most quickly in Latin America, sub-Saharan Africa, and parts of Asia. To make sense of this expansion in so many developing regions, I suggest that Pentecostalism fosters norms and behaviors that harmonize with neoliberal economic restructuring. I frame this theoretically with Polanyi's notion of double movement. In our current era of weakened state governance vis-à-vis neoliberal trade and fiscal policy, non-state sites of reaction have emerged. Pentecostalism is one such site, and, in contrast with Polanyi's example, I suggest that Pentecostalism has embedded the self-regulated aspects of neoliberal capitalism. I make this argument by using the feminist political economy theorization of social reproduction to interpret a number of empirical studies of Pentecostalism. Pentecostalism addresses dilemmas of social reproduction engendered by neoliberalism, and so may be said to embed this form of economic organization in human social life in a way that reinforces neoliberal capitalism.
Keywords: Pentecostalism; capitalism; double movement; economic systems; economics; neoliberalism; social interaction; social reproduction; social structure; socialization

Poverty, Security and the Janus-Faced State - Eadie, Pauline (The British Journal of Politics & International Relations, 2007)
In this article Polanyi's double move and Wæver's securitisation argument inform an analysis of poverty as a security issue. The inclusion of poverty on the security agenda confirms and complicates, rather than marginalises, the state as a central referent of security. It is argued that analytically and pragmatically qualitative and socially contextualised analysis of poverty offers deeper understanding than quantitative approaches. It is also argued that the rhetoric of inclusion currently espoused by the likes of the World Bank seeks to secure institutional hegemony rather than state or human security. Neo-liberal solutions to poverty premised on growth, as opposed to redistribution, mean that the states and peoples poorly equipped to compete in the capitalist game will remain impoverished. Markets and neo-liberal institutions serve to splinter, rather than coalesce, state and society.
Keywords: Copenhagen school; double movement; poverty; security

The political economy reader: markets as institutions - Barma, Naazneen; Barma, Naazneen H.; Vogel, Steven Kent (Routledge, 2007)
This reader combines in a single volume the key writings of classical and contemporary thinkers on political economy. The articles provide both a theoretical approach to understanding capitalism and a survey of the varieties of capitalism around the world today, examining the interaction between politics and markets both in theory and practice. Drawing on history, economics, political science and sociology, it emphasizes the ways in which markets are embedded in and influenced by political and social institutions. Steven K. Vogel and Nazneen Haider Barma provide an informative overview of a number of the most significant controversies and contemporary debates in political economy through the selections of contending perspectives on a variety of issues, including: How can rich countries make their economies more competitive? How can poor countries achieve economic development? How can post-communist countries make a successful transition to markets? Will theinformation technology revolution render the national varieties of capitalism obsolete? Does globalization imply that the national varieties of capitalism will converge to one global capitalism? A Political Economy Reader will be an essential resource for students of political economy and economic sociology.
Keywords: business & economics; capitalism; economics; international economic relations; political economy; political science; sociology

The battle of the ancient economy - Hindess, Barry (Economy & Society, 2007)
Ancient Athens and Modern Ideology addresses the battle between primitivism and modernism over the ancient economy, focusing especially on the contributions of three major figures, Max Weber, Karl Polanyi and Moses Finley. Finally, a short Epilogue returns to the examination of Marx's puzzle and his manifestly unsuccessful attempt to resolve it. Mohammad Nafissi uses this discussion to put this dispute out of its misery by advancing his own resolution of the primitivist-modernist dispute. Unfortunately, the limitations he seeks to avoid are mostly those which the supporters of one or the other side have identified in the claims of their opponents. As a result, his attempted resolution fails to disrupt their shared assumptions regarding the special place of the ancient Greeks in human development.
Keywords: Athens (Greece); FINLEY, M. I. (Moses Israel), 1912-1986; Greeks; WEBER, Max, 1864-1920; book review; history of economics; ideology; primitivism; socioeconomics

Conflict of Laws as Constitutional Form: Reflections on International Trade Law and the Biotech Panel Report - Joerges, Christian (Social Science Research Network, 2007)
Hardly anywhere is the trend towards a perfection of transnational governance arrangements and their “legalization” more visible than in international trade. Governance arrangements established through and alongside WTO law are both practically important and theoretically challenging. They do not just organise international trade relations. They also affect national and regional (European) regulatory policies partly directly, partly more indirectly. How can we explain and how should we evaluate their emergence? The WTO system of 1994, which replaced the GATT of 1947, responded to the ever increasing importance of non-tariff barriers to trade. These barriers reflect regulatory concerns especially in the fields of health and safety, consumer and environmental protection. There importance for WTO member is such that they cannot simply be abandoned for the sake of free trade. This is why the responses the new international trade system institutionalised by special agreements concerning on-tariff barriers to free trade such as the Agreement on the Application of Sanitary and Phytosanitary Measures (SPS) and the Agreement on Technical Barriers to Trade (TBT) reflect a politicisation of international trade. Can we conclude that international markets have been re-regulated and that international trade law ensures their “social embeddedness”? The paper seeks yardsticks for an answer to these questions in the debates on transnational constitutionalism. It submits that constutionalisation can and should be based on a conflict-of approach. For its elaboration of this suggestion, the paper first contrasts the jurdification of transnational governance at the European and the international level. It then discusses the WTO panel report on the Biotech dispute. It concludes that the legalisation and judicialisation in that case have remained “thin.” What can be observed is a political rather than a social and legal embeddedness of markets.
Keywords: FOUCAULT, Michel, 1926-1984; Polanyi and Foucault; World Trade Organization (WTO); constitutionalisation; economic law; embeddedness; european governance; international trade; legal embeddedness; legalization; legitimacy; multilevel governance; national autonomy; risk regulation; social embeddedness; transnational governance

Neoliberalism, embedded neoliberalism and neocorporatism: Towards transnational capitalism in Central-Eastern Europe - Bohle, Dorothee; Greskovits, Béla (West European Politics, 2007)
This article analyses the key features and origins of three variants of transnational capitalism emerging in Central-Eastern Europe: a neoliberal type in the Baltic states, an embedded neoliberal type in the Visegrád states, and a neocorporatist type in Slovenia. These regimes are characterised by their institutions and performances in marketisation, industrial transformation, social inclusion, and macroeconomic stability. Explanations for regime diversity are developed at two levels. First, it is argued that the legacies of the past, and their perceptions as either threats or assets to these countries' future, have had deep impact on regime types. Legacies and initial choices were no less crucial for the degree of democratic inclusion, and the different patterns of protest and patience on the paths towards the new regimes. Second, the article demonstrates the importance of transnational influences in industrial transformation and social inclusion.
Keywords: Central-Eastern Europe; embedded neoliberalism; neoliberalism; transnational capitalism

The Transnational Politics of Corporate Governance Regulation - Overbeek, Henk; Apeldoorn, Bastiaan van; Nölke, Andreas (Routledge, 2007)
This ambitious volume explores the politics of recent changes in corporate governance regulation and the transnational forces driving the process. Corporate governance has in the 1990s become a catchphrase of the global business community. The Enron collapse and other recent corporate scandals, as well as growing worries in Europe about the rise of Anglo-Saxon finance, have made issues of corporate governance the subject of political controversies and of public debate. The contributors argue that the regulation of corporate governance is an inherently political affair. Given the context of the deepening globalization of the corporate world, it is also increasingly a transnational phenomenon. In terms of the content of regulation the book shows an increasing reliance on the application of market mechanisms and a tendency for corporations themselves to become commodities. The emerging new mode of regulation is characterized by increasing informalization and by forms of private regulation. These changes in content and mode are driven by transnational actors, first of all the owners of internationally mobile financial capital and their functionaries such as coordination service firms, as well as by key public international agencies such as the European Commission. The Transnational Politics of Corporate Governance Regulation will be of interest to students and researchers of international political economy, politics, economics and corporate governance.
Keywords: NGOs; NGOs (non-governmental organizations); business & economics; economic policy; international political economy; political science; public policy

Globalization, Inequality, and "Double Movement" in East Asia - Kim, Wonik (Conference Papers -- New England Political Science Association, 2007)
The purpose of this paper is to analyze the effects of rising income inequality on the welfare state in East Asia. Specifically, I explore and test two causal links: 1) the effects of economic globalization on income distribution, and 2) the increase in income inequality on the prospect of socio-welfare policies. Building on Polanyi's politico-economic concept of "double movement," I hypothesize that rapid neoliberalization and financial globalization in East Asia since the early 1990s (after the Asian Financial Crisis) has de-constructed the traditional state apparatuses that supported a well-known state-led accumulation strategy. This shift in political arrangements and national growth strategy, in turn, has entailed rising income inequality in a society, calling for restructuring the traditional East Asian welfare state. The success and failure of the creation of a new welfare state for new social risks depends on the level of contentious politics and country specific traits. With this general theoretical framework, I conduct a comparative method of five East Asian countries - China, Japan, South Korea, and Taiwan - for the period from the 1990s to the present, and explain the similarities and differences among them. ..PAT.-Unpublished Manuscript
Keywords: East Asia; equality; globalization; income distribution; international competition; neoliberalism

Rethinking the Categories of Feminist Theory: Diverse Feminist Responses to the Market Economy - MacLean, Lee (Conference Papers -- New England Political Science Association, 2007)
Feminist theory is often articulated as a series of categories of thought: liberal feminism, socialist feminism, Marxist feminism, psychoanalytic feminism, etc. These categories have aided the recent development of feminist thought, but their prevalence sometimes limits discussion to predicable perimeters. My argument begins from the observation that feminists often have very different responses to the rise of the market economy as a separate institution largely free of control by political and kinship-based authorities. In particular, there is a difference of opinion about the liberating possibilities of participating in a largely self-regulating market economy. I think an investigation of this disagreement could provide a new way of conceptualizing the main lines of feminist argument. For example, feminists who emphasize that the market economy provides an opportunity for women to free themselves from gender restrictions expressed in family and kinship traditions might be called libertarian-type feminists. Other feminists, those who (from varying perspectives) are skeptical that participation in the free market results in freedom for women, might be termed free-market skeptics. Of course, one wants to avoid creating new rigid labels, but thinking about this conceptualization can help to destabilize old categories and to recast often divisive debates (for example, over issues such as prostitution, pornography and housework).The argument is inspired by thinking through descriptions of the historically changing relations between market, family and politics found in two works: Karl Polanyi's The Great Transformation and Linda Nicholson's "Feminism and Marx: integrating Kinship with the Economic." ..PAT.-Unpublished Manuscript
Keywords: capitalism; families; feminism; feminists; kinship; women

Reforming Social Justice in Neoliberal Times - Brodie, Janine M (Studies in Social Justice, Vol 1, Iss 2, Pp 93-107 (2007), 2007)
This article unfolds in three stages. First, it locates the emergence of modern conceptions of social justice in industrializing Europe, and especially in the discovery of the “social,” which provided a particular idiom for the liberal democratic politics for most of the twentieth century. Second, the article links this particular conception of the social to the political rationalities of the postwar welfare state and the identity of the social citizen. Finally, the article discusses the myriad ways in which this legacy of the social and social justice has been disrupted, although not yet fully displaced, by the economic orthodoxies and individualization that inform the contemporary neoliberal governing project in Canada. The result, the article concludes, has been the institutionalization of insecurity, which demands the renewal of a social way of seeing and a politics of social justice on local and global scales.
Keywords: criminology; neoliberalism; political economy; social and public welfare; social governance; social justice; social pathology; social policy; social sciences; sociology

Reconfiguring the Terrain of Cultural Governance in Mexico: The Role of the Mexican Film Community in the Era of Neoliberal Globalization - Busmann, Nadine (2007)
Reconfiguring the Terrain of Cultural Governance in Mexico: The Role of the Mexican Film Community in the Era of Neoliberal Globalization Embracing the dominant neoliberal project, many Mexican elites have prioritized economic growth and market logics over broader social goals. The unleashing of market forces globally,and the adoption of neoliberal policies nationally have had a significant impact on local communities and national culture in Mexico. Focusing on Mexican cultural production, this paper explores the shifting terrain of political struggle in the Mexican film industry. One of the central concerns of this paper is what processes and on what authority the imagined political community in Mexico is constructed, reconstructed, and reproduced in the current era of neoliberal globalization. Historically, political contestation among political, cultural and business elites has been central to the perpetuation of the national cultural project, in this paper, it is argued that the changing political landscape in Mexico has created new conditions for contestation providing sites for previously marginalized forces to challenge the hegemony of neoliberalism.Conceptualising neoliberal globalization and its application by Mexican elites in Polanyian terms?as a double movement?the paper examines the consolidation of the Mexican film coalition as a counter-movement, driven by cultural elites, which emerged to contest the hegemony of market driven politics. In this regard the paper analyzes the ideological and material foundations of this movement. Further, it examines the coalition´s efforts to create a social base from which to reshape the state´s politico-cultural agenda to ensure the survival of an indigenous film industry, thus providing (sub)national identities with an image and voice in the face of globalizing forces. It suggests that organic intellectuals built collective political agency upon the conviction that neoliberal globalization is to be resisted insofar as it subjects the nation to transnational?and hence alien?cultural, political and economic forces. Lastly, it challenges the assumption that in challenging the hegemony of neoliberalism the film community is anti-capitalist. As the evidence will reveal the motivating factors and ideological foundations driving the efforts of the film community are much more complex. ..PAT.-Unpublished Manuscript
Keywords: Mexico; cultural production; elite (social sciences); globalization; international studies; neoliberalism; social goals

Searching for the Theory of Practice behind the WTO's Commodification Mandate - Göpel, Maja (2007)
When trying to understand the origins of the collapse of nineteenth-century civilization, Karl Polanyi identified a Great Transformation into a "starkly utopian" Self-Regulating Market (SRM). This shift entailed 2 elements: a wide-ranging re-regulation of organization and control of production processes, and the development of economic liberalism as a body of thought that provided justification of a new set of public policies that facilitated a transformation of land (nature), labor (people), and capital (money) into "fictitious commodities." Even though these factors have not originally been produced for sale, they are now organized by purchase-logics and their value determined by market signals. Philosophy of praxis approaches point out that this process of transformation is never complete. Neither the ?discovery? of new commodities, nor the expansion of market logics are natural, but the outcome of socio-political struggles. New agreements of the World Trade Organization for example render ever more elements of social life and nature as ?trade related? and under its auspices the next great commodification wave unfolds. This paper traces which type of knowledge publicly justifies the resulting floods these policies release before comparing it with concrete negotiated outcomes and their impacts. The final discussion will circle the question to which extent ?objective? science influences policy-making - or if subjective selection of sciences supports policy-selling. ..PAT.-Unpublished Manuscript
Keywords: World Trade Organization (WTO); commodification; ideal types; institutionalism; international trade; manufacturing processes; methodology; policy sciences; trade regulation

The Intellectual Commons vs Intellectual Property: Marxian and Polanyian Perspectives on Intellectual Capital, including Remarks on Primitive Accumulation - Jessop, Bob (2007)
This paper explores the increasing significance of intellectual property rights for the appropriation of surplus value in capitalism. Building on Marx's analysis of the value form and extending it to the commodification of knowledge, it develops a Marxian critique of informational capitalism based on the basic categories of value theory; inter alia, this looks at the commodification of knowledge from the viewpoint of commodity fetishism, the enclosure of traditional knowledge, the formal subsumption of intellectual labour, the real subsumption of intellectual labour, and the role of intellectual property rights as a contradictory means to support the average rate of profit for firms specializing in immaterial production (whilst enabling them to appropriate monopoly profits). The second part of the paper inquires whether these arguments lend support to a Polanyian interpretation of knowledge as a fictitious commodity. On the basis of the arguments already deployed, plus further arguments, it is suggested that knowledge can function as a non-commodity, a quasi-commodity, a fictitious commodity, a real commodity, and as fictive capital. This has interesting implications for the concepts of primitive accumulation and accumulation through dispossession. ..PAT.-Unpublished Manuscript
Keywords: Marxist philosophy; capitalism; commodification; intellectual property; political doctrines

The Slight Transformation: Contesting the Legacy of Karl Polanyi - Lacher, Hannes (Reading Karl Polanyi for the Twenty-First Century, 2007)
The postwar reconstruction of domestic and international orders ushered in a new political economy of capitalism. It entailed a far-reaching reorganization of social relations and economic institutions and accorded to the state an important role in the management of the economy. Many of the institutions of classical liberalism were displaced by interventionist mechanisms. The welfare state consolidated and extended multifarious forms of protection accorded to labor. A new level of labor-market regulation and public provisioning transformed the conditions under which people worked and lived, leading to higher incomes for large groups of society, and creating a higher degree of security for them both in the workplace and beyond. International institutions were created to facilitate the regulatory functions that these welfare states had assumed, supported by a conducive exchange-rate regime and restrictions on capital mobility.
Keywords: capital mobility; market society; market system; postwar period; postwar reconstruction; welfare state

Linking Political Economic Projects and Pension Systems in Europe: A Comparison of the Role of Occupational Pension Funds as Investment Actors in Three European Countries - Roumpakis, Antonios (Conference Papers -- International Studies Association, 2007)
The paper explores the relation of different political economic projects and the development of pensions as a social right in three countries: Sweden, Germany and United Kingdom. It comprises three parts. The first part provides the conceptual framework, which combines a Polanyian perspective for the social embeddedness of markets with a three dimensional power theoretical approach in order to analyse modes of governance as practices of socio-economic regulation. The second part identifies the link between the macro-level of analysis i.e. different political economy logics and modes of governance and the meso-level of analysis i.e. the institutional paths that these countries have followed in developing their pensions systems and what used to be and currently is the role of occupational pension funds in them. This type of funds offers a prime example of how institutions that originally developed within a logic of social rights have now become actors in the economy. The decision-making of this new actor is however depended on the power relations between labour and capital in each country. The third part of the paper continues to show how the institutional paths have departed from their national spatio-temporal fix and have been re-embedded in the market-economy rationale of the neo-liberal project. The paper identifies a trend towards the ?equitisation? of pension funds as part of a broader process of marketisation of pensions as social right. The significance of the investment decision for pension occupational funds becomes crucial since funds are becoming major actors in the economic field. Their investment decision depends much on power relations between labour and capital ranging for example from social development (public houses, creation of jobs in the national environment) to the creation of profits through domestic and foreign financial markets. The paper concludes that pension occupational funds are re-embedded in a framework of choices, dominated increasingly more from the market economy rationale and the neo-liberal political project. ..PAT.-Unpublished Manuscript
Keywords: Germany; Great Britain; Sweden; capital; decision making; pensions; political economic analysis

Globalization and Contestation: The New Great Counter-Movement - Munck, Head of Civic Engagement Dublin City University and Visiting Professor of Development Studies University of Liverpool and St Mary's University Nova Scotia Ronaldo; Munck, Ronaldo (Routledge, 2006)
Globalization is undoubtedly the great overarching paradigm of our era. However, there is still little agreement on what globalization actually ‘is’ and some do not accept that it ‘is’ anything at all. This new book addresses the contestation of globalization by the anti- or counter-globalization movement. To contest means to challenge, to call into question, to doubt, to oppose and to litigate. This study shows how globalization is ‘contestable’ in many different ways and how the counter-movements we have seen emerging over the last decade also ‘bear witness’ on behalf of an alternative human future. Ronaldo Munck presents an overarching framework that allows us to understand how globalization and its contestation are inextricably bound up with one another. This volume insightfully explores a number of case studies, including: the battle of Seattle in 1999 the World Social Forum peasant internationalism environmental movements and reactionary movements including: the US Patriot's movement, Islamic fundamentalist movements and other nationalist movements. Globalization and Contestation will be of great interest to all students and scholars of international relations, politics and of globalization and global governance in particular.
Keywords: countermovement; globalization; political economy; political science

Understanding Global Capitalism: Passive Revolution and Double Movement in the Era of Globalization - Xing, Li; Hersh, Jacques (American Review of Political Economy, 2006)
This paper attempts to provide a framework for understanding the way globalization has reshaped the terrain and parameters of social, economic and political relations both at the national and global levels, and exerted pressure on the resiliency capacities of capitalism. It proposes to examine the ways social relations of domination and subordination are produced, reproduced and maintained while continuously undergoing transformations. Through conceptualizing the evolution of the capitalist world order in a historical perspective and by exploring the changes of relations brought about by the intensification of globalization since the 1990s, the objective is to generate a perspective for understanding such a process based on the application of Gramscian and Polanyian theoretical and analytical categories. The conclusion aims to convey that the process is contingent on both structures and agencies and it also produces the opposite result: i.e. reducing the legitimacy of capitalism's hegemony and especially limiting its resilient capacities.
Keywords: capitalism; capitalist systems: political economy; colonialism; double movement; globalization; imperialism; international economic order; postcolonialism

Theorising globalisation's social impact: proposing the concept of vulnerability - Kirby, Peadar (Review of International Political Economy, 2006)
The concept of vulnerability was introduced into IR theorising by Keohane and Nye who saw it as one of the consequences of complex interdependence and it is being increasingly employed by IGOs to capture the impact of globalisation on society. However, the concept has been little used in the academic literature on globalisation, except in a descriptive sense. This article argues that the concept has the potential to fill a gap in the toolkit of the ‘new’ IPE, offering an analytical category that can capture the distinctive impact of globalisation on society more adequately than other concepts that are more widely used. The article begins by surveying how the concept has been used by Keohane and Nye and by IGOs. It then offers a definition and illustrates the application of the concept by describing some of the principal ways in which globalisation is increasing risk and eroding coping mechanisms. It goes on to argue that the concept of vulnerability captures in a fuller way the distinctive social impact of globalisation than do other concepts widely used in the IPE literature, examining in turn the limitations of the concepts of poverty/inequality, risk and insecurity. Finally, the article situates the concept of vulnerability within the social theory of Karl Polanyi, arguing that it expresses in the conditions of today's globalisation the threats to human livelihood from the inroads of the market that are widely referred to by scholars within the ‘new’ IPE, capturing better than do other concepts the key features of these threats as seen by Polanyi. The article concludes by proposing the concept of vulnerability as a core conceptual category for IPE scholars that offers the potential for the disciplinary field to generate more original insights into the social impacts of the political economy processes to the understanding of which it has made such a major contribution.
Keywords: economics; globalisation; globalization; human security; industrial revolution; inequality; interdependence; international political economy; international relations; poverty; social impact; social problems; vulnerability

Towards a Polanyian Perspective on Fair Trade: Market-based Relationships and the Act of Ethical Consumption - Watson, Matthew (Global Society: Journal of Interdisciplinary International Relations, 2006)
Fair trade requires that developed country consumers engage in market-based transactions with developing country producers. Yet this is not market trade in any straightforward sense, because the purchase of fairly traded products brings consumers into two market relationships at the same time. One is the market relationship through which consumers buy the product itself, which enables them to act altruistically by consciously paying the price premium that the producer receives. The other is the market relationship through which consumers buy the socially reputable knowledge of having helped a distant stranger, which enables them to harness their ostensibly ethical consumption to a knowingly self-interested action. This latter relationship adds a new dimension to orthodox commodity fetishism. A Polanyian perspective is developed to investigate the way in which fair trade reworks the commodity fetish. This serves as a prelude to an extended discussion of the moral status of the behavioural motivations that underpin fair trade consumption.
Keywords: commodity fetishism; comparative studies; economic consumption & ethics; globalization; international trade; relationship marketing; unfair competition

Beyond Globalization: Capitalism, Territoriality and the International Relations of Modernity - Lacher, Hannes (Routledge, 2006)
Hannes Lacher presents a new critical social theory of international relations that integrates sociology, history and political geography to understand the formation and development of modern international relations. Far from implying a return to state-centrist Realism, this essential new volume leads us towards a critical social theory of international relations that questions the prevailing conceptions of the modern international political economy as a collection of nationally bounded spaces more fundamentally than ever before. It also shows us that capitalist modernity itself was, from the beginning, characterized by the dualism of global economic integration and the fragmentation of political space, which actually stems from the divergent origins of capitalism and territorial sovereignty. This book will be of great interest to al students of historical sociology, political geography, international relations and political science.
Keywords: international political economy; international relations

Globalization and contestation: A Polanyian problematic - Munck, Ronaldo (Globalizations, 2006)
The Polanyian problematic presents us with a unified, complex, and dialectical means to interpret globalization and its social contestation by diverse social and political forces. For Karl Polanyi (1886–1964), globalization as we know it would probably be conceived of as an extension of the ‘one big self-regulating market’ he discerned in his day, while his belief that ‘simultaneously a counter-movement was afoot’ provides an interpretative lens to examine the various facets of the counter-globalization movement. The Polanyian problematic of modern history as a ‘double movement’, whereby market expansion and social protection respectively lead phases, provides a useful antidote to all forms of economic reductionism when dealing with globalization on the one hand and political voluntarism with regard to contestation on the other. Basically, globalization is a human construct, and it can thus be deconstructed by society.
Keywords: Polanyi problem; countermovement; globalization

The Dialectics of Design - Jenkins, Barbara (Space & Culture, 2006)
The popularity of deconstructivist architecture around the world has invited controversy over the sensationalist design of these buildings. New urbanists, in particular, have criticized decon architecture as alienating and disorienting. From a historical perspective, this opposition between deconstructivists and new urbanists is the latest in a long line of debates over what constitutes "good design." Using a political-economy approach based on the work of Karl Polanyi, this article examines a centuries-long dialectic in design ideology between those who seek to embed design in social mores and those who attempt to "disembed" it from oppressive discourses. This analysis shows that the dialectic of design movements is intintately connected to the development of capitalist markets.
Keywords: capitalism; cities & towns; cultural studies; deconstructivism; deconstructivism (architecture); dialectic; disembeddedness; embeddedness; good design; modern architecture - 20th century; new urbanism; political economy

Between Aristotle and the Welfare State: The Establishment, Enforcement, and Transformation of the Moral Economy in Karl Polanyi's The Great Transformation - Akturk, Sener (Theoria: A Journal of Social & Political Theory, 2006)
The article examines the transformation of the moral economy in the book "The Great Transformation," by Karl Polyani. Polyani's work has been criticized for having an anti-democratic, Aristotelian, and aristocratic undertones. However, the author claimed that it has been misinterpreted and a communitarian-liberal debate has been brought to clarify the nature of moral economy.
Keywords: Great Transformation, The (Book); criticism; democracy; economic policy

Keynes and Polanyi: the 1920s and the 1990s - Polanyi Levitt, Kari (Review of International Political Economy, 2006)
Keywords: KEYNES, John Maynard, 1883-1946; international political economy

What's Left in the City? What's Right in the Hinterland?: Urban Political Economy in Contemporary Latin America - Goldfrank, Benjamin; Schrank, Andrew (2006)
This paper accounts for the initial divergence and subsequent convergence of two types of urban political economy-neoliberal and socialist-in late twentieth and early twenty first century Latin America. Part 1 identifies the ideological differences between the two types of city as well as their implications for public policy. While neoliberal cities prioritize accumulation, and therefore use tax breaks, regulatory rollbacks, and the repression of organized labor to attract and retain foreign direct investment, their socialist rivals prioritize distribution, and therefore use social funds,microcredit arrangements, and participatory institutions to employ and empower their citizens. Part 2 treats the emergence of municipal neoliberalism as a secondary city or hinterland reaction to the growth of urban primacy or bias in the 1960s and 1970s. While industrial interests in population centers like Mexico City and São Paulo reaped the rewards of import-substituting industrialization, and therefore organized to defend their gains, their agro-commercial rivals paid a high price for tariffs and foreign exchange controls, and therefore deployed free trade zones (and similar incentives) in places like Chihuahua and Salvador to offset or compensate for the growth of urban primacy. Part 3 traces the origins of municipal socialism to the breakdown of ISI and the accompanying debt crisis in the late twentieth century. While neoliberal municipalities had already embraced the world market, and therefore welcomed structural adjustment at the national level, their socialist rivals feared globalization, and responded with a variety of compensatory measures of their own designed to increase the "social wage" not only in Mexico City and São Paulo but in other major cities like Caracas, Montevideo, and Lima. And, finally, Part 4 concludes by offering a Polanyian interpretation of the seemingly odd convergence of neoliberal and socialist municipalities today-suggesting that, whatever their ideological preferences, municipal authorities must balance accumulation with distribution if they are to survive and prosper in a globalized world. ..PAT.-Unpublished Manuscript
Keywords: EPZ; Latin America; Latin America - politics & government; cities & towns; foreign investments; local politics; neoliberalism; participatory budgeting; political planning; socialism

Vulnerability and violence: the impact of globalisation - Kirby, Peadar (Pluto, 2006)
'Vulnerability' is now a key term in globalisation studies. It is used to describe how globalisation impacts on individual security, local communities and even global flows of trade, finance and investment. Yet there has been little attempt to interrogate the term and what it is trying to express about globalisation.Peadar Kirby examines what is really meant by 'vulnerability' and links it to new forms of violence that have resulted from decreased security and social cohesion. He argues that vulnerability and violence are characteristic features of a new world order dominated by neoliberal globalisation. Illustrating his argument with a wealth of examples taken from all over the world -- from the sudden collapse of the middle class in Argentina to increased levels of poverty internationally -- he offers a robust theoretical grounding that will be of use to anyone studying vulnerability and violence and their relation to contemporary globalisation.
Keywords: globalization; globalization - economic aspects; globalization - social aspects; international security; national security; political freedom & security; violence; violence in society

Commercialisation, inequality and the limits to transition in health care: a Polanyian framework for policy analysis - Mackintosh, Maureen (Journal of International Development, 2006)
The effects of commercialised health care in embedding, exacerbating and legitimating social and economic inequality are at the root of widespread and recurrent resistance to commercialisation in health. In low income developing countries suffering generalised poverty, and notably in Sub-Saharan Africa, liberalisation of largely unregulated clinical provision has created a substantially informalised, fee-for-service primary health sector which is exclusionary, low quality and under stress. This article argues against a policy assumption that health systems constitute a sector that can benefit like other commodities from liberalisation. Health care is better understood as a ‘fictional commodity’ in the Polanyian sense: inappropriate for full commodification, producing intensely perverse effects when provided on competitive markets, and therefore requiring planning and social constraint. If managed effectively, integrated health systems—like redistributive land reform and effective labour protection—can support a broader economic transition that avoids extremes of inequality; conversely if treated simply as a transitional sector, health systems can make exclusion and inequality much worse. Copyright © 2006 John Wiley & Sons, Ltd.
Keywords: Africa, Sub-Saharan; economic structure; equality; health care reform; liberalism; medical care; medical policy

Governing the Market: The "Political" and the "Economic" in the Restructuring of the "Third World" - Makki, Fouad (Conference Papers -- International Studies Association, 2006)
My intention in this paper is to rethink the central contentions of "Globalization Theory" with respect to the relationship of the "state" to the "economy." I will do so via a consideration of recent discussions of the formation of the modern states system within the discipline of International Relations, and Karl Polanyi?s suggestive notion of the "double movement" presently enjoying a revival in sociological studies of the conjuncture of the 1990s. The paper concludes with reflections on how these critical reflections might make it possible to gain a betterappreciation of the current neoliberal restructuring of the erstwhile "Third World." PAT.-Conference Proceeding
Keywords: economic structure; economics; globalization; international markets; international trade

Food Sovereignty vs. the Corporate Food Regime - McMichael, Philip (Conference Papers -- International Studies Association, 2006)
In the twenty-first century, the Polanyian trinity of fictitiouscommodities (land, labor and money) cannot be realised through thetwentieth-century double movement. The regulation of money is no longervested in the state per se, but in instrumentalities such as the IMF, whosetask has become a generalized imperative to reproduce (corporate) moneythrough expending labor and land across the world with decreasing regardfor their sustainability. The construction of a 'world agriculture,'deepening the instrumental use, misuse, and abandonment of natural andsocial resources, unfolds within this general imperative. This paper arguesthat the world-wide food sovereignty movement is the most direct symptom ofthis socio-ecological crisis, embodying a diversity of responsescorresponding to the re-spatialization of social and economic relations inthe corporate food regime. As an expression of the corporate food regime,it reveals both the immanent, and the historical, conditions governing thepolitics of capitalist development under the neo-liberal project. ..PAT.-Conference Proceeding
Keywords: commercial products; economic policy; international economic assistance; international economic relations; international studies; sovereignty

The Poverty of the Global Order: Limits of the North/South Division - Mohan, Dia; McMichael, Philip (Conference Papers -- International Studies Association, 2006)
Development in the global order is represented in economically reductionist, and in impoverished, terms. The latter refers to the global reproduction of material inequality through the progressive appropriation of alternative visions of development. We argue that the legitimacy of the global order, while represented in terms of 'economic progress,' depends on the progressive naturalization of its epistemological foundations. Here, solutions to the crisis of development become methods of social control through which the dominant visions of what count as viable futures are reproduced and regulated. We critique efforts to humanise development (eg, World Bank, Amartya Sen) as evidence of developmentalism's epistemological crisis. Karl Polanyi's distinction between 'formal' and 'substantive' economy allows us to transcend the reductionism of the scarcity paradigm and revalue difference as the foundation of equality. We consider examples of substantive economy, which realise equality through strategic sovereignty and representational power, in collective and individual terms. Among other such initiatives these represent practical and epistemological 'spaces of hope' for critique of the crisis of the market epistemology that infects both development studies and international studies. Present divisions of the world must be understood as the impoverished outcomes of a market epistemology's construction and development of inequality. ..PAT.-Conference Proceeding
Keywords: economic development; international organization; international relations; reductionism; social control

Karl Polanyi in Vienna: The Contemporary Significance of The Great Transformation - Polanyi Levitt, Kari; McRobbie, Kenneth (Black Rose Books, 2006)
Karl Polanyi’s belief that the greatest threat to freedom was a poorly administered economy led him to an economics that was more existential and human-centered. Part I of this book develops Polanyi’s thinking for its significance today through a selection of papers on re-reading his major work entitled The Great Transformation. Part II looks at the life and work of Ilona Duczynska (Polanyi’s wife), political activist, writer and translator and important influence over Karl and his work. Kenneth McRobbie, a poet and historian who teaches at the University of British Columbia, is the editor of Humanity, Society and Commitment. Kari Polanyi Levitt, emeritus professor at McGill University, is the editor of The Life and Work of Karl Polanyi.
Keywords: autobiography; biography; business & economics

Globalization and Declining Welfare State: The Case of Social Insurance in Turkey - Yasar, Yavuz (Conference Papers -- International Studies Association, 2006)
The norm has been rapidly moving from the managed markets under the welfare state back to self-regulating market with the rise of contemporary version of globalization. Today?s globalization is characterized by neoliberal economic policies such as privatization, deregulation, and limited government intervention--despite the growth of government--in open economies. In such an environment, social insurance, one of the defining characteristics of the welfare state, has become a great fiscal burden and not surprisingly on the neoliberal agenda of the institutions of global order such as IMF and the World Bank lately. Solutions required by the neoliberal agenda involve privatization and deregulation of social insurance systems especially in developing countries such as Turkey. Despite the fact that the welfare state played a significant role between 1960 and 1980, social insurance has become one of the few safety nets left for many since the beginning of neoliberal policies in Turkey. Now with the increasing pressure from IMF, Turkish government has been actively working on market oriented solutions for financing health insurance, social security and pensions. However, this trend undermining social insurance jeopardizes at least two, if not more, important issues: sovereignty of the state and future of welfare state as an insurance against the unwanted consequences of self-regulating markets. These two issues are investigated and alternative social policy measures are evaluated in the context of Karl Polanyi?s theory of ?double movement.? ..PAT.-Conference Proceeding
Keywords: deregulation; economic policy; economics; globalization; privatization; welfare state

Massacre of the Doves?: Interpreting Israel's 2003 Elections - McMahon, Sean F. (British Journal of Middle Eastern Studies, 2005)
This article argues that Israel's 2003 elections are best understood as a deeper embedding of neoliberalism in the Israeli polity. It is argued that the most accurate characterization of the elections is as an articulation of Polanyi's Phase I of the double-movement. The argument is developed in four stages. First, the Israeli elections are understood as a local reaction to the multilayered processes of globalization. The Israeli state and its elections are located in the neoliberal ideology which underwrites the phenomenon broadly defined as globalization. Second, the election results are reviewed. Third, the dominant interpretations of the elections are critically examined. Specifically, representations of the elections as a defeat of the parties of peace and as a rebuke of Sephardim/ultra-Orthodox influence in Israeli government are interrogated. Fourth, the coalition negotiations of February 2003, the constitution of Israel's 30 th government and some of the initiatives undertaken by Finance Minister Benjamin Netanyahu are explicated through deployment of Polanyi's double-movement framework.
Keywords: Israel - politics and government; double movement; elections; globalization; neoliberalism

Bridging boundaries and Mending Fences? Finding "community" in transboundary conservation approaches - Hoon, Parakh (Conference Papers -- International Studies Association, 2005)
The article presents the conference paper titled "Bridging boundaries and Mending Fences? Finding community in transboundary conservation approaches" prepared for the "Annual Convention of the International Studies Association" held in Honolulu, Hawaii. It discusses the implementation of the Community Based Natural Resource Management in Botswana in early 1990s. It examines the contemporary applications of the idea of embeddedness which was coined by intellectual Karl Polanyi as an analytical and ideological foil to the notion of self-regulating markets.
Keywords: Botswana; conservation of natural resources; conservation projects; international relations; self-regulating market

Gramsci, Polanyi and Impressions from Africa on the Social Forum Phenomenon - Bond, Patrick (International Journal of Urban and Regional Research, 2005)
The  rise  of  the  Social  Forum  phenomenon  has  been  heartily  welcomed,  partly  so  as to unite diverse discourses of anti-neoliberal and anti-imperialist resistance under a common  banner.  There  are  debates  worth  flagging,  however,  that  draw  our  attention to  political  philosophies  (typically  binary  statist  versus  anti-statist  disputes),  visions of agency (typically networked movements versus parties), and potentials for revolutionary processes to emerge within ‘civil society’. In the spirit of Polanyi, many South Africans and other Africans are working on ‘decommodification’ strategies that range from particular sites of project-level struggles to national, regional and international advocacy. But we must be conscious, as well, of warnings by Gramsci about the long march through a civil society often co-opted to support state and neoliberal projects. The merits of African intellectual engagements with radical social movements have been shown in sites such as South African cities, but the African Social Forum awaits further opportunities to welcome allied researchers and academics. As the World Social Forum comes to Africa in 2007, Marcuse’s hope that the constituent movements begin to coalesce around a program is timely. However, this is likely to emanate more from intra-sectoral networks rather than from multidisciplinary moments such as the WSF itself. La montée du phénomène des Forums sociaux a été accueillie chaleureusement, en partie comme manière d’unifier sous un même drapeau les multiples discours de la résistance anti-néolibérale et anti-impérialiste. Certains débats éminents attirent pourtant l’attention sur des philosophies politiques (généralement des oppositions binaires étatistes/anti-étatistes), des visions de l’intermédiation (en général, mouvements interconnectés/partis) et des processus révolutionnaires susceptibles de naître au sein de ‘la société civile’. Dans l’esprit de Polanyi, nombre d’Africains, du Sud et d’ailleurs, s’emploient à des stratégies de ‘démarchandisation’ couvrant à la fois sites de conflit particuliers liés à un projet et plaidoyers aux niveaux national, régional et international. Toutefois, il ne faut pas oublier les avertissements de Gramsci pour qui la longue marche passant par la société civile risquait d’être cooptée afin de soutenir des projets gouvernementaux ou néolibéraux. Si les engagements d’intellectuels africains aux côtés de mouvement sociaux radiaux se sont révélés bénéfiques dans des cas tels que les villes d’Afrique du Sud, le Forum social africain espère d’autres occasions de rallier chercheurs et universitaires. Comme le Forum social mondial se tiendra en Afrique en 2007, l’espoir de Marcuse — de voir les mouvements constitutifs s’unir progressivement autour d’un programme — est d’actualité. Cependant, cette évolution viendra plus probablement de réseaux intra-sectoriels que d’élans multidisciplinaires comme le FSM.
Keywords: GRAMSCI, Antonio, 1891-1937; South Africa; decommodification; development studies; geography; social forum phenomenon

Beyond Boganism - Brown, Beth; Brown, Doug (Journal of Popular Culture, 2005)
The article analyzes the global economy by subjecting it to an interpretive scheme derived from popular culture Boganism, an Australian colloquialism or street slang used by teenagers. Boganism, the social phenomenon of being both unaware and irresponsible, is the result of a particular type of human abandonment. This abandonment is linked to the new hypercapitalism of globalization. The article will establish the structural roots of boganism, examine the case of the abandonment of U.S. youth, and conclude with reform recommendations necessary to shift us beyond boganism to a culture of sustainability. Karl Polanyi, a Hungarian economist, argued a half century ago that the birth of capitalism meant the emergence of what he called the disembedded economy. Polanyi's essential problem with capitalism, when it emerged in the sixteenth century, was that it creates a society in which everyone is dependent on markets to meet their basic needs. The pace of life has clearly increased with the maturation of capitalism and industrialism. But with the high-technology revolution, accompanied as it has been by the globalization of capitalism, what is happening is acceleration of everyday life, the economy, market transactions, and much more. Stratification: relationships of supra- and subordination, relations of domination and injustice. These are the social dimensions and institutional, structural relations between people and groups that have played defining roles in social, political, and economic analysis over the last three centuries of industrialism. Categories of stratification include classism, racism, statism, and sexism, and others. Along with these, we can add boganism.
Keywords: capitalism; disembedded economy; disembeddedness; globalization; popular culture; socioeconomics

Labour and Globalization: Towards a New Internationalism? - Ramasamy, P. (Travail et Mondialisation: Vers un nouvel internationalisme?, 2005)
A one-dimensional view of capitalism inevitably leads to the conclusion that labour is in a state of deep crisis. However, if we examine globalization as a contradictory process, then it is possible to regard its relationship with labour as a transformative one. In this context, the decline of trade union density in developed countries and the rise of new forms of trade unionism in selected countries of the South, illustrate the contradictory relationship between labour and capital. In accordance with Marx, capitalist expansion not only does away with old forms of labour organizations, but has the tendency to create new forms of labour resistance. Similarly, Polanyi argues that attempts to disembed the economy (return to free market enterprise) from the rest of society will be resisted by societal forces. (English)
Keywords: capitalism; developed countries; embeddedness; free enterprise; globalization; international trade; labor; labor unions; labour; labour unions; political doctrines

The Global Resistance Reader - Amoore, Louise (Psychology Press, 2005)
The Global Resistance Reader provides the first comprehensive collection of work on the phenomenal rise of transnational social movements and resistance politics: from the visible struggles against the financial, economic and political authority of large international organizations such as the World Trade Organization, World Bank and International Monetary Fund, to the much less visible acts of resistance in everyday life. The conceptual debates, substantive themes and case studies have been selected to open up the idea of global resistance to interrogation and discussion by students and to provide a one-stop orientation for researchers, journalists, policymakers and activists.
Keywords: GILL, Stephen; political science / globalization; political science / reference

Engendering Charismatic Economies: Pentecostalism, Global Political Economy, and the Crisis of Social Reproduction - Barker, Isabelle V. (Conference Papers -- American Political Science Association, 2005)
Pentecostalism is the fastest growing religion in the world today. A number of explanatory theories exist, but in this paper, I hone in on the nexus between economic restructuring and Pentecostalism to explore this extraordinary expansion. Bringing together the work of feminist political economists and of Karl Polanyi, I argue that neo-liberal globalization threatens mechanisms for meeting social reproductive needs. Neo-liberalism cannot meet these needs on its own, and I suggest that Pentecostalism addresses these gaps, effectively embedding neo-liberal economic policies. It does so by facilitating norms and practices on the part of individual adherents to provide for the care work required for human reproduction; to adopt norms required of a neo-liberal labor force; and, to embrace the kind of transnational social identity that is compatible with labor migration and global markets. ..PAT.-Conference Proceeding
Keywords: CHRISTIANITY; GLOBALIZATION; Globalization; PENTECOSTALISM; Pentecostalism; Polanyi, Karl, 1886-1964; RELIGION & sociology; feminism; feminist political economy; neo-liberalism; social reproduction

Citizenship unbound: The global politics of neo-liberalism and labor migration - Barker, Isabelle Virginie; Cornell, Drucilla (2005)
This dissertation considers the status of citizenship in an era of neo-liberal globalization. Citing increased labor migration and the retreat of domestic social policies throughout the world as intersecting processes, I argue that narratives of national citizenship lie at the heart of this intersection, transformed by rapidly changing geopolitical conditions. Despite challenges, national citizenship remains a relevant political category, though reformulated along the lines of neo-liberal principles of privatization, market rationality, and individual responsibility. the politics and rhetoric surrounding the 1996 federal reforms of immigration and social policy in the United States serve as one example of this process. I further support my claim with an extensive illustration of the linkages between the restructuring of U.S. health care policy for senior citizens with the increased migration of women from the global South to provide low-wage direct care services for the aging population in the United States. I then evaluate the work of Martha Nussbaum, Amartya Sen and Thomas Pogge, arguing that their respective efforts fail to offer effective interventions into the fate of democratic citizenship in an era defined by expanding inequalities and shrinking public spaces. I conclude by bringing together the works of Karl Polanyi, David Held, and Hannah Arendt with feminist scholarship to develop a feminist theory of democracy and political membership for the twenty-first century. (Copyright applies to all Abstracts.)
Keywords: ARENDT, Hannah; HELD, David; NUSSBAUM, Martha; POGGE, Thomas; SEN, Amartya; citizenship; feminist theory; globalization; labour migration; political science; women's studies

José Bové and the Globalisation Countermovement in France and Beyond: A Polanyian Interpretation - Birchfield, Vicki (Review of International Studies, 2005)
This article illustrates the continuing salience of Karl Polanyi's The Great Transformation (1944) by employing two of its central concepts, fictitious commodities and the double movement to interpret the globalisation countermovement and one of its most important figures, José Bové. I explain the transformation of José Bové from rural sheep farmer to French folk hero and global activist and analyse the extent to which his rhetoric and political actions are congruent with Polanyi's key insights. Arguing against the media characterisation of Bové as protectionist, I show that this misrepresentation conceals the larger ideological threat his movement poses to institutionalised politics and neoliberal hegemony. The political vision underlying Bové's symbolic media tactics and articulated in his book, Le Monde n'est pas une Marchandise, reveals significant manifestations of Polanyi's chief intellectual legacy - an unparalleled critique of economism and market society. An often neglected question in Polanyian scholarship is whether or not it is possible to have a market economy without becoming a market society. A more careful analysis of Polanyi's thought sheds light on this key issue while the empirical analysis of Bové's movement reveals its implications for French society and the broader globalisation countermovement.
Keywords: capitalism; commodities; countermovement; economic globalization; economic liberalism; free market economies; globalization; international economics; political movements; social movements

A New Middle East? Globalization, Peace and the Double Movement - Guy Ben-Porat (International Relations, 2005)
The rise and fall of the New Middle East (NME) cannot be separated from wider global developments and must therefore be studied in relation to them, in both their ideational and material aspects. The ideological background of the NME has drawn upon the ideology of globalization and shares its underlying tenets of rationality, professionalism and virtues of market economy. In the early 1990s a discourse of globalization was set in motion, highlighting economic and technological development that supposedly rendered territory and territorial disputes marginal or irrelevant. The NME, supported by Israel's business, political and academic elites, advocated liberal economics and peace as a solution to the region's problems. But Israeli elites have failed to turn the idea of the NME into a hegemonic concept, as this attempted liberal hegemony invoked a Polanyian double movement that undermined the peace process. The scenario of the NME and the trade-off between territorial integrity and promised regional prosperity not only met fierce ideological rejection, but, perhaps more importantly, failed to persuade the many more skeptics. Limited in its appeal and lacking sufficient legitimacy, the peace process was exposed to derailment by extremists, locking the region into cycles of violence.
Keywords: Middle East; capitalism; double movement; economic development; globalization; ideology; international relations

The Economy as a Polity: The Political Constitution of Contemporary Capitalism - Joerges, Christian; Stråth, Bo; Wagner, Peter (Psychology Press, 2005)
The debate about so-called economic globalization has reached a new phase. The hegemony of neo-liberal thinking has ended, in the face of both the increased and increasingly effective resistance to the social consequences of neo-liberal market-making - rising inequality and insecurity throughout the world - and the visibly dysfunctional effects of lack of regulation - currency and stock market crashes, among others. Thus, the story about 'the rise and fall of market society', which was first told in these terms by Karl Polanyi sixty years ago, is about to receive a new chapter. In this light, this volume offers a novel perspective on the interaction between states and markets. In contrast to much of current theoretical wisdom, we hold, with Polanyi, that markets cannot even be consistently thought of as self-regulating. Markets are always constituted by framework conditions that cannot be set by the markets themselves. The range and scope of market rules requires some agreement, or at least acceptance, for economic exchange to be working at all; in democratic societies, these rules are at least theoretically always subject to political debate and decision. To put the issue in theoretical terms: even the most pure version of economic liberalism always entails at the same time a political philosophy. This volume, thus, proposes to understand contemporary capitalism by regarding the economy as a polity, as an arrangement that is always constituted by some collective agreements about its mode of operation. Such theoretical position on its own, though, is insufficient to explain the workings of capitalism once and for all. Historical experiences with capitalism have led to transformations that require new angles of analysis. It is in the nature of the struggles over the embedding of markets that their outcomes are subject to historical contingency and cannot be completely known beforehand. Beyond a review of the theoretical tools at hand, therefore, the analysis of the contemporary constellation of capitalism, also requires an understanding of its recent transformations. This is the second task to which this volume is devoted - through analyses of the current state of regulation of labour and money and through investigations of the historical development and novel forms of the mode of embedding markets. While focusing on the renewal of the analysis of contemporary capitalism, the volume also points to fruitful directions of institutional or policy change and provides perspectives for a much-needed political renewal, with a particular focus on the European Union as a novel polity embedding the European economy.
Keywords: business & economics; economic policy; free enterprise; public policy

Surviving Capitalism: How We Learned to Live with the Market and Remained Almost Human - Ringmar, Erik (Anthem Press, 2005)
Human life cannot be reduced to market transactions and human beings cannot only be treated as economic actors. When the power of the market increases, human beings will always try to protect themselves. Given the differences that exist in social and cultural traditions, these protective responses are likely to differ from one society to the other. This is why, even in a global market, diversity is always likely to persist. This book investigates the question of economic globalization - whether it is likely to lead to full convergence between political models and ways of life, or whether, even in a completely globalized world economy, there is likely to be scope for alternative solutions. But in a fully globalized world, how will we survive capitalism?
Keywords: economic globalization; globalization

Social Embeddedness. Within Political Economy: The Work of Karl Polanyi - Watson, Matthew (Foundations of International Political Economy, 2005)
BOOK ABSTRACT: Despite a burgeoning debate on substantive issues in IPE, little attention has been devoted to its theoretical foundations. In this important new text, Matthew Watson reviews the main current theoretical approaches to IPE and highlights the problems that arise from treating 'states' and 'markets' as separate and contesting units of analysis. Foremost among these problems is the lack of attention given to theorizing the constitution of the individual as both an economic agent and a moral being.
Keywords: international political economy; social embeddedness

Constructing opposition in the age of globalization: the potential of ATTAC - Birchfield, Vicki; Freyberg-Inan, Annette (Globalizations, 2004)
This article examines the movement ATTAC and assesses its potential to function as a vital part of the emerging global opposition to neoliberal globalization. We analyze the agenda of the movement and assess its coherence, both in terms of policy evaluations and prescriptions and in terms of the fit of the movement's organizational structure with its substantive mission and official aims. To this end, we explain the emergence and stellar rise of the movement, compare the particularly successful nation-wide organizations of ATTAC in France and Germany, and examine the movement's transnational activities. We find ATTAC to be coherent in terms of agenda as well as organizational practices and to make a laudable effort to reflect its agenda of democratic empowerment in its political praxis. Acknowledging the enormous challenges faced by transnational civic opposition, we nonetheless conclude optimistically that ATTAC has the potential of serving as a core movement around which such opposition might usefully rally. As a subordinate contribution, our investigation poses the question of how to most usefully conceptualize the nature and role of the movement. We invite scholarly dialogue by locating ATTAC in the context of the study of social movements and transnational civil society and by enriching the theoretical debate on the nature of the emerging global opposition with our empirical observations on one of its main protagonists. Annette Freyberg-Inan is assistant professor at the Political Science Department of the University of Amsterdam. She specializes in the areas of International Relations Theory; International Political Economy and Globalization; European Integration, Democratization and Enlargement; Romanian Politics; Political Psychology; and Methodology. Her most recent publications includeWhat Moves Man: The Realist Theory of International Relations and Its Judgment of Human Nature(New York: SUNY Press, 2004); ‘Organic intellectuals and counter-hegemonic politics in the age of globalisation: the case of ATTAC’, with Vicki Birchfield, in Catherine Eschle and Bice Maiguashca (eds), Critical Theories, World Politics and the ‘Anti-Globalization Movement’(London: Routledge, forthcoming 2005); ‘Transition economies’, in Richard Stubbs and Geoffrey Underhill (eds), Political Economy and the Changing Global Order(Oxford University Press, 3rd ed., forthcoming 2005); Transition, Civil Society, and the Social Sciences in Romania(Stuttgart/Hannover: Ibidem Verlag, forthcoming 2005); ‘World system theory: how the fate of Kosovo reflects the logic and the grip of the world capitalist order’ in Jennifer Sterling-Folker (ed.), Making Sense of IR Theory(Boulder, CO: Lynn Rienner, forthcoming 2005); ‘Which way to progress? The impact of international organizations in Romania’, in Ronald Linden (ed.), Norms and Nannies: The Impact of International Organizations on the Central and East European States(Lanham, MD: Rowman & Littlefield, 2002). Vicki Birchfield is an assistant professor in the School of International Affairs at the Georgia Institute of Technology. Her research interests include comparative and international political economy and European politics. She is currently completing a book manuscript entitledInstitutions, Values and Income Inequality in Capitalist Democraciesand has published articles in theReview of International Political Economy, European Journal of Political Researchand theReview of International Studies.
Keywords: ATTAC; globalization; international studies; neoliberalism; social movements

Antecedents of Resistance: Populism and the Possibilities for Democratic Globalization - Plante, David J.; Niemi, William L. (Conference Papers -- American Political Science Association, 2004)
Globalization is often portrayed as a new and unique phenomenon to our times. However, the dependence of American society upon global markets is not new. American Populists of the 19th century faced a similar matrix of political economic constraints. The Populists faced such challenges as the expansion of international trade, a deflationary international monetary order, integrating global capital markets, dependence on credit, and a political system unable to effectively regulate economic activity to public ends. In short, they responded to a system that from their perspective emphasized corporate profits at the expense of democracy. The Populists goal was to create a more democratic political economy in the face of these constraints. Today globalism has been countered by a diverse series of previously unconnected social movements. This paper argues that these movements are part of a rich tradition of democratic responses to the dislocations resulting from attempts to internationalize and commodify all social relations. As such, these 19th century movements offer instruction in the confrontation between democracy and capitalism in its latest iteration. For example, one important continuity between resistance to globalism today, is the use of democratized traditions of moral economy arguments to confront developing inequalities. Successful fair trade alternatives to free trade similarly depend upon moral economy arguments. Despite the inequalities resulting from globalization, challenges from the democratic promise have endured.
Keywords: capital market; capitalism; corporate profits; democracy; fair; globalism; globalization; international trade; monetary policy; populism; trade

International Relations and the Problem of Difference - Inayatullah, Naeem; Blaney, David L. (Routledge, 2004)
International Relations and the Problem of Difference has developed out of the sense that IR as a discipline does not assess the quality of cultural interactions that shape, and are shaped by, the changing structures and processes of the international system. In this work, the authors re-imagine IR as a uniquely placed site for the study of differences as organized explicitly around the exploration of the relation of wholes and parts and sameness and difference-and always the one in relation to the other. KM: Chapter 5 "Toward an Ethnological IPE" deals extensively with Polanyi's ideas
Keywords: economic anthropology; ethnological IPE; international political economy; international relations; political economy

Environmental Values in a Globalizing World: Nature, Justice and Governance - Lowe, Ian; Paavola, Jouni (Routledge, 2004)
This multidisciplinary volume presents a refreshing new approach to environmental values in the global age. it investigates the challenges that globalization poses to traditional environmental values in general as well as in politics and international governance.Divided into five parts, the book investigates how environmental values could be reconceived in a globalizing world.Part I explores contemporary environmental values and their implications for a globalizing world.Part II examines the development of Western and Eastern environmental valuesPart III discusses contemporary environmental politicsPart IV examines how values inform environmental governance and how governance solutions influence which values are realisedPart V concludes the volume with two different views of the prospects of environmental values in a globalising world. This study will be of great interest to students and researchers studying the environment in philosophy, political science, international relations, international environment law, environmental studies and development studies. KM - Contains chapter: "Global Liberalism, Environmentalism, and the Changing Boundaries of the Political : Karl Polanyi's Insights" by John M. Meyer
Keywords: MEYER, John M.; environmental policy; globalization; public policy

Globalization, Labor and the 'Polanyi Problem' - Munck, Ronaldo (Labor History, 2004)
This article outlines what the Polanyi problem consists of and provides information on some of the implications that arise in developing a Gramscian/Polanyian strategy of counter-hegemony for the labor and the modern social movements, as of August 2004. Labor and new social movements are allegedly an integral element for a progressive solution of the so-called Polanyi problem, which is how the tendency towards the creation of a global free-market economy can be reconciled with a degree of stability and cohesion in society. Taking a Polanyian perspective allows the development of a historical perspective on the dual transformations of globalization and labor. Towards the end of the Second World War, Karl Polanyi wrote of how a self-regulating market that allegedly could not exist for any length of time without annihilating the human and natural substance of society. Such a utopia would allegedly destroy humanity and transform the world into a wilderness, an opinion mirrored by modern eco-socialists. The strategy and ideology of globalization as transformative revolution seems to echo and confirm Polanyi's account of the 19th century industrial revolution, an attempt to set up a self-regulating market.
Keywords: GRAMSCI, Antonio, 1891-1937; Polanyi and Gramsci; Polanyi problem; counter-hegemony; economic policy; free enterprise; globalization; international relations; labor movement; labour movement; social movements

Dynamics of Conflict and System Change: The Great Transformation Revisited - Halperin, Sandra (European Journal of International Relations, 2004)
Karl Polanyi's analysis in The Great Transformation has played a prominent role in shaping our understanding of the nature and outcome of both globalization and the movements that have emerged to resist it. However, this article argues that Polanyi's account of the rise and demise of Europe's 19th-century market system is, in important respects, incomplete and misleading. Its central concern is Polanyi's neglect of class structures and processes and how this leads him to mischaracterize both the international and domestic institutions of Europe's 19th-century market system, and the central dynamic driving its development and ultimate collapse. The article critically reviews key features of Polanyi's analysis. Based on this review, it then presents a re-reading of the history of Europe's unregulated market system. Finally, it considers the implications of this alternative account for how we view the context and conditions for globalization and the ways it can best be resisted or shaped in less destructive ways.
Keywords: Europe; class conflict; globalization; international relations; international trade; markets; organizations and policy; social conflict; transformation; transnational capital

And if there was no state?: critical reflections on Bates, Polanyi and Evans on the role of the state in promoting development - Menocal, Alina Rocha (Third World Quarterly, 2004)
The article review three books about the role of the state in promoting development. It includes "Markets and States in Tropical Africa: The Political Basis of Agricultural Policies," by Robert Bates, "Embedded Autonomy: States and Industrial Transformation," by Peter Evans and "The Great Transformation: The Political and Economic Origins of Our Time," by Karl Polanyi.
Keywords: BATES, Robert H., 1942-; EVANS, Peter, 1944-; Embedded Autonomy: States and Industrial Transformation; Great Transformation, The (Book); Markets & States in Tropical Africa: The Political Basis of Agricultural Policies (Book); nonfiction; state development

'Social Market Economy' as Europe's Social Model? - Joerges, Christian; Roedl, Florian (Social Science Research Network, 2004)
Europe continues to search for its - "European" - social model and the search seems to become increasingly urgent. It is no longer just the "democratic deficit", but also and alongside it, the "social deficit" of the EU which needs to be cured. That new concern is, in fact, a rejection of the older answers. According to the ordo-liberal interpretation of the European legal order as an "Economic Constitution" and, successively, in the analyses of the EU as a "Regulatory State", the sphere of social policy was to remain a domain of the nation state. This seems to have become impossible. The Constitutional Treaty, indeed, makes a new commitment: "The Union shall work for a Social Market Economy". This paper submits that this commitment is conceptually a failure, and politically not credible. The Convention preparing the Constitutional Treaty has apparently ignored the meaning of the concept in the form in which it was shaped in Germany's post-war period. This history entails some pitfalls for the Convention's intentions, as the German "Social Market Economy" involved not only a claim of integrating social concerns into the market economy, but also served to restrict claims for instruments of social policy remarkably at the same time. Moreover, the Convention has failed to confer a new and independent content to the concept of the "Social Market Economy", which could help to overcome the concept's ambivalent history, as well as the Union's real "social deficit". The few innovations, the Charter's Fundamental Social Rights and the Open Method of Co-ordination, were incorporated in such modest and non-committal forms that their potential to further the case for "social Europe" seems marginal. The paper concludes that the invocation of the "Social Market Economy" in the Constitutional Treaty is conceptually flawed and is politically an all too risky promise which may raise expectations which it will subsequently fail to deliver.
Keywords: constitution building; economic law; economic policy; governance; social deficit; social market economy; social policy

Agenda 2010: German social democracy and the market state - Thompson, Peter (Debatte, 2004)
Ideology is always for something. Who thought neoliberalism was any different? The post-Cold War provides an excellent laboratory in which to observe 20th c. civilization crumbling, even as it marches towards world markets unbounded by law or social principles. Through repetition and rhetorical sleight-of-hand, the market has robbed the state and thus the polis of its agency. Thus, Schroeder’s SPD is contemplating yet another retreat from the social democratic model, in favor of the post-welfare-state model already well established in the UK and America. And yet within the SPD ranks are breaking as members watch the party abdicate Germany’s basic social contract. These events are reminiscent of M. Polanyi’s The Great Transformation [1744], and they demonstrate once again Marx’s prescience.
Keywords: Germany; Great Transformation, The (Book); Social Democratic party; markets; social democracy

The third way and the third world: poverty reduction and social inclusion in the rise of 'inclusive' liberalism - Porter, Doug; Craig, David (Review of International Political Economy, 2004)
In the wake of frank neo-liberalism, and in the context of rising security fears, ways are being found to provide market liberalism with a more inclusive face. The Poverty Reduction Strategies currently prominent in international development, and Thirdway OECD 'Social Inclusion' policy frames claim common purpose to promote 'opportunity, empowerment and security' for people and places on the peripheries of global economies and societies. They share commitments to global economic integration and openness, market led growth, 'good' and 'joined up' governance, local and social partnerships, and wide-ranging activation of 'capacities'. But the high rhetorical aspirations of liberalism to social 'inclusivity' have so far overreached empirical gains for the poor. Drawing on developing country examples of Poverty Reduction Strategy and public policy in New Zealand's current Labour government, this paper sketches salient features of 'inclusive' liberalism. It critically examines its status as a Polanyian turn within a wider liberal project, which seeks to re-embed and legitimate a liberal social and economic order.
Keywords: New Zealand; developing countries; international competition; international political economy; liberalism; political planning; poverty; poverty reduction; self-efficacy; social inclusion; third way

Disembedded Liberalism: Why global - Borowiak, Craig (Conference Papers -- Midwestern Political Science Association, 2004)
Bringing together democratic theory and international political economy literatures, I begin with the thesis that economic globalization is undermining the embedded liberalism of the post WWII era. Embodied in the Keynsian welfare state, embedded liberalism held out democratic avenues for disaffected groups to hold political actors responsible for suffering induced by market forces. Transformations in the global economy, however, constrain the options available to governments and curtail avenues of democratic accountability. Some have argued that the market itself can provide an adequate alternative. This view is deeply flawed. Drawing from the economic theory of Hayek and Friedman, I discuss how markets can operate as accountability mechanisms. I then turn to Karl Polanyi to discuss how markets that become disembedded from social contexts induce severe consequences for society and the environment. These consequences exceed what markets alone can account for. What’s more, as Habermas has observed, the system logic of markets is incompatible with the deliberative contexts in which democratic decision-making takes place. To propose markets as the solution to democratic deficits is to miss the point that it is the substitution of markets for social regulation that generates many of the problems in the first place. It is also to ignore the ways markets undermine the very spaces in which legitimate solutions can be determined. Somehow the effects of market accountability need to be accounted for. For this, there can be no substitute for forms of democratic deliberation that are themselves not reducible to market pressures.
Keywords: economics; globalization; international relations; liberalism; markets

How likely is a Post-Smithist 21st Century? - Cole, Constance H. (Conference Papers -- International Studies Association, 2004)
The current understanding of U.S. hegemony rests on the assumptions of neoclassical theories of both the state and the market. While the service-dominated economy is considered post- Fordist, the rhetoric of the state focuses on institutions of democracy. To what extent is our understanding of democracy dependent on the prior assumptions that the economy is ‘free’? If we reexamine the assumptions about the links between state and economy, drawing on the work of Gramsci, and Polanyi the necessary link between state and economy assumed in our current neoclassical theory looks quite different. The thesis of this research is that hegemonic ideologies of the relationship of state and market reinforce the interests of the commercial class at the expense of any meaningful representation of the working classes. Reconceptualizing the links between state and market in terms of an economics subordinate to social relations beyond those of commercial interests indicates the possibilities of a ‘post- Smithist’ understanding of both the imperfections of neoclassical market theories, and of the narrowness of institutional analyses.
Keywords: Fordism; Smithism; United States; democracy; economics; economy; hegemony; international; political; post; theory

The Culture War Goes Global: 'Family Values' and the Shape of U.S. Foreign Policy - Kline, Scott (Conference Papers -- International Studies Association, 2004)
Examines a neoconservative-religious right nexus that has emerged in and around the Bush White House. Discussion on the work of Karl Polanyi to examine a paradoxical tension that exists between U.S. nationalism and the promotion of a free-market economy; Family values nationalism and free market capitalism; Proposed two areas of critique that have been influenced by the work of Christian realists.
Keywords: United States; capitalism; economic policy; free enterprise; international studies; nationalism; neo-conservatism; political doctrines

The Reconfiguration of the State under Economic Conditionality and the Creation of Hollow Democracies ? With Illustrations from Zambia - Lloyd, Peter (Conference Papers -- International Studies Association, 2004)
This paper will explore the linkages and contradictions between the promotion of democracy and the application of economic and political conditionality in Southern Africa, with particular reference to Zambia. Many electoral democracies have emerged in Africa in the last decade in conjunction with and partially as a consequence of the conditions applied to loans by bilateral and multilateral donors. It will be argued that the process of conditionality and the neoliberal policies applied actually inhibit the emergence of substantive democracy and present a threat to the consolidation and longevity of even minimal forms of liberal democracy. The conditions applied to aid represent an attempt to reconfigure the activities, capacity and capabilities of the state. Most significantly, they involve the imposition of a neoliberal economic model which is seen as technically necessary to tackle economic crisis and which due to the leverage offered donors by the indebtedness of recipient countries is uncontestable, yet require active state intervention to achieve (Polanyi’s insight that the creation of self regulating markets require regulatory state activity). A major area of state policy is thus placed beyond accountability to the electorate of the recipient country; this is also true of many aspects of political and social policy. The process of negotiation between the International Financial Institutions and representatives of countries (most often the President and a small group of politicians and advisors from the finance ministry) also promotes a concentration of power within the state as representatives must be able to adopt positions on the behalf of their country and enact agreed policies from the top down. Conditionality thus involves a reduction in the democratic accountability of the state in three ways: Firstly, as political authority shifts upwards to the international sphere, to the IFIs and donor community; secondly as power is centralised within the presidency and finance ministry; thirdly, the scope of democracy is limited as liberalisation and the strict separation of politics and economics are enforced, placing many elements of economic life beyond the reach of democratic institutions. Applying this framework to Zambia, it will be argued that consequently a very limited and hollow form of democracy where most of the important political and economic processes affecting people’s lives are unaccountable to them has been created, and that increasing disillusionment and political volatility are ensuing, possibly representing a threat to even this minimal democracy.
Keywords: South Africa; democracy; economics; international studies; political doctrines; political science

Debt Abides: A Prolegomena for Any Future Chapter 11 - Ayer, John D. (American Bankruptcy Law Journal, 2004)
This article presents information related to market transactions. As a mode of organization, markets are so pervasive in our own lives that it may be hard to think just how novel and contingent (in geologic time) they may be. It was economist Karl Polanyi who sought to isolate a juncture in this process of "becoming a market", the point at which the idea of the market transaction becomes not just a tool or an instrument, but a central organizing principle of social life. But it is not clear that even Polanyi would have been able to conceive a later stage, a stage in which the market becomes not merely a tool of the firm or an expression of sovereignty, but a substitute for the firm and for sovereignty itself.
Keywords: autonomy (Political science); international law; markets; organization; political science; social interaction

The Great Transformation in Understanding Polanyi: Reply to Hejeebu and McCloskey - Blyth, Mark (Critical Review, 2004)
Santhi Hejeebu and Deirdre McCloskey's rebuttal to Karl Polanyi's Great Transformation begs several important questions. Yes, commerce can be found throughout human history--but is that the same as saying that people have been equally capitalistic at all times? If not, then how did modern capitalism come into being? Hejeebu and McCloskey portray capitalism as having evolved gradually, indeed quite naturally, rather than being a contingent product of politics. Not inconsistently, Hejeebu and McCloskey radically distinguish between what people "think" and what they "do"--that is, between their ideas and their actions. This distinction, too, suggests that human action is ahistorically capitalistic--whatever human agents at different times and places might think.
Keywords: Hejeebu; McCloskey; economic thought; history; modern capitalism

War and Social Change in Modern Europe: The Great Transformation Revisited - Halperin, Sandra (Cambridge University Press, 2004)
Halperin traces the persistence of traditional class structures during the development of industrial capitalism in Europe, and the way in which these structures shaped states and state behavior and generated conflict. She documents European conflicts between 1789 and 1914, including small and medium scale conflicts often ignored by researchers and links these conflicts to structures characteristic of industrial capitalist development in Europe before 1945. This book revisits the historical terrain of Karl Polanyi's The Great Transformation (1944), however, it argues that Polanyi's analysis is, in important ways, inaccurate and misleading. Ultimately, the book shows how and why the conflicts both culminated in the world wars and brought about a 'great transformation' in Europe. Its account of this period challenges not only Polanyi's analysis, but a variety of influential perspectives on nationalism, development, conflict, international systems change, and globalization.
Keywords: Europe; history; international relations; political science - history and theory

The Meaning of Freedom in a Complex Society: The Development of Karl Polanyi's Thought on Economics, Modernity, and Human Liberty - Katsh, Gabriel (Harvard University, 2004)
Keywords: freedom in a complex society

Desolation and Enlightenment: Political Knowledge After Total War, Totalitarianism, and the Holocaust - Katznelson, Ira (Columbia University Press, 2004)
During and especially after the Second World War, a group of leading scholars who had been perilously close to the war's devastation joined others fortunate enough to have been protected by distance in an effort to redefine and reinvigorate Western liberal ideals for a radically new age. Treating evil as an analytical category, they sought to discover the sources of twentieth-century horror and the potentialities of the modern state in the wake of western desolation. In the process, they devised strikingly new ways to understand politics, sociology and history that reverberate still. In this major intellectual history, Ira Katznelson examines the works of Hannah Arendt, Robert Dahl, Richard Hofstadter, Harold Lasswell, Charles Lindblom, Karl Polanyi, and David Truman, detailing their engagement with the larger project of reclaiming the West's moral bearing. In light of their epoch's calamities these intellectuals insisted that the tradition of Enlightenment thought required a new realism, a good deal of renovation, and much recommitment. This array of historians, political philosophers, and social scientists understood that a simple reassertion of liberal modernism had been made radically insufficient by the enormities and moral catastrophes of war, totalitarianism, and holocaust. Confronting their period's dashed hopes for reason and knowledge, they asked not just whether the Enlightenment should define modernity, but which Enlightenment we should wish to have. Decades later, in the midst of a new type of war and reanimated discussions of the concept of evil, we share no small stake in assessing their successes and limitations.
Keywords: ARENDT, Hannah; World War II; fascism; military history; political history; political philosophy; political theory; totalitarianism

Global liberalism, environmentalism and the changing boundaries of the political: Karl Polanyi's insights - Meyer, J.M. (Environmental Values in a Globalizing World: Nature, Justice and Governance, 2004)
Keywords: environmentalism; global liberalism

Globalization: People, Perspectives, and Progress - Mott, William H. (Greenwood Publishing Group, 2004)
This study expands the narrow economic-commercial focus of the topical media and places globalization in a multidisciplinary context as a continuing process and a permanent condition that transforms human living and society. Early chapters review the development of globalization as creating and diffusing knowledge, expanding people's perspectives on living, and continuing progress. These chapters introduce globalization as an iterative, human, and deliberate process of creating new knowledge and using it to reinterpret the world, time, and man's place in both. The later chapters present the major analytical perspectives of globalization--political, cultural, and economic--and a comparison of the primary carriers of globalism and barriers to globalization.Drawing on classical and modern analysis, as well as narrow, topical journalism, the work focuses each perspective on people through the human processes of creating knowledge and living together. The work expands the economic perspective beyond the fashionable focus on trade and investment into the triggering and shadowing relationships between economic growth, political conflict, and social stress. The political perspective expands international politics and law to global governance, triadic dispute resolution, and global civil society. The cultural and antiglobal perspectives reflect the success of economic globalization in bringing people directly into the narrowly rational processes of international politics and economics. The final analytical chapter collects and compares observations and develops conclusions about globalization across the several perspectives. Speculation about alterative futures for globalizing humanity can constitute a coherent standard, ideal, or direction for policymaking, or an agenda for continuing research and debate.
Keywords: comparative politics; political science; social science

Sustainable Development and the North American Free Trade Agreement: A Polanyian Interpretation - Plante, David J (University of Utah, 2004)
Keywords: economic integration; environment and development; environment and trade; environmental accounts and accounting; environmental equity; population growth; sustainability; sustainable development; thesis; trade and environment

The Great Transformation II: Human Rights Leapfrogging in the Era of Globalization - Howard-Hassmann, Rhoda (Conference Papers -- American Political Science Association, 2003)
Whether globalization will result in improvement or deterioration in protection of human rights is not a matter that can be observed in the short term. Globalization is, in effect, the second ‘great transformation’ (Polanyi) spreading capitalism over the entire world. In consequence, many of its short-term effects will be negative. Nevertheless, its medium and long-term effects may well be positive, as it impels social changes that will result in greater moves to democracy, economic redistribution, the rule of law, and promotion of civil and political rights. Capitalism is a necessary, though hardly sufficient condition for democracy: democracy is the best, though not the inevitable, political system to protect human rights. This does not mean that the non-Western world will follow the exact same path to protection of human rights that the Western world followed. The West had a singular advantage: it was not expected to protect human rights during its own era of economic expansion. Thus, the West was able to practice slavery, expel surplus populations, and colonize other parts of the world. Genocide and ethnic cleaning were permissible state activities. The non-Western world does not enjoy the advantage of human rights lawlessness. It does, however, enjoy other advantages occasioned by the presence of human rights. There is a global communications network and a global pro-human rights social movement. There is also the movement to global governance. Finally, and paradoxically, there is the global social movement against globalization, which forces some reflection upon its deleterious consequences. Thus, the non-Western world benefits from geographical and chronological human rights ‘leapfrogging’. This, along with the social changes that global capitalism and industrialism may impel, may mean that the medium and long-term consequences of globalization are positive for human rights.
Keywords: capitalism; democracy; globalization; human rights; human rights advocacy; social change

Institutions, Politics and Culture: a Polanyian Perspective on Economic Change - Harriss, John (International Review of Sociology, 2003)
Presents the perspective of philosopher Karl Polanyi on economic change. Works of Polanyi on the topic; Analysis of pre-modern economies by Polanyi. According to Jeffrey Nugent, institutions make social life fairly predictable by restricting some actions and providing incentives for other actions. The article discusses Polanyi's book "The Great Transformation," the self-regulating market economy, scarcity, individual choice, economic development in India, trust in India's corporate sector, new institutional economics, and distribution of private property rights.
Keywords: Great Transformation, The (Book); India; NUGENT, Jeffrey; economic development; institutional economics; personal property; philosophers; scarcity; social interaction

Idiosyncrasy and integration: suggestions from comparative political economy - Jones, Erik (Journal of European Public Policy, 2003)
There is a growing consensus in comparative political economy that 'globalization' is not eliminating the distinctive character of specific nation-states. Even in Europe, where formal integration between countries is most profound, nation-states remain idiosyncratic. Starting from this consensus, the questions I ask are: (a) how can we explain the coincidence of national idiosyncrasy and international integration; (b) what does our explanation tell us about processes of European integration? The answers, I argue, lie in two theoretical traditions -- one stemming from Karl Polanyi's (1957) insistence on the social embeddedness of market institutions and the other from Gunnar Myrdal's (1956) interpretation of the cumulative causality behind integration at the national and international levels. Although well received in other areas, neither tradition has played much of a role in the study of the European Union. The article concludes by suggesting a research program that could develop from the interface between idiosyncrasy and integration.
Keywords: MYRDAL, Gunnar, 1898-1987; convergence (economics); embeddedness; globalization; international political economy

Democracy and the Global System: A Contribution to the Critique of Liberal Internationalism - Biancardi, F. (Palgrave Macmillan UK, 2003)
Jacket abstract: "Democracy and the Global System analyses the relationship between liberal democracy and the global system while developing a critique of liberal internationalism. Fabian Biancardi examines some of the key questions of modern politics and the major ideas of a number of significant authors and texts, including Barrington Moore Jr., Karl Polanyi, Joseph Schumpeter, Samuel Huntington and David Held. While sympathetic to the aim of spreading liberal democracy globally, he demonstrates the many tensions and contradictions involved in achieving this outcome." Google books: What are the prospects of the liberal democratic form of state spreading throughout the world? Democracy and the Global System analyses the relationship between liberal democracy and the international system while developing a critique of liberal internationalism. Fabian Biancardi examines some of the key questions of modern politics and the major ideas of a number of significant authors and texts. While sympathetic to the aim of spreading liberal democracy, he demonstrates the many tensions and contradictions involved in achieving this outcome.
Keywords: democracy; international relations; political ideologies; political science

Great Transformations: Economic Ideas and Institutional Change in the Twentieth Century - Blyth, Mark (Cambridge University Press, 2002)
Mark Blyth argues that economic ideas are powerful political tools as used by domestic groups in order to effect change since whoever defines what the economy is, what is wrong with it, and what would improve it, has a profound political resource in their possession. Blyth analyzes the 1930s and 1970s, two periods of deep-seated institutional change that characterized the twentieth century. Viewing both periods of change as part of the same dynamic, Blyth argues that the 1930s labor reacted against the exigencies of the market and demanded state action to mitigate the market's effects by "embedding liberalism" and the 1970s, those who benefited least from such "embedding" institutions, namely business, reacted against these constraints and sought to overturn that institutional order. In Great Transformations, Blyth demonstrates the critical role economic ideas played in making institutional change possible and he rethinks the relationship between uncertainty, ideas, and interests on how, and under what conditions, institutional change takes place. Mark Blyth is an assistant professor of political science at the Johns Hopkins University specializing in comparative political economy. He has taught at Columbia University, and at the University of Birmingham, UK. Blyth is a member of the editorial board of the Review of International Political Economy.
Keywords: economic policy; political economy; political science; public policy

Place, Capitalism, and Democratic Efficacy - Kogl, Alexandra (Conference Papers -- American Political Science Association, 2002)
Keywords: DELEUZE, Gilles; capitalism; democracy; democratic; economy; efficacy; empire; place; political; theory

The Great Transformation at Sea: Fictitious Commodities and the Crisis of Marine Fisheries - Ziegelmayer, Eric (Conference Papers -- American Political Science Association, 2002)
Challenging contemporary debates concerning the regulation of ocean fisheries, this paper deploys theoretical insights developed by Karl Polanyi. In The Great Transformation, Polanyi documented the consequences of the establishment of market economy upon European society, and thereby upon the entire planet. The concept of the self-regulating market, according to Polanyi was based on three "commodity fictions" of land, labor and money; the extension of this concept to all of the economic institutions of society he called "market utopianism." This paper extends Polanyi’s fictitious commodity thesis to the living resources of the ocean and argues that the roots of the contemporary problems of the world’s fisheries originate in the exposure of nature to a market economy. Concerned with the future governance of ocean resources and democracy in fishery regulation, the paper examines the globalization of the fishing industry in comparative and historical perspective to illuminate the validity of Polanyi’s theory. While there can be no final agreement as to the constitution of "good society", a useful starting point for debate is provided by the work of Karl Polanyi. A good society, he claims, is a society capable of producing goods, and a necessary condition of life in such a society is that human beings and nature are not treated as commodities
Keywords: capitalism; democracy; economy; fictitious commodities; fisheries; fishery policy; political; property; rights; saltwater fishing

Market Liberalism and Social Protection: Hayek, Durkheim and Polanyi in Theoretical Perspective - Akturk, Sener (Journal of Academic Studies, 2002)
Examines the views of neoclassicist Friedrich A. Hayek, sociologist Emile Durkheim and Karl Polanyi on liberalism. Relationship between the individual, the market economy and society; Features of Hayekian neoclassical economics; Information on Polanyi's book 'The Great Transformation.'
Keywords: DURKHEIM, Emile; Great Transformation, The (Book); HAYEK, Friedrich A. von (Friedrich August), 1899-1992; liberalism; social protection

Transnational Pharmaceutical Corporations and Neo-Liberal Business Ethics in India - D'Mello, Bernard (Journal of Business Ethics, 2002)
The author critiques the expedient application of market valuation principles by the transnational corporations and other large firms in the Indian pharmaceutical industry on a number of issues like patents, pricing, irrational drugs, clinical trials, etc. He contends that ethics in business is chiseled and etched within the confines of particular social structures of accumulation. An ascendant neo-liberal social structure of accumulation has basically shaped these firms' sharp opposition to the Indian Patents Act, 1970, government administered pricing, etc. The author contends that the practice of neo-liberal economics is strongly associated with a "one dimensional" ethics that privileges market valuation principles over all others. This seems to inevitably generate a social counter-movement that struggles for social protections. He critiques neo-liberal business practices from a perspective that derives from the work of the economic anthropologist Karl Polanyi. Before the present phase of liberalization in India, markets were "managed", but without a "welfare state" in place. Moving toward deregulation of the markets without a welfare state in place is unethical. Keeping the debilities of the institutional framework of public policy in mind, the author adopts a Polanyian perspective that places its trust and hope in the growing social legitimacy of the counter-movement in opposition to both neo-liberal business practices and the degenerate behavior of state agencies.
Keywords: India; business ethics; intellectual property; international business enterprises; pharmaceutical industry; socialism

The World Bank or Polanyi: Markets, Poverty and Social Well-being in Latin America - Kirby, Peadar (New Political Economy, 2002)
Explores the role of markets in achieving social well-being in Latin America, highlighting alternatives theories for this relationship based on the work of Karl Polanyi. Role of markets in reducing poverty; Relation between markets and social institutions; Ways in which market liberalization is damaging the livelihoods of the poor.
Keywords: Latin America; markets; poverty; social institutions

Globalization and Democracy: A New 'Great Transformation'? - Munck, Ronaldo (Annals of the American Academy of Political & Social Science, 2002)
Examines the relationship between democracy and development to set the scene for the pressing contemporary issue of how globalization might affect democracy and vice versa. Reference to the work of Karl Polanyi who posited a dual movement of market expansion matched by increasing social control over it; Impact of globalization.
Keywords: POLANYI, Karl, 1886-1964; democracy; double movement; economic development; globalization

Constructing a European Market: Standards, Regulation, and Governance - Egan, Michelle P. (Oxford University Press, 2001)
'An excellent contribution to our understanding of the political construction of markets... This is a well-written book, enjoyable to read as well as being very informative. I view this volume as a 'must read' for all scholars and graduate students in the areas of government and business, the politics of market economies and comparative politics in general. Michelle Egan's description and explanation of market construction and its impact on business standards, regulation and governance will be valuable to all of us for many, many years to come.' -Henry Jacek, McMaster University; Polibus: Newsletter of the IPSA Research CommitteeThis book provides a detailed analysis of the policies and institutions used by the EU to create a single market. Through a historical overview, sectoral case studies, and an assessment of recent policy initiatives, the author provides a comprehensive account of the evolution of European economic integration.
Keywords: European Court of Justice; European Union; United States; business & economics; economic policy; harmonization; market integration; mutual recognition; public policy; regulation; single market; standards; trade barriers

Institutional Investors and Polanyi's Double Movement: A Model of Contemporary Currency Crises - Harmes, Adam (Review of International Political Economy, 2001)
This article constructs a model of contemporary currency crises which incorporates the role played by institutional investors and the dynamics associated with Karl Polanyi's notion of the "double movement." Polanyi's double movement, and its recognition of the need to integrate politics with economics, is used to explain why so many governments are prone to pursue policies that lead to a speculative attack against fixed exchange rates and why virtually every modern fixed exchange rate regime has ended in crisis. Evidence on the short-term and herd behaviour of institutional investors is used to explain why contemporary currency crises do not appear to be justified by underlying economic fundamentals and why these crises do so much more damage than their earlier counterparts. The model is then applied to the 1992 European Exchange Rate Mechanism crisis, the 1994 Mexican peso crisis and the 1997 East Asian crisis. While recognizing that variations exist in the specific circumstances of each episode, the argument of this article is that the progression of events do seem to conform to the model presented.
Keywords: corporate finance and governance; double movement; economic development; financial instruments; financial markets; foreign exchange; institutional investors; international linkages to development; international monetary arrangements and institutions; international political economy; non-bank financial institutions; pension funds; role of international organizations; saving and capital investment

Contesting the "Great transformation" : local struggles with the market in South India - Herring, Ronald (Agrarian studies : synthetic work at the cutting edge, ed. by James C. Scott and Nina Bhatt, 2001)
Keywords: India; agrarian studies

Regulationist and Autopoieticist Reflections on Polanyi's Account of Market Economies and the Market Society - Jessop, Bob (New Political Economy, 2001)
This article re-interprets and develops Polanyi’s substantive institutionalist analysis of capitalist market economies and the market society in the light of two more recent approaches to the same issues. These are the Parisian ‘regulation school’ on contemporary capitalism and systems-theoretica l accounts of the modern economy. All three regard the capitalist economy (or, for autopoietic systems theory, the market economy) as an operationally autonomous system that is nonetheless socially embedded and needful of complex forms of social regulation. For each, an adequate account of economic activities should explore how they are related to the wider social environment; how they are embedded in a wider nexus of social institutions; how the latter assist in reproducing the capitalist (or market) economy; and how their development is coupled to that of these and other environing institutions. There are also some important differ- ences among these approaches, however, which enable an exploration of their respective limitations and also provide useful bases for further theoretical and empirical research. Thus, after presenting these three perspectives on the institutedness and embeddedness of economies. I consider some basic problems in analysing the improbable stability and reproducibility of the capitalist economy, paying particular attention to governance and meta-governance.
Keywords: capitalism; economics; market society; political economy; regulation school; substantive approach

A Tale of Three Karls: Marx, Popper, Polanyi and Post-Socialist Europe - Marquand, David (Royal Institute of Philosophy Supplement, 2000)
Focuses on the social and political changes brought about by capitalism in Europe. Advocacy of socialist Karl Marx, Karl Popper and Karl Polanyi for social democracy; Discussion on the relationship between society and economy; Notion of futurism regarding the inevitability of change.
Keywords: Europe; European politics & government; capitalism; change; socialism

The Second Great Transformation: The Politics of Globalisation in the Global North - Zincone, Giovanna; Agnew, John (Space & Polity, 2000)
Dominant strands of thinking in contemporary social science consider economic globalisation, the increasing role of cross-border flows and transactions in economic organisation, in terms of some combination of either limited or considerable economic impact and either positive or negative consequences for the general welfare. Little attention has been given thus far to its political consequences within those parts of the world, the developed countries of the Global North, where its impact should be greatest. This paper argues that economic globalisation is in fact the geographical face of a new great transformation in the forces of production (reductions in transport and communication costs, dramatically increased capital and labour mobility, delocalisation of technological innovation, etc.) on a par in its potential impact with the transition to market society with fragmented states first identified by Karl Polanyi. Globalisation, it is claimed here, is the product of action by states as much as markets and, in the short-term, seems to accentuate social inequalities within states, to weaken the rights of current citizens, to lessen the weight of the democratic vote and to stimulate a profound restructuring of both work and the welfare state in the developed world or ‘Global North'. But more significantly, in the long term, when focus on globalisation shifts from its recent economic causes and short-term political impact to its more long term political consequences, recent trends towards a more global economy can be seen in a different light: as entailing a potential positive transformation in the geographical organisation of political rights and citizenship on a par with the first great transformation in economic life and citizenship signalled by the coming of market society.
Keywords: globalization; international economic relations; market society; political science; production (economic theory)

Conceptualizing Resistance to Globalization - Chin, Christine B. N.; Mittelman, James H. (Globalization and the Politics of Resistance, 2000)
Assessments of resistance to globalization are necessarily influenced by the manner in which one conceptualizes these processes. Too often, both of the terms (‘resistance’ and ‘globalization’) are used promiscuously, the latter as a buzzword or catchall and the former in many different ways, sometimes as a synonym for challenges, protests, intransigence, or even evasions. Hence, we seek to juxtapose alternative explanations of resistance and highlight the complexities of conceptualizing it. The purpose of this chapter, then, is to explore the question, what is the meaning of resistance in the context of globalization?
Keywords: Islamist movement; NAFTA; globalization; international political economy; organic intellectual; resistance; symbolic resource; transnational capital

The Rise of the Capital-State and Neo-Nationalism: A New Polanyian Moment - Svitych, Oleksandr (Brill, 2022)
Keywords: critical social sciences; global studies; neo-nationalism; populism; social sciences; sociology & anthropology

Karl Polanyi and the Rise of Fascism - England, Christopher M. (New Political Science, 2022)
This article reconstructs Karl Polanyi’s account of fascism’s rise in his 1935 article, “The Essence of Fascism.” Following the elevation of Hitler to power in 1933, Polanyi embarked on a reassessment of Nietzsche, Othmar Spann, Spengler, Evola, and other figures of the interwar conservative revolution. He argues that the fascist quest for national unity emerges when 19th century liberalism fails to address the growing atomization and economic dislocation of modern society. On the one hand, fascism valorizes the mythopoetic, prehistorical vitalism that liberal rationalism and social democracy sought to purge from public life. On the other, fascism aspires to a higher form of elitist, technological mastery than egalitarian states can achieve. These tensions, he predicts, will result in the radicalization and collapse of fascist regimes in a European war. This article illuminates Polanyi’s deep understanding of political modernity and the contemporary implications of his philosophical critique of the far right.
Keywords: Karl Polanyi; conservative revolution; fascism; modernity; radical right

The political trilemma of contemporary social-ecological transformation – lessons from Karl Polanyi’s The Great Transformation - Novy, Andreas (Globalizations, 2022)
This article advances Rodrik's political trilemma of the world economy by using insights from Polanyi’s The Great Transformation, which helps to grasp the interwoven dynamics of long-term transformations due to climate change and geopolitical reordering on one hand, and on the other short-term political ruptures due to countermovements. Rodrik's globalization trilemma shows the incompatibility of hyperglobalization with the need for an enlarged democratic policy space. Its nodes (globalization, nation state and democracy), however, have to be redefined to grasp contemporary dynamics of deglobalization. Based on a modified political trilemma of contemporary social-ecological transformation, I discuss and compare three visions and the resultant strategies: (1) Liberal globalism, focusing on hyperglobalization and individualism, (2) nationalistic capitalism, stressing national sovereignty and authoritarian governance, and (3) foundational economy based on planetary coexistence which combines selective economic deglobalization with a strengthening of a place-based foundational economy, and their respective social-ecological infrastructural configurations.
Keywords: Great Transformation, The (Book); Polanyi; deglobalization; foundational economy; hyperglobalization; social-ecological transformation

Polanyi, Market Fundamentalism, and the Institutional Structure of Capitalism - Burlamaqui, Leonardo (CEBRI Brazilian Center for International Relations, 2022)
The basic proposition of this paper is that the so-called "new economic sociology", which is rooted in key ideas of Karl Polanyi, is an indispensable "tool" for two tasks: a) it provides us with a powerful critique of market fundamentalism, and b) it allows us to analyze the economic performance of contemporary capitalism by accessing the working of its institutional structure. From an analytical perspective, the paper suggests that Polanyian Economic Sociology is an essential complement to both the Schumpeterian and the Post-Keynesian perspectives in economics. This is especially so when it comes to the discussion of "socioeconomic stability" and, more precisely, as Keynes himself stated in the General Theory: to explain why capitalist economies manifest themselves in different ways and degrees, in spite of encompassing inherent elements of instability and unpredictability.The basic proposition of this paper is that the so-called "new economic sociology", which is rooted in key ideas of Karl Polanyi, is an indispensable "tool" for two tasks: a) it provides us with a powerful critique of market fundamentalism, and b) it allows us to analyze the economic performance of contemporary capitalism by accessing the working of its institutional structure. From an analytical perspective, the paper suggests that Polanyian Economic Sociology is an essential complement to both the Schumpeterian and the Post-Keynesian perspectives in economics. This is especially so when it comes to the discussion of "socioeconomic stability" and, more precisely, as Keynes himself stated in the General Theory: to explain why capitalist economies manifest themselves in different ways and degrees, in spite of encompassing inherent elements of instability and unpredictability.
Keywords: Brazil; new economic sociology; political economy

Capitalism and Crisis: Thinking Through Capitalist Crisis with Schumpeter and Polanyi - Delanty, Gerard (Capitalism, Democracy, Socialism: Critical Debates, 2022)
The chapter offers an analysis of capitalist crisis through a reading and discussion of two seminal texts on capitalism, Joseph Schumpeter’s Capitalism, Socialism and Democracy [1943] and Karl Polanyi’s The Great Transformation [1944]. These inspiring works on economic history and social theory offer profound insights into the nature of capitalist crisis. Although written in the mid-twentieth century many of the insights in these books are of relevance to the current situation as capitalism undergoes another revulsion. While the two authors were very different – Polanyi a left-wing critic of capitalism; Schumpeter a politically right-wing economist who favoured capitalism – both were influenced by Marx’s analysis of capitalism and have helped to shape the debate on the crisis of capitalism. Indeed, Schumpeter was convinced Marx was mostly right in his prediction of the end of capitalism and the triumph of socialism. The chapter begins with a brief account of the Marxist theory capitalism in order to contextualise the discussion of the two theorists.
Keywords: MARX, Karl, 1818-1883; Polanyi; SCHUMPETER, Joseph Alois, 1883-1950; capitalism; crisis

The double movement in Africa: a Nkrumah-Polanyi analysis of free market fatigue in Ghana’s private sector - Langan, Mark (Review of International Political Economy, 2021)
Karl Polanyi’s double movement is a key tool for conceptualising free market fatigue in African business communities wrought by the insecurities of trade liberalisation. Synthesising Polanyi with Kwame Nkrumah’s work on neo-colonialism, the article argues that exhausted business communities in Africa can contest free market reforms and push for a return to developmentalist strategies, underscoring a double movement. In this discussion it highlights Ghana, a ‘donor darling’ in terms of historical implementation of free market reform. It builds upon the author’s engagement with 66 interviewees – business people and policy stakeholders – in relation to the condition of that country’s poultry and tomato industries. Unpacking interviewee narratives, the article points to a striking common theme, namely that business stakeholders call for the re-embedding of the economy via developmentalist strategies to move beyond neo-colonial trade systems. In this vein, the article provides an original contribution to studies of International Political Economy by demonstrating the efficacy of a Nkrumah-Polanyi ensemble for making sense of business communities’ potential role in countermovements for developmentalism in Africa.
Keywords: Ghana; Nkrumah; Polanyi; double movement; free trade; neo-colonialism; private sector

Seeing like a Socialist: On Socialist Worldviews from Polanyi to Taylor to Now - Grant, John; Dunlop, Mallory (New Political Science, 2021)
In this article we argue that reinvigorating socialist politics requires championing a socialist worldview that goes beyond the critique of capitalism. Neglecting such an outlook leaves socialism tethered to the fortunes of capitalism and inhibits a broader account of its own virtues. We begin by explaining why worldview thinking is appropriate today. Then we examine two underappreciated works by Karl Polanyi (his 1927 lecture “On Freedom”) and Charles Taylor (his 1974 essay “Socialism and Weltanschauung”). Each treats worldview thinking as indispensable and we use them as catalysts for developing a socialist vision. Finally, we bring our insights to bear on the worldview potential of socialist republicanism. We contend that a promising worldview emerges by elaborating the following components: a political anthropology of human possibilities; anti-capitalism, social freedom, and non-domination; socialist civic virtues; and the promise and limits of pluralism.
Keywords: TAYLOR, Charles; socialism

Platform Power and Regulatory Politics: Polanyi for the 21st Century - Cioffi, John W.; Kenney, Martin; Zysman, John (2021)
The rapid rise, expansion, and growing asymmetric power of online platform firms towards other businesses, labor and even the state itself occurred in a context of minimal regulatory oversight. In many respects, because the existing legal system was handicapped in understanding and regulating the new platform business models. The platform firms undermined traditional industry boundaries and developed surprising synergies by expanding in unexpected ways due to their ability leverage data and computational expertise. The growth of these platforms was accompanied by minimal intervention by state actors until recently, as concerns about the platform firms’ remarkable power has attracted the concern of States globally and the previous regime is giving way to intense debate and increasingly interventionist governmental policies and enforcement actions. We examine several salient aspects of this emerging regulatory and political reaction, and suggest that this represents an attempt to rebalance the positions of social groups in their relationship to the increasingly central platform firms. First, we view the rise of, and recent political responses to, the often-predatory power and manipulative conduct of platform firm in terms of a “Polanyian” double movement in which the destabilizing and destructive effects of unchecked corporate power and market development eventually generates political and regulatory responses to constrain private actions by new economic actors as they threaten the social, political, and economic order. Second, incipient legal changes, most notably the EU’s proposed Digital Markets Act and Digital Services Act, indicate a shift in regulatory emphasis from competition (and antitrust) policy and law, which has proven limited in its capacity to address inherent monopolistic tendencies of platform firms and markets, towards more intensive and encompassing forms of social and economic regulation. Finally, the political dynamics of legal and institutional change open up new possibilities for political economic and societal reordering, but the particular changes will likely vary in character and significance across political jurisdictions, and therefore follow distinctive and possibly divergent developmental trajectories. We hypothesize that the EU may be able to become the first-mover in regulating the powerful multinational platform firms. We recognize that we are at the very beginning of a transformational process that is likely to reorder old and generate new political economic interests, identities, coalitions, and conflicts at the sectoral, national, regional, and international levels.
Keywords: European Union; Platform economy; Polanyi; antitrust; monopoly

Constituting the Political Economy of the Kurds: Social Embeddedness, Hegemony, and Identity - Tekdemir, Omer (Routledge, 2021)
This book examines the development of Kurdish political economy and the emergence of collective Kurdish identity within a historical context through three main periods: the late-Ottoman Empire, the initial Republican Turkey era, and then the post-1990s period. It relates historical developments to the dynamics of Kurdish society, including the anthropological realities of the nineteenth century through the moral economy frame, the evolving nature of nationalism in the early twentieth century and the more recent construction of a modern political Kurdishness by means of radical democracy, and an agonistic pluralism shaped by left-wing populism.
Keywords: Kurdistan; Political Science / World / Middle Eastern; embeddedness; ethnic studies; middle eastern studies; regional studies

Non-market institutions and crime in US counties: Hayek v. Polanyi - Zullo, Roland (Review of Social Economy, 2021)
Karl Polanyi’s The great transformation emphasized the importance of non-market institutions for social equity and stability. In that same era, Friedrich Hayek postulated in The road to serfdom that superior economies were market-based and featured minimal government. I compare these worldviews in relation to property and violent crime. Using US county data, change in crime is modeled as a function of economic structure, economic conditions, and demographics. Consistent with Polanyi, the size of the public sector in the economy negatively associates with crime. Within the public sector, education is a critical crime-reducing function, more so than law enforcement. Industry diversity is positively associated with crime, contrary to Hayek. Manufacturing equates with lower crime and the size of the private non-profit sector is unrelated to crime. Overall the results favor Polanyi’s assertion that non-market institutions are necessary to counter the harsh outcomes arising from market economic systems.
Keywords: H41 (public goods); P17 (capitalism performance); Socialism; Z13 (economic sociology); crime; laissez-faire; non-market institutions; public goods

Commodification & countermovement: community-supported agriculture (CSA): a case study in Minas Gerais, Brazil - Matzembacher, Daniele Eckert; Meira, Fabio Bittencourt (Organizações & Sociedade, 2020)
The conventional way of producing and distributing food is based on the use of agrochemicals, fertilizers, industrial fertilizers and other techniques from the Green Revolution, with increasing dependence on financial-industrial capital, which implies the intensification of the agriculture commodification. The object of this study was the emergence of modes of organization resisting this trend. Based on the theoretical reference of Karl Polanyi (2012a, 2012b), a case study was developed in a Community-Supported Agriculture (CSA) initiative. It is a movement that resituates agricultural production through the principles of fair trade, agroecology and the use of short supply chains, which bring production and consumption closer together. The result is a better nutritious quality food at affordable and fair price. The analysis of the CSA Alfa case points to the coexistence of different principles of regulation, in a combination of mercantile exchange and reciprocity. According to the proposition by Karl Polanyi, the economic activity is shown to imbricate with the social aspect, of which friendship, tolerance, fidelity and commitment establish a community ethos around food. The CSA seems to manifest a countermovement to the commodification by enhancing the relative autonomy of individuals that elevates the social cohesion of the participating groups. Resumo A forma que se tornou convencional de produzir e distribuir alimentos baseia-se no uso de agroquímicos, adubos, fertilizantes industriais e de outras técnicas provenientes da Revolução Verde, com crescente dependência do capital financeiro-industrial. Isto significa a intensificação da mercantilização da agricultura. O problema que norteou esta pesquisa é a emergência de modos de organização resistentes a essa tendência. Com base no referencial teórico de Karl Polanyi (2012a, 2012b), construiu-se um estudo de caso cujo objeto é a agricultura sustentada pela comunidade, cujo acrônimo em inglês é CSA (community supported agriculture). Trata-se de um movimento que ressitua a produção agrícola pelos princípios do comércio justo e da agroecologia e uso de cadeias curtas que aproximam produção e consumo. O resultado é um alimento de qualidade nutritiva superior a preço acessível e justo. A análise do caso CSA Alfa aponta a coexistência de diferentes princípios de regulação numa combinação de troca mercantil e reciprocidade. Na esteira de Karl Polanyi, observa-se a atividade econômica imbricada ao social, daí que amizade, tolerância, fidelidade e comprometimento estabelecem um ethos comunitário em torno do alimento. A CSA parece manifestar um contramovimento à mercantilização ao potencializar a autonomia relativa dos indivíduos, o que eleva a coesão social dos grupos participantes.
Keywords: Karl Polanyi; commodification; community-supported agriculture; reciprocity; social cohesion

Double movement, embeddedness and the transformation of the financial system - Galarza, Oscar Ugarteche (Karl Polanyi and twenty-first-century capitalism, 2020)
The chapter reviews aspects of the possible transformation of the financial system into a banking complex, that comprises both embedded Too Big to Fail (TBTF) financial institutions and disembedded ones. The transformation of the financial system into a two-tier banking complex is the result of the disconnection of the TBTF embedded institutions and the right size to fail disembedded financial institutions. The chapter revises the scope and consequences of this change on the monopolization of financial capitalism and international financial governance. It contains two sub-sections. The first reviews Polanyi’s concept of embeddedness/ disembeddedness and TBTF; the second reviews the concept of a complex. This chapter aims to use Polanyi’s concept of embeddedness and disembeddedness in order to understand how the category of TBTF financial institutions came into being through the double movement of market deregulation and social regulation. The concepts of embeddedness in social regulation and disembeddedness under market regulation permit an understanding of how, as the few TBTF financial institutions re-embedded themselves, becoming risk proof, the majority remained disembedded and subject to failures. We argue that, given this, the financial system may no longer be considered a system.
Keywords: disembeddedness; double movement; embeddedness; financial system; too big to fail

Debt, land and money: From Polanyi to the new economic archaeology - Hudson, Michael (Karl Polanyi and twenty-first-century capitalism, 2020)
Polanyi spoke of the commodification of money, and this chapter focuses on how interest-bearing debt became the major dynamic, also contributing to the commodification of land and labor. By the late third millennium BC the main way to obtain manual labor was to lend money and make debtors work off their debts as an antichretic interest charge. Personal debt became the lever for creditors to pry land out of the clan-based tenure system, mainly for sale under economic duress. Debtors who pledged their crop or land rights usually ended up forfeiting them. This alienation catalyzed the ‘commodification’ of land. By tracing these debt dynamics, the new economic archaeology is compatible with Polanyi’s intuitions and recognition that market relations are embedded in social relations, and extends his analysis in tracing how administered pricing and monetary valuations created the preconditions for market exchange. The earliest markets, credit and land tenure systems were regulated. Administered pricing was a precondition for creating weights, measures and price equivalencies to enable market exchange to evolve more flexibly.

Multilinear trajectories: Polanyi, The Great Transformation and the American exception - Lacher, Hannes (Karl Polanyi and twenty-first-century capitalism, 2020)
Karl Polanyi’s call, in The Great Transformation, for a re-embedding of markets, is widely understood to have come to fruition in the American New Deal and in the post-war order of ‘embedded liberalism’. Based on archival sources, this chapter shows that Polanyi’s political project was far more radical. Polanyi initially considered the New Deal a vital response to the problems of American capitalism, but one that would have little relevance to the problems and dynamics of European societies. There, he considered a socialist transformation both possible and necessary. But eventually, Polanyi realised that the US, far from remaining an exceptional outlier of ‘nineteenth-century civilisation’, was imposing its model on Britain and Europe. The internationalisation of the American New Deal in the Bretton Woods order marked the defeat of Polanyi’s political project.

Polanyi in space - Peck, Jamie (Karl Polanyi and twenty-first-century capitalism, 2020)
The chapter addresses the potential of Karl Polanyi’s contribution as a spatial theorist, or as an economic geographer in all but name. Although Polanyi did not identify as a spatial or geographical theorist as such, his work is rich with spatial insights and implications, notably as one of the original analysts of economic diversity. The chapter begins by contextualising Polanyi’s work in relation to the shifting locales and vantage points that shaped its production. It then turns to the question of the potential of Polanyi’s research programme (incomplete as it understandably was) for the conceptualisation and exploration of economic geographies. The goal here is to sketch some of the ways in which neoPolanyian approaches can be put to work in the service of geographically sensitive modes of economic inquiry, including those attuned to the ongoing diversity of economic formations and development trajectories, contemporary engagements with uneven spatial development, and the evaluation of (localised) economic experimentation. Polanyi’s programmatic project of ‘comparative economics’ was never completed during his own lifetime. There is much to be gained from resuming this project.

Polanyi’s democratic socialist vision: Piketty through the lens of Polanyi - Somers, Margaret R.; Block, Fred (Karl Polanyi and twenty-first-century capitalism, 2020)
This chapter brings Karl Polanyi into dialogue with Thomas Piketty, author of Capital in the Twenty-First Century. The dialogue is intended to make visible key aspects of Polanyi’s theoretical framework while also suggesting limitations in Piketty’s approach to political economy. Specifically, the authors use the concept of ‘predistribution’ – implicit in Polanyi – to critique Piketty’s emphasis on redistribution as the solution to growing wealth and income inequality. Predistribution conveys the idea that the initial market distribution of income is not natural but is shaped by the systematic exercise of political and economic power.

The Euro as a Polity: Karl Polanyi in Frankfurt? - Thomasberger, Claus (Global Perspectives, 2020)
As factors of production, labor, money, and land play a role in economics that is rarely understood. The difficulty of deriving the contribution of the individual factor of production to the value of jointly produced final commodities (the famous “problem of imputation”) occupied generations of Austrian economists (Hayek 1984) and inspired Ludwig Mises to produce his 1920 article “Economic Calculation in the Socialist Commonwealth” (Mises 1935). Any attempt at rational socialist planning is utopian, Mises argued, because only price-making markets for the factors of production provide the information for economically rational decision-making. If the birthplace of neoliberalism was, as Slobodian (2018, p. 30) put it, Ludwig Mises’s office in the Vienna Chamber of Commerce, this article was its moment of birth.Karl Polanyi was one of the first to respond, doing so in the same journal in which Mises’s piece had been published, the Archiv für Sozialwissenschaften, long before Friedrich Hayek, Walter Lippmann, Lionel Robbins, and German ordoliberals such as Alexander Rüstow and Wilhelm Röpke intervened (Polanyi 2016, 2018b). In his contributions to what became the famous socialist accounting debate, Polanyi outlined his idea of a society’s “constitutional form … as a relationship of mutual recognition” (Polanyi 2018a, 54) based on direct cooperation between consumers and producers, as well as a functional democracy.Two decades later, Polanyi resumed this discourse with a more radical critique, making use of Mises’s argument for his own end (cf. Thomasberger 2020). Mises’s case for price making markets is no less utopian than the central planning model, he argued in The Great Transformation (TGT). The crucial point, Polanyi contended, is that the factors of production are fundamentally different from genuine commodities. Polanyi drew on a line of reasoning put forward by the sociologist Ferdinand Tönnies (2001, p. 81-82) and by Mises’s intimate enemy, the Austrian economist Friedrich Wieser (1927, p. 175-77), who was inclined toward Fabian socialist ideas. Given that the factors of production are not (and cannot be) produced for sale by private enterprises, the commodity form of labor, money, and land is fictitious.Polanyi’s category fictitious commodities is the pivot of Klein’s paper. This starting point allows him to go beyond the common interpretation of Polanyi’s work, which focuses on the dichotomy of market opening and social closure, and to address instead a more profound problem: the conflict between capitalism and democracy. Such a reading is indeed closer to the core of the Polanyi approach, which refers to a society that “transcends the self-regulating market by consciously subordinating it to a democratic society” (Polanyi 2001, 242). Not social protection, but democracy, is the alternative to the self-regulation of the market. Polanyi never believed that protection could achieve more than a temporary stabilization of market society. In fact, it is somewhat paradoxical that in the discussion about the contradictions of European integration, Polanyi is celebrated as a defender of societal closure, while he himself expressed the conviction that the protective measures “impaired the self-regulation of the market, disorganized industrial life … and finally disrupted the social organization based upon it” (Polanyi 2001, 4). From the point of view of the conflict between capitalism and democracy, the institutions that result from the attempt to commodify labor, money, and land are crucial because they are, as Klein puts it, the “point of entry of political power into the economic sphere” (Klein 2020, 11). Concerning the debate about the crisis of European integration, this is a rather unexplored terrain.In what follows, I will not discuss the question of whether the category fictitious commodities can be fruitfully linked to the idea of premodern modes of economic integration, a connection that Polanyi himself never established. Instead, I will concentrate on two issues that Klein’s paper raises without discussing them explicitly. The first question is: What if the creation of a self-regulating market system becomes the dominant political goal? What if, for example, the central bank is transformed into a market maker for money on political grounds? The second point seems to me even more important. Europe is not a nation. However, “in Polanyi’s schema, the self-regulating market was a national economic institution” (Polanyi-Levitt 2013, 89), which linked the “rest of the world” to England by a “golden straightjacket,” as Polanyi’s daughter, the development economist Kari Polanyi Levitt, remarked. In TGT even European colonialism plays only a marginal role. As a result, European integration after World War II raises issues that Polanyi did not discuss in depth. I will proceed in two steps: First, I will reconstruct some essential points of Polanyi’s analysis. Following this, I will pose the question of how to apply his analysis to Europe.From the point of view of a market system, the crux of the factors of production—or the fictitious commodities, as I shall hereinafter refer to them—is that, on the one hand, private enterprises must be enabled to buy labor, land, and money on a market. On the other hand, private companies are notcapable of producing and selling the fictitious commodities. The difficulty is obvious: In a market economy, enterprises depend on markets for the fictitious commodities, but such an economy is unable to produce them. This means that the market system depends on external forces. Certainly, this is also true for other institutions and social infrastructures that only the state can provide. However, the fictitious commodities are different in that they cannot be understood as part of the extra-economic framework. Labor, money, and land are economic factors; they are the condition sine qua non of the market system. No self-regulation is conceivable without including the fictitious commodities. What legal scholars with regard to the secular state call the Böckenförde dilemma in the case of fictitious commodities affects economic liberalism directly. The market system is unable to produce and reproduce itself spontaneously. The economic mechanism lives by prerequisites it cannot create. Social institutions are required to provide what for the functioning of a market system is indispensable. Only society can provide the commodities on which a market economy is based. Therefore, in a market society, the economy is not—and can never be—a functional machinery. “Laissez-faire economy was the product of deliberate State action,” as Polanyi (2001, p. 147) stated, summing up the nineteenth-century answer to the dilemma. The different institutions that coordinate economic activities are the outcome not of functional pressure but of a political struggle around the (de)commodification of the fictitious commodities. “Market economies are polities,” to paraphrase the felicitous title of a book edited by Christian Joerges, Bo Stråth, and Peter Wagner (2005).In other words, an ideal market society presupposes the political creation and regulation of particular social institutions whose purpose is to simulate market conditions. Unemployment insurance, health care, union legislation, central bank acts, land property rules, and environmental regulations are indispensable for transforming labor, money, and land into commodity-like entities. Here a conflict between the social nature of the task and its economic role arises. From the perspective of the market system, these institutions fulfill the function of market makers. However, from the viewpoint of society, they allow for various forms of political regulation and economic planning, taking into account the social needs of the different strata of society. It is this tension between their political roots and their economic function within the market system that puts these institutions at the center of the political struggle. Since law cannot ignore prevailing ideals, worldviews, and external expertise, it plays a contradictory role in this process, functioning as a vehicle for commodification and political regulation.In TGT Polanyi showed that from the beginning, law played a key role in the process of commodification. In England, three legal regulations were crucial:Even if a market society presupposes the commodification of all three fictitious commodities, for reasons of space I will concentrate on money. The crucial point is to understand that the nineteenth-century gold standard was primarily not an economic but a political system.In the first decades of the century, substantially inconvertible paper money circulated in England. The commercial banks—and their theoretical advocates, the so-called Currency School—pushed for the right to provide money according to the banks’ calculations. In contrast, the supporters of the Banking School argued that this would lead to the risk of an overissuance of notes. The essential feature of the banking system created by the abovementioned Peel’s Bank Act was to keep the supply of money artificially scarce by linking the amount of banknotes to the quantity of gold in the issuing department of the Bank of England (BoE). By law, political control and the discretionary influence of the government on money and banking were reduced to a minimum.Over the course of the century, the commodification of labor, money, and land in England set in motion a transformation on a global scale. Relying on bank money, the market system generated a previously unknown social and economic dynamic. In the last decades of the “long” nineteenth century, Polanyi (2001, p. 136) commented, “a new way of life spread over the planet with a claim to universality.” The international gold standard gave birth to a worldwide system, in which the constitutional regimes became almost the corollary of the gold standard.Here we can observe in outline two problems that we encounter again in Europe today: (1) Given the legislation that forced central banks to limit the supply of money, the international gold standard not only limited the British government’s room for maneuver, but it confined also, and often even more strictly, the policy space in the other countries. The open market for money and finance created international economic and political interdependencies, which reached deeply into society and undermined democratic aspirations. Social legislation, labor unions, and budgetary and monetary policy were forced to accept the priority of the external monetary stability even if this was in contradiction to national interests. (2) The variety of socioeconomic environments, institutional traditions, and sociopolitical objectives in different countries was negated. The gold standard forced the individual countries to adapt to the liberal economic model with its universal aspirations.The BoE functioned as the conductor of the global monetary orchestra. Polanyi introduced two categories to describe the international dependencies in this period: “anarchistic sovereignty and ‘justified’ intervention in the affairs of other countries” (Polanyi 2001, 261). On the one hand, sovereignty was “anarchistic” insofar as under the gold standard and the prevailing system of unregulated foreign trade, governments lacked any power with respect to international economic affairs. The treatment of trade as a relationship between private undertakings made effective international (political) economic cooperation between states impossible. On the other hand, interventions were “justified” whenever the budgets, finances, and currencies of debtor countries required control. Given the rigidities of the economic system, Polanyi underlined that “the peoples of the world were institutionally standardized to a degree unknown before” (Polanyi 2001, 261).At the same time, however, the inelasticity of the gold supply resulted in a deflationary bias that spread over the world. Even if central banks tried to introduce some doses of flexibility, the system required the adjustment of wages and prices to the current account balances, affecting both the opportunities for profit and the living conditions of large sections of the population. Such a rigid system could survive, Polanyi summarized, only as long as popular democracy was suppressed. Confronted withIn nineteenth-century England, the gold standard and popular democracy were irreconcilable. This explains why attempts to restore the former in the 1920s were bound to fail. Barry Eichengreen took up Polanyi’s point when he pointed out that after the First World War, “the spread of universal suffrage and … the consequent politicization of the policy environment … had destroyed the viability of the gold standard itself” (Polanyi 2001, 233–34). As long as prosperity prevailed, the conflict could be contained. Not so in crisis situations. The restored international gold standard collapsed in 1931.The European Monetary Union (EMU) is at the heart of current debates on the crisis of European integration. Whether Streeck (2014, p. 185) calls the EMU “a political mistake” or Habermas (2012, p. 3) criticizes the “construction flaw of a monetary union,” they share a focus on the Maastricht process. Obviously, this interpretation ignores the fact that the crisis also includes countries—among others the United Kingdom, Poland, and Hungary—that have never been part of the EMU.If we look at the crisis from Polanyi’s perspective, the focus shifts. Not the EMU but the Single European Act, signed in 1986, emerges as the turning point. The single market program was by no means the deregulatory exercise that the European Commission had presented it as being. It was about developing competition throughout the European Union, including markets for labor, land, and money. The novel feature of the program was that it aimed at creating cross-national markets for the fictitious commodities between democratically constituted countries. This is not to say that markets for genuine goods do not cause interdependencies; however, the political character of the process of commodification of the fictitious commodities produces interdependencies of a different quality. Economic, monetary, fiscal, income, and social policy decisions in one country affect directly all other countries participating in the single market. They create political interdependencies, which, if we take Habermas’s understanding that “democratic self-government means that the addressees of mandatory laws are at the same time their authors” (Habermas 2012, 14), is incompatible with national democracy.Why did Jacques Delors and the European Commission nevertheless argue for the creation of Europe-wide markets for the fictitious commodities? Did they underestimate the political costs? Or did they believe that the economic benefits outweighed the loss of political self-determination?It is important to keep in mind that the discussions within the economic discipline never led to the consensus that the European Commission assumed. David Ricardo (1817) had already argued that markets for production factors are by no means necessary in order to enjoy the advantages of the international division of labor. In the twentieth century, declared supporters of free trade such as Gottfried Haberler (1930) and Jagdish Bhagwati (1998) took the same line. Recently, an IMF Staff Paper evaluating empirical studies on the effects of financial globalization concluded that there is evidence not of direct economic gains but rather of political effects: “Our interpretation of the newer literature is that … financial openness can … impose discipline on macroeconomic policies” (Kose et al. 2009, 10). In Europe, the internal market program was met with strong approval by the neoliberal camp. It is reasonable to assume that with the single market, Europe made the political turnaround that the Anglo-Saxon world had already accomplished with Thatcher and Reagan.Be that as it may, the commodification of labor, land, and above all money changed the rules of the game.1 To remain within the context of monetary relations: Open financial markets transformed the European Monetary System (EMS) into an arrangement that came close to what McKinnon (1988) had defined as the “gold standard without gold.” Although the EMS was intended as a symmetrical arrangement, under the conditions of open financial markets the most hard-nosed national central bank, the Deutsche Bundesbank (DBB), assumed the role of a kind of European central bank. The monetary authorities of other European countries were forced to adapt. Recall that in autumn 1992, the conflicts that arose out of these political dependencies nearly put an end to European monetary integration. The different conditions—most European countries were in recession, while Germany was experiencing the unification boom—placed incompatible demands on monetary policy. In this conflict, the DBB acted not as a European but as a German central bank, raising interest rates to record levels. In September 1992, the system faltered. The Italian lira and the pound sterling were forced out of the exchange rate mechanism. Great Britain definitively turned its back on monetary integration, while in Italy a political earthquake shook the party-political landscape.Streeck (2014, p. 186) calls for “a new European monetary system” built on Keynes’s model of fixed but adjustable exchange rates. Now, Keynes was well aware of the fact that systems such as the Bretton Woods System (or the original EMS) are incompatible with transnational financial markets.2 They can function only as long as capital movements are politically controlled. The internal market program destroyed these conditions.Fatally, the Maastricht Treaty did not pursue the goal of reducing political interdependencies but was limited to replacing asymmetry with the all-encompassing dependence on a supranational, technocratic institution that is apparently separate from the political sphere. The German economist Horst Sievert (1993, p. 18) exposed the core idea of the EMU when he remarked, “What is decisive, is that in the monetary union the individual state must pay its debts with money that it cannot produce itself.”3 In the European type of monetary union, not the political authorities but technocrats and private financial institutions control the currency in which public debt is denominated. While in countries with their own currencies the government can turn to its central bank in a time of need, in the EMU, as we have seen in the case of Greece, state bankruptcy becomes a real threat.The financial and economic crisis has revealed the utopian character of the idea of imposing discipline through markets. To touch on just two aspects: (1) Since then, the socioeconomic heterogeneity between the countries has found new forms of expression. By creating long-term interest rate differentials, the crisis has spatially divided what was conceived as a single European capital market. Paradoxically, those countries most dependent on cheap credit are penalized by less favorable financing conditions. (2) If the demand for money and credit is insufficient, efforts to keep the money supply scarce lose their purpose. Neither the Public Sector Purchase Program (PSPP) adopted in 2015 nor the Pandemic Emergency Purchase Program (PEPP) can be derived from theoretical principles based on the commodity fiction of money. The coronavirus crisis is, as Peter Bofinger (2020) suggests, “the hour of Modern Monetary Theory”—an approach that until recently was marginalized by mainstream economics because it regards money not as a commodity but as a means of payment.To overcome the crisis of European integration, two alternatives are usually proposed: deepening integration, “an ever closer union,” or downscaling of integration, defending democracy on the nation-state level. More than seven decades ago, Polanyi already envisaged a third possibility: political cooperation between self-determining nations. Polanyi was in favor of (a) the international division of labor and (b) the liberty of the individual countries “to organize national life at will” (Polanyi 2001, 262). He was (c) aware that both could be achieved only if the commodification of labor, money, and land was restricted. His ideas were indeed aimed at politically controlled regional cooperation between countries that would maintain and develop their particular characteristics. In the final chapter of TGT, he highlighted:The link between the removal of the fictitious commodities from the market and the emergence of a variety of new societies is the crucial point. In another well-known essay published shortly after TGT, Polanyi outlined his idea of a global economic order by contrasting his concept of “regional planning” with that of “universal capitalism” (Polanyi 2018b). For Polanyi, a variety of human societies was not only a fact but also a normative value. It must suffice here to recall his last project, the magazine Co-Existence, which explicitly aimed at the strengthening of peaceful international cooperation.4From this perspective, the debate on the ECB cannot be limited to questions of Outright Monetary Transactions, negative interest rates, state financing, and price stability. The question of how the monetary authorities of a heterogeneous European Union can and should act has to go back to the root problem, the commodification of money. To bring Polanyi’s ideas to Frankfurt would mean at least:However, from the point of view of the commodity fiction, the erosion of the predominance of formal legal rules in the mid-1980s, the emergence of the “regulatory state,” the turn toward governance, and finally the spread of “executive managerialism” (Joerges and Weimer 2013) since the financial crisis appear as a series of functionally necessary adjustments to an originally incomplete regime. As long as this vision prevails, the tensions between increasingly technocratic rule and democratic control are likely to persist. In the light of Europe’s ever-growing diversity, a fundamental redesign of the project, including a reconceptualization of European law that overcomes the fiction of an apolitical integration process, is necessary and, indeed, overdue. Polanyi’s analysis can provide the economic and sociological premises for such an endeavor. However, his writings also show that, especially in the twentieth century, social transformations that would have been necessary proved impossible to implement. We should be prepared; the possibility of some kind of “fundamental shock” to the integration project cannot be ruled out.Claus Thomasberger is a sociologist and economist whose main fields of research are political philosophy, history of economic thought, international political economy, European integration and social ecological transformation. Until 2017, he was Professor of Economics and Foreign Economic Policy at the Berlin University of Applied Sciences. He has been a visiting Professor at the University of Knoxville, the Duke University, and the Vienna University of Economics and Business. He is a member of the Board of the Institute for Ecological Economy Research, Berlin, the International Karl Polanyi Society, Vienna, and of the Executive Committee of the Karl Polanyi Institute of Political Economy, Montreal. Among his publications are: Chronik der großen Transformation, Artikel und Aufsätze von Karl Polanyi 1920-1947 (3 vol.) (with M. Cangiani and K. Polanyi Levitt), 2002-2005; Der neoliberale Marktdiskurs (with W. Ötsch), 2009; Das neoliberale Credo, 2012; Auf der Suche nach dem Ökonomischen (with R. Lucas and R. Pfriem), 2018; Karl Polanyi’s Vision of a Socialist Transformation (with M. Brie), 2018; Karl Polanyi. Economy and Society. Selected Writings (with M. Cangiani), 2018.

Karl Polanyi and substantivism in economic development - Rodrigues, Waldecy; Santos, Nayara Silva Dos (Brazilian Journal of Political Economy, 2020)
ABSTRACT A reading of Karl Polanyi’s work gives us a broader and more plural view of the development process beyond the exclusively economic dimension. This scientific text aims to recover the theoretical contribution of Karl Polanyi and its contribution to the understanding of the development process from a plural and substantive conception of economy. The key lesson learned in this research is that regardless of a country’s economic system, one should pay attention to the existing institutional variety and complexity of its cultural and social mosaic. True development will only be achieved if it is structured with effective public policies in order to promote this heterogeneity to the maximum possible social welfare.
Keywords: Economic development; Karl Polanyi; plural economy

On the Nature of the Countermovement: A Response to Stuart et al.’s ‘Climate Change and the Polanyian Countermovement: Carbon Markets or Degrowth?’ - Carton, Wim (New Political Economy, 2020)
In a recent article for this journal, Stuart, D., Gunderson, R., and Petersen, B. [(2017). Climate change and the Polanyian counter-movement: carbon markets or degrowth? New political economy, 1–14. doi:10.1080/13563467.2017.1417364] discuss solutions to climate change in terms of Karl Polanyi’s concept of the double movement. They set up their argument as a critique of my own article on the topic to make the point that carbon markets do not constitute a genuine form of such countermovement. I’m sympathetic to the critique of carbon markets that the authors present, as well as their discussion of degrowth, which mirrors a by now extensive literature demonstrating the pitfalls respectively the necessity of these diametrically opposed approaches to the current socioecological crisis. However, in setting up their case the authors provide an overly optimistic reading of Polanyi that I believe misses a crucial part of his argument, a reading that at least partly explains our differences in opinion. This commentary offers a friendly critique of Stuart et al.’s use of Polanyi and clarifies the argument in my previous text that the authors take issue with.
Keywords: Polanyi; carbon markets; climate change; commodification; countermovement

Karl Polanyi and Twenty-first-century Capitalism - Desai, Radhika; Levitt, Kari Polanyi (Manchester University Press, 2020)
As far right movements, social disintegration and international conflict emerge from the decay of the neoliberal order, Karl Polanyi's warnings against the unbridled domination of markets, is ever more relevant. The essays in Karl Polanyi for the 21st Century extend the boundaries of our understanding of Polanyi's life and work. They will interest Polanyi scholars and all interested in socialism and our future after neoliberalism. One asks whether, following Keynes and Hayek, Polanyi's ideas will shape the twenty-first century. Some clarify, for the meaning of money as a fictitious commodity. Others resolve difficulties in understanding the building blocks of Polanyi's thought: fictitious commodities, the double movement, the United States' exceptional development, the reality of society, and socialism as freedom in a complex society. And yes others explore how Polanyi sheds light on income inequality, world systems theory, comparative political economy.
Keywords: capitalism; double movement; neoliberalism; reality of society; socialism

The utopian character of the counter-movements : reading Karl Polanyi in the twenty-first century - Rondelez, Pieter (13th Global Studies Conference : Globalization and Social Movements : Familiar Patterns, New Constellations?, 2020)
In the introduction of the 2001 edition of The Great Transformation, Fred Block argues that we all have much to learn from the insights of Karl Polanyi. Relying on Polanyi’s arguments in the Great Transformation is not only useful in order to understand the history of market liberalism, but also for the contemporary debate on globalization and its contestation. The work of Karl Polanyi is inspiring a lot of academics nowadays who are studying the global uprisings since 2008. Some academics – like Block - argue that neoliberals embrace the same utopian visions of their predecessors which lead to counter-movements that are resisting marketization processes and its political and economic consequences. Relying on Polanyi’s work, I point to a danger of interpreting the current neoliberal order as a similar trend towards marketization as in the period that Polanyi is dealing with in his book. Misinterpreting the current marketization project raises questions not only about the feasibility of re-embedding the economy back into society, but also about the desirability of disembedding society from the economy. In concrete, I argue that the utopian character shifted from the marketization project to the counter-movements that are trying to resist and change it. This also raises questions about the role of social scientists in (studying) the process of social change in the twenty-first century.
Keywords: contemporary relevance; countermovement; globalization; marketization; utopia

The Moral Economy of the Capitalist Crowd: Utopianism, the Reality of Society, and the Market as a Morally Instituted Process in Karl Polanyi’s The Great Transformation - Somers, Margaret R. (Humanity: An International Journal of Human Rights, Humanitarianism, and Development, 2020)
In an age of egregious inequality and rising authoritarian, many call for a new “moral economy” and turn to Karl Polanyi’s The Great Transformation for inspiration. Yet Polanyi’s great insight is that those who cannot reckon with the moral economy of “market justice”—the claim that market outcomes, however unequal, are morally just—fail to understand the power of capitalism. Justified by its original claim to rest on natural science, market justice laid the predicate for democracy as mortal threat. Polanyi reveals market justice as based not on natural law but on predistributive political power, and builds his democratic socialist vision on the “reality of society.”
Keywords: market justice; moral economy

Economy–society tensions in the Eurozone: the "anti-democratic virus" revived - Markantonatou, Maria (Capitalism in Transformation, 2019)
This chapter draws on Polanyi’s analysis of the economy-democracy tension to discuss today’s crisis in Greece and the Eurozone. First, some of the economic and social effects of the Greek austerity programme are discussed with reference to his observations on liberal international interventionism in the interwar period. Secondly, the chapter looks at the ways in which democratic outcomes (elections, referenda, parliamentarian decisions, etc.) in Greece and elsewhere were, during different crisis episodes following 2010, put aside in favour of market discipline and austerity doctrines. It is argued that Polanyi’s thesis on the “mutual incompatibility” between capitalism and democracy (the core of what he termed the “anti-democratic virus”) is crucial for understanding today’s crisis and crisis management in the framework of Eurozone’s liberalism.
Keywords: Eurozone crisis; Greece; fascist virus

Risk Markets and the Landscape of Social Change - Breger Bush, Sasha (International Journal of Political Economy, 2016)
With the critical derivatives and financialization literatures as background, I argue in this essay that risk markets (i.e., derivatives and insurance markets) play an integral role in insulating global neoliberalism from popular and elite demands for reform, as well as from the related imposition of new forms of government intervention. Inspired by Polanyi’s “double movement” and Bryan and Rafferty’s (2006) notion of “blending” in derivatives markets, the argument rests upon the insight that risk markets transform social risk into individual cost, resulting in potentially large but subtle implications for global prospects for social change. After providing a taxonomy of risk instruments that emphasizes their growing role in managing important social risks, I describe and provide brief case studies of two pathways through which risk markets help to protect the neoliberal order from political threats. The first involves the political positioning of insurance and derivatives instruments and markets as “solutions” to global social problems. The second involves the manner in which insurance and derivatives products generate “political moral hazards” that discourage support for new kinds of global policies and structures. As such, this essay contributes to the growing body of critical political economy literature on financialization, financial innovation, and derivatives and insurance markets.
Keywords: Polanyi; derivative securities; derivatives; finance; financialization; innovation; insurance; insurance exchanges; neoliberalism; social change

'Freedom in a Complex Society': The Relevance of Karl Polanyi's Political Philosophy in the Neoliberal Age - Cangiani, Michele (International Journal of Political Economy, 2012)
Karl Polanyi's demanding vision of freedom and democracy seems far from the reality of our times and current ideologies. However, a deeper analysis reveals the ability of his political philosophy not only to find a solution of the paradox of liberty in spite of social constraints, indeed through social institutions, but also to answer the most important practical question with which we are confronted: that of improving, as Polanyi says, "our chances of survival." The conception synthetically expounded in the last pages of The Great Transformation can be better clarified through some of Polanyi's recently published manuscripts of the interwar period. A reference is also to be made to Karl Marx in the first place but also to other more recent authors.
Keywords: capitalist systems; elections; freedom in a complex society; history of economic thought; legislatures; lobbying; political philosophy; political processes; rent-seeking; voting behavior

'Planning for Freedom': Hayekian and Polanyian Policies in Latin America - Valderrama, Paula (International Journal of Political Economy, 2012)
In the first part of the paper, the concepts of "planning for freedom" by Friedrich Hayek and Karl Polanyi are compared. Hayek rejects "central planning" and also all kinds of "planning for specific aims," but he defends the principle of "planning for competition" as the main condition of a free society. This principle includes the provision of a pertinent institutional framework and state intervention to create markets in spheres of society previously ruled by nonmarket principles. Polanyi agrees that "planning" is necessary in order to achieve freedom in a complex society, but he criticizes the liberal understanding of freedom as a vain "illusion" and considers the principle of "planning for competition" a political ideal that endangers the cohesion of societies. The starting point of Polanyi's argumentation is Karl Marx's theory of reification, but he goes beyond this, complementing it with the concept of "social freedom" based on knowledge and responsibility. Considering the Latin American experience in recent decades, the paper compares Hayekian and Polanyian concepts of "planning for freedom" in their real political and social dimensions.
Keywords: HAYEK, Friedrich A. von (Friedrich August), 1899-1992; Latin America; capitalist systems: planning, coordination, and reform; formal and informal sectors; freedom; history of economic thought: individuals; institutional arrangements; planning models; planning policy; political processes: rent-seeking, lobbying, elections, legislatures, and voting behavior; shadow economy